Distinct molecular programs drive compensatory versus normal growth in Qihe gibel carp (Carassius gibelio var. Qihe): integration of muscle transcriptomics, histology and physiology - Yongjing Li; Ling Lv; Yujiao Jin; Yanzhi Wang; Yuqi Li; Lei Wang; Meng Zhang; Xuejun Li; Limin Wu (Aquaculture, 2027)

Emergence of an optrA-positive Enterococcus faecalis ST699 lineage in animal-derived foods in Beijing, China - Chuncai Liang; Yizhu Chen; Xuan Wu; Rui Chang; Wenkai Cao; Ling Wei; Hui Li; Bing Shao (International Journal of Food Microbiology, 2026)

A mechanism-constrained large language model-based intelligent diagnosis framework for bridge defects - Hui Jin; Si-Ming Zhou; Han Chen; Zhi-Yu Xie; Feng Li; Yong Li; Jian-Feng Zhu; Yi-Feng Ling; Zhi-Min Wu; Xiang-Ming Zhou (Engineering Structures, 2026)

Epigallocatechin-3-gallate enhances in vitro maturation and developmental competence of sheep oocytes - Ruigang Wang; Zhenliang Zhang; Jesse Oluwaseun Ayantoye; Wen Wu; Jingjing Wang; Yucheng Liu; Zhanmin Lv; Lei Gao; Jianhong Ni; Changbin Liu; Ling Tang; Yuxuan Hua; et al. (Theriogenology, 2026)

STCAFormer: Spatio-temporal cross attention based transformer for fusion of remote sensing images - Jun Li; Xiaowei He; Yantai Yang; Qinghong Sheng; Zhaocong Wu; Bo Wang; Xiao Ling; Xiang Liu; Yu Liu; Fan Gao; Libo Wang; Matthieu Molinier (Remote Sensing of Environment, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Coupled wind-rain-subsidence effects on soil erosion dynamics in an arid mining area: Insights from CFD-DEM and physical simulations - Chuning Ji; Ziheng Song; Chuanjiu Zhang; Yanli Huang; Ling Wu; Xiaobin Li; Xiaolong Wang; Ruimin He; Yangnan Guo; Jian Zhang; Chuanxu Wang; Yu Tian; et al. (CATENA, 2026)

Hierarchical transcription factor interaction network: RsrF mediates dual-layer regulation of plant-polysaccharide-degrading enzyme biosynthesis in fungus - Mei-Ling Pang; Wen-Tong Li; Ze-Yu Deng; Di Tian; Yan-Hao Zhao; Dian-Qi Wu; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (Bioresource Technology, 2026)

Vegetation restoration patterns shape microbial functional coupling of soil carbon and nitrogen in arid coal-mining areas - Chuning Ji; Ziheng Song; Suo Zhang; Junliang Dong; Chuangang Gong; Jian Zhang; Guiyuan Wang; Xiaobin Li; Rulin Xiao; Ling Wu; Jihong Dong; Yanli Huang (Applied Soil Ecology, 2026)

Thermal modulation of nearshore groundwater flow and solute transport in a tidally influenced coastal aquifer bounded by a mild-slope beach - Xuan Wu; Yu Fan; Xiaogang Chen; Chengji Shen; Ling Li (Advances in Water Resources, 2026)

Sectional load characteristics and load transfer mechanisms of a 15 MW semi-submersible floating offshore wind turbine platform - Ben He; Yibo Wang; Shuaibing Zhang; Shuijin Li; Ling Wan; Weiwei Wu (Ocean Engineering, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Three-dimensional interpenetrating network assembled by Co-Fe-Mo sulfides anchored on N-enriched porous carbon/graphene oxide nanosheets for efficient oxygen evolution reaction - Qilin Wu; Weixin Li; Cheng Gong; Ling Zhuang; Haijun Zhang; Lei Zhao (Journal of Environmental Chemical Engineering, 2026)

Insights into the analysis of microbial communities in fermented foods from the perspective of DNA-based techniques - Hao Zhou; Lijun Yan; Ling Zhang; Ruijuan Wang; Shanshan Xu; Boyang Xu; Xuefeng Wu; Xingjiang Li (Food Research International, 2026)

New perspectives on serum-free cell culture: Harnessing microbial resources for innovative media development in food biomanufacturing - Qinya Niu; Nuo Chen; Qinghua Ye; Qingping Wu; Yuwei Wu; Xinyu Zhao; Qihui Gu; Xianhu Wei; Youxiong Zhang; Ying Li; Ling Chen (Food Research International, 2026)

Effects of endogenous fat content on gel network, physicochemical properties, and flavor of plant-based coconut yogurt: a comparative study with dairy-based counterpart - Xuyan Zong; Xinyu Zhang; Ling Wu; Shujuan Shao; Junya Zhou; Wei Dai; Chunli Liu; Li Li; Guangbin Ye (Food Research International, 2026)

Conversion of tropical peat swamp forest to oil palm plantations shifts prokaryotic beta diversity and reshapes the community structure, composition, and co-occurrence patterns of soil biota - Farhana Adilah Zahari; Sharon Yu Ling Lau; Meldon Fienberg Kelbin; Gaik Ee Lee; Umar Hussaini Tarmizi; Qiqian Wu; Xiangzhen Li; Lars Vesterdal; Jan Frouz; Chengming You; Amirah Alias; Kai Yue; et al. (Forest Ecology and Management, 2026)

Integrated metabolomic, transcriptomic, and proteomic analyses reveal changes in the non-volatile metabolite profile of LED light–withered oolong tea - Qiuming Li; Yucheng Zheng; Hongzheng Lin; Yongpeng Wu; Jihang He; Xinru Yu; Mingxing Ling; Xiang Li; Jinke Lin; Zhilong Hao; Xinchao Wang; Yun Sun (Food Chemistry, 2026)

Establishment of a novel brain cell line from grass carp (Ctenopharyngodon idella) with high transfection efficiency and CRISPR/Cas9-mediated genome editing capacity - Zi-Ling Qu; Tao Liu; Tang-Kai-Yuan Qin; Hua-Mei Yue; Ling Huang; Rui Ruan; Chang-Song Wu; Huan Ye; Chuang-Ju Li (Fish & Shellfish Immunology, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Beyond direct toxicity: Cross-system regulation and the gut-retina axis in pollutant-induced visual dysfunction in fish - Yiqun Wu; Yiwei Liu; Tengzhou Li; Ling Liu; Ping Li; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A bioinspired flavin-based catalytic construct enabling intracellular NAD+/NADH redox regulation for mitigating skin aging - Jiani Xiang; Qian Ling; Li Yan; Ying Xia; Peizhen Lou; Zhen-Gang Wang; Ting Li; Huiling Wu (Chemical Engineering Journal, 2026)

Dynamic light-scattering metamaterial for smart window application - Haifeng Nan; Ling Wang; Hanrong Wu; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2026)

CO2 sequestration via mixed hydrate formation in depleted Class I, II, and III hydrate reservoirs: A comparative study from laboratory to field scale - Hongyu Ye; Ling-ban Wang; Jie Li; Daoyi Chen; Xuezhen Wu; Dayong Li; Guang-jin Chen; Chang-yu Sun; Mucong Zi (Chemical Engineering Journal, 2026)

Development and validation of an E2 based indirect ELISA for serological detection of porcine Getah virus - Zijun Xiang; Wenjing Tian; Dong Li; Meiqi Liu; Zhicheng Han; Qiong Wu; Zhong Peng; Ling Zhao; Bin Wu; Danna Zhou (Veterinary Research Communications, 2026)

Ferulic acid liposomes improve diabetic EPC angiogenesis by upregulating the AMPK/KLF4/FAM3A pathway - Xiao-ling Zou; You-yuan He; Xi Zhang; Wen-xiao Hu; Si-ying Li; Xiang-nan Liu; Shao-ye Qiao; Ying Wang; Biao Luo; Si-jia Zhao; Qiao Liu; Wu Xiong (In Vitro Cellular & Developmental Biology - Animal, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Modulation of JAK/STAT signaling pathway in the ovine thymus and lymph node during early pregnancy - Chenxu Wu; Jingjing Li; Yaqi Zhang; Qianqian Shi; Leying Zhang; Ling Yang (Veterinary Immunology and Immunopathology, 2026)

The potential role of the Sox9a protein in regulating cyp19a transcription and ovarian development in the olive flounder (Paralichthys olivaceus) - Chang Shu; Lijuan Wang; Congcong Zou; Xungang Tan; Yuxia Zou; Zhihao Wu; Yan Liu; Qiaowan Wu; Ling Wang; Guoyu Wang; Ze Li; Feng You (Theriogenology, 2026)

Cumulative deformation characteristics of offshore wind turbine structure under long-term marine loading - Zhang Bing-jie; Zhang Xiao-ling; Zhou Guang-li; Wu Yang (Soil Dynamics and Earthquake Engineering, 2026)

Effect of dissolved organic matter chemical characters on microbial community of paddy soils in subtropical China - Yaxin Liu; Yingcong Ye; Daming Li; Rong Cui; Xiaoli Liu; Ling Chen; Meng Wu; Jia Liu; Xi Guo; Ming Liu (Soil and Tillage Research, 2026)

Tide-induced groundwater table fluctuations in a coastal unconfined aquifer with the seaward boundary featuring a slope break - Huawen Zhao; Ye Ma; Xuan Wu; Xiaogang Chen; Ling Li (Journal of Hydrology, 2026)

Deciphering the carrier potential of microplastics aged in freeze-thaw soils: Multiscale insights into mechanisms for antibiotic adsorption amplification - Wen-hao Yang; Jian-yong Wu; Kong-yan Luo; Ling-li Ma; Bin Yan; Jin-song Guo; Jie Zeng; Yi-zhi Pei; Jun-min Gao (Journal of Hazardous Materials, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Anchoring cubic CeO2 on the CdS surface to construct a heterojunction enables highly efficient visible-light photocatalytic degradation of tetracycline - Shuang Luo; Jiayi Peng; Yuxin Zheng; Liang Wu; Renhui Ling; Yixuan Gong; Zhongxiao Zhou; Sanshan Li; Yulin Zhang; Yu Hu; Jianjian Wang (Environmental Research, 2026)

Long-term exposure to air pollution, proteomic aging clocks, and liver-related outcomes in Chinese adults - Yating Huang; Dong Sun; Axing Lv; Jun Lv; Canqing Yu; Dianjianyi Sun; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Dan Huang; Xiaoming Yang; et al. (Environmental Research, 2026)

Microbial-driven transformation of dissolved organic nitrogen in estuarine waters: mechanisms and environmental implications - Pengju Li; Jia Yang; Yunchao Wu; Jinlong Li; Feng Ye; Yuanbi Yi; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Environmental Research, 2026)

Evolution of cracks in red-bed mudstone under the coupling of drying-wetting cycle and temperature: From microscopic mechanism to a kinetic model - Guodong Zhang; Sixiang Ling; Chengjun Xiao; Hongwei Liu; Xiaoning Li; Rui Deng; Xiyong Wu (Engineering Geology, 2026)

Exogenous auxin mediates the NnARF9–NnSUS2 module to regulate sucrose synthesis in lotus leaves (Nelumbo nucifera) - Peng Wu; Yuda Guo; Wenjing Ling; Chenyan Qu; Mengnan He; Jin Hao; Jing Zhang; Liangjun Li (Planta, 2026)

Helicobacter pylori phages: resource landscape, translational challenges, and engineered antibacterial strategies - Zhenkai Li; Ling Chen; Shixuan Huang; Ying Zhang; Fei Yao; Peihao Huang; Yanyan Shang; Xiaoming Yuan; Xinqiang Xie; Ying Li; Qingping Wu (Archives of Microbiology, 2026)

New enantiomers from Ficus variolosa Lindl. ex Benth. and their anti-inflammatory and neuroprotective activities - Ling-Fei Tong; Yu-Qiong Lu; Qing Li; Shun Pan; Hui Li; An Jin; Wen-Ming Wu (Natural Product Research, 2026)

Ammonium and heat stress reveal divergent life-history strategies and environmental resilience in coral-symbiont dinoflagellates - Yulin Huang; Shuaishuai Wu; Jiamin He; Shutao Wu; Zhen Shen; Yujie Wang; Ling Li; Senjie Lin (Coral Reefs, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

Correction: Salvia miltiorrhiza (Danshen) and its extracts in the alternative treatment of diabetic nephropathy: mechanisms and clinical perspectives - Lu Song; Yan Li; Huakui Zhan; Ling Wu; Li Tang; Xinyu Wang; Qinyuan Deng (Journal of Natural Medicines, 2026)

Heavy metals or emerging organic contaminants: Which drive zebrafish embryo toxicity in printed circuit board manufacturing wastewater? - Ling Zhang; Lingzhi Xie; Huizhen Li; Yujun Tong; Xinyan Wu; Hao Hu; Jingru Zhang; Peipei Meng; Jianjun Li; Jingchuan Xue; Qian Tan; Jing You (Water Research, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Solving excited states for long-range interacting trapped ions with neural networks - Yixuan Ma; Chang Liu; Weikang Li; Shun-Yao Zhang; Lu-Ming Duan; Yukai Wu; Dong-Ling Deng (Science Bulletin, 2026)

Experimental and numerical investigation of evaporation, heat transfer, and ignition of RP-3 fuel on curved hot surfaces - Ling Yang; Chen Wang; Jie Ji; Xin Li; Hao Wu; Wenjie Xu (Process Safety and Environmental Protection, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

Thermodynamic-kinetic integrated analysis of heat exchanger scaling and control techniques: A case study from a potash processing plant in northwest China - Qian Zheng; Hengtao Deng; Zhen Wang; Huanhuan Song; Ling Xia; Gao Tang; Shaojie Huang; Zhuolin Xie; Yingying He; Hang Li; Nasriddinov Zamoniddin; Hojiev Saidmukbil; et al. (Journal of Cleaner Production, 2026)

Dietary supplement Forskolin improves MASLD through hepatocyte-macrophage crosstalk via the GLUT1/ABCF1-HNF4α axis - Sai-Hu Liu; Mei-Yan Xuan; Chong Gao; Shuang Zheng; Jia-Xin Zhang; Li-Hua Lian; Ji-Xing Nan; Zhen-Yu Cui; Yan-Ling Wu (Food Research International, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

Land-use-driven terrestrial inputs and fresh-seawater mixing jointly shape sediment organic nitrogen in the Pearl River Estuary - Jia Yang; Pengju Li; Yunchao Wu; Jinlong Li; Feng Ye; Yuanbi Yi; Shicheng Lin; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Science China Earth Sciences, 2026)

Elevation-dependent factors of soil organic carbon in food legume-based agroecosystems - Qi Liu; Xuebin Xu; Shuang Wang; Liang Wei; Yongfu Li; Wenli Ling; Xiang Wan; Wu Xiang; Zhenke Zhu; Yakov Kuzyakov; Qiong Liu; Tida Ge (Plant and Soil, 2026)

FengYuan: An End-to-End Global Weather Forecasting Model Driven by Multi-Source Observational Data - Zhaoming Liang; Yang Li; Yaqiang Wang; Yiheng Shi; Junming Chen; Fenghua Ling; Enda Zhu; Hai Wang; Lei Bai; Huabing Ke; Zhongyan Hu; Xiaoxu Liu; et al. (Journal of Meteorological Research, 2026)

Revealing phenological vulnerabilities in wheat yield formation under climate warming: a process-based framework for adaptive breeding - Ming Li; Shizhao Li; Xiaoli Wu; Ling Wu; Miao Liu; Tao Xiong; Chaosu Li; Yonglu Tang (Agricultural and Forest Meteorology, 2026)

Drug-associated cytokine release syndrome: a FAERS pharmacovigilance study with complementary transcriptomic analysis - Ye Zhang; Xiang Li; Jieyu Zhang; Shudong Chen; Juxiang Zang; Dongni Wu; Jun Qin; Wei Ling (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biomechanical Evaluation of Zygomatic Implants: Intrasinus vs. Parasinus Surgical Approaches - Yu-Ling Wu; Aaron Yu-Jen Wu; Jui-Ting Hsu; Heng-Li Huang (Journal of Medical and Biological Engineering, 2026)

Exogenous methyl jasmonate enhances maize resistance by modulating secondary metabolites and suppressing Spodoptera frugiperda performance - Wenjing Li; Qingqing Ju; Ling Wang; Nina Yang; Haichen Yin; Shengbo Cong; Huaiheng Wu; Li Xue; Zhenbiao Jiao; Dong Xu; Peng Wan (Crop Protection, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

Clean heating transition in China: Technological innovation, residual emission burden, and regional inequality in northern cities - Linyan Li; Yunlong Wu; Li Zhang; Huili Wang; Jieyi Li; Lin Xiang; Xiurong Hu; Jiaxuan He; Ling Jin; Xiaojun Chen; Hui Xu; Yu Lei (Sustainable Production and Consumption, 2026)

Ca-Mg isotopic decoupling in a Neoproterozoic alkaline province: tracing crustal recycling at the Yangtze Block margin - Yvren Liu; Zhehua Li; Wenli Ling; Hui Wu; Wafa Berkana; Dong Li; Qianhe Dong (Precambrian Research, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Efficient capture of Cs+ ions by two supertetrahedral cluster-based microporous metal chalcogenides in neutral and alkaline environments - Ya-Dong Wu; Lu Yang; Zhi-Hua Chen; Hai-Yan Sun; Chuan Lv; Xiao-Ying Huang; En-Chao Li; Mei-Ling Feng (Journal of Hazardous Materials, 2026)

H3K18 lactylation-regulated ATG10 is involved in the acute respiratory distress syndrome induced by acute exposure to hydrogen sulfide through activation of autophagy in lung epithelial cells - Bingyu Ling; Ping Geng; Bowen Fan; Xiaolong Wu; Yi Yang; Jiaheng Lin; Wenjie Li; Qizhan Liu; Cheng Cheng; Jinsong Zhang; Hao Wu (Journal of Hazardous Materials, 2026)

Homothorax regulates BarH1 expression and olfactory perception in Monochamus alternatus hope - Qi-Cheng Li; Sheng-Xin Wu; Mei-Jiao Yang; Pu-Yuan Zhang; Yan-Ling Wei; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

Stable cerium isotope fractionation during basalt-rhyolite magmatic differentiation - Peng Wu; Fang Liu; Lei Li; Zhengjie Zhao; Jiaojiao Wu; Wenke Wang; Yajun An; Xin Li; Paul Savage; Mingxing Ling; Zhaofeng Zhang (Geochimica et Cosmochimica Acta, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Ecological dominance and genomic features of bacterial generalists during pit fermentation of three distinct baijiu types in Anhui Province - Hao Zhou; Boyang Xu; Ling Zhang; Lijun Yan; Ruijuan Wang; Qinxiang Xu; Chao Jiang; Anyuan Chen; Xuefeng Wu; Xingjiang Li (Food Research International, 2026)

Size-dependent lipidomics and fatty acid profiles of fat globules in buffalo milk - Shaohong Jin; Jinsu Liao; Yanan Sun; Ran Wang; Ling Li; Lianqiao Wu; Jianhuan Wei; Pengjie Wang; Fazheng Ren; Yi Wang (Food Chemistry, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

A simple method to estimate seismic subsidence in soft soil under amplitude non-stationary seismic action - Gan-Ling Xian; Jing-Yan Lan; Li-Chun Chen; Yong-Zhi Wang; Lei Wang; Zhao-Ran Wu (Engineering Geology, 2026)

Assessing the interaction of invasive species invasion risks and ecosystem services: Spatial heterogeneity and landscape mediation in Hubei, China - Junchen Chen; Lanjing Li; Xiaoping Xin; Shuya Wu; Ruiqi Zhang; Dan Fan; Zhaohua Li; Ling Wang; Kun Li (Environmental Impact Assessment Review, 2026)

Bond-strength engineering enables cooperative stabilization of Mn-rich olivine cathodes - Wenqin Ling; Yao Wu; Shan Fang; Xuerui Yang; Sisi Xiong; Yixi Li; Shuchao Zhang; Naigen Zhou (Chemical Engineering Journal, 2026)

Particle size-dependent photobiological hydrogen production in microalgal gel beads - Yan Wu; Ling-Li Yong; Xu Wang; Shao-Yang Liu; Jin-Song Guo; Fang Fang; You-Peng Chen; Peng Yan (Chemical Engineering Journal, 2026)

Boosting aqueous Zn-ion battery performance with Co2+-doped δ-MnO2/Ti3C2Tx cathode through enhanced ion transport and structural stabilization - Shuo Li; Jing Zhu; Longkun Wu; Yasong Han; Ningning Zhao; Bin Li; Shaaban M. Shaaban; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2026)

Spatiotemporally reprogramming the cardiac pathological microenvironment with injectable POM-engineered hydrogel for chronological myocardial infarction treatment - Ling Luo; Yalan Wang; Yuliang Wu; Yanlan Xie; Chenghui Liu; Chuan Zhang; Bin Li; Jing Zhou; Xiaoxue Xu; Yuan Yong (Chemical Engineering Journal, 2026)

Radiofrequency-responsive nanogel co-delivering cisplatin and EGCG for enhancing the efficacy of hepatocellular carcinoma interventional therapy by thermoresistance modulation and immune remodeling - Yaowei Bai; Mengqin Guo; Kexin Wang; Yu Lei; Jun Wu; Bo Sun; Wenlong Wu; Xiatong Bai; Yang Su; Ling Li; Yanbing Zhao; Chuansheng Zheng; et al. (Chemical Engineering Journal, 2026)

Short and long-term exposure to fine particulate matter, nitrogen dioxide and meteorological factor and the risk of glaucoma: evidence from the China health and retirement longitudinal study, distributed lag non-linear and Mendelian randomization models - Yeni Li; Ling Zhu; Miaomiao Lu; Manli Wu; Xiaoxu Zhang; Feng Shi; Xiaonan Li (International Journal of Biometeorology, 2026)

A Study on the Suitability of Operating Strategies for PV/T-Medium-to-Deep-Ground-Source Heat Pump Heating Systems Based on Peak-and-Off-Peak Electricity Rates - Dong Wei; Yu-ping Zhang; Quan-hui Liu; Yi-chao Zhao; Hao Wu; Sheng-ji Xu; Yu Cao; Jia-yuan Li; Ling-ling Bao (Applied Geophysics, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

Hybrid PSO-ML framework for predicting lateral bearing capacity of nearshore rigid piles in sloping seabed - Shao Yue; Junhui Zhang; Wenzhe Peng; Shuai Zhou; Ling Zhang; Hao Yang; Shengnan Li; Gaoqiao Wu (Marine Georesources & Geotechnology, 2026)

The role of cellular senescence in immune-metabolic features and prognosis of ovarian cancer: an integrated analysis based on single-cell sequencing and multi-omics data - Yuan Li; Mengying Bai; Ziqiong Zhou; Wenbo Wu; Haifeng Wu; Shuyi Ling; Liping Wang; Yuehui Zheng (GeroScience, 2026)

Water-quality responses and management-oriented spatial thresholds in a complex river-estuary continuum - Jiang Wu; Tang Liu; Dian-Bao Li; Li-Juan Zhang; Hua-Peng Qin; Wei-Ling Sun; Nan Xu (Water Research, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Mechanochemical elimination of antibiotics and antibiotic resistance genes using PAN@BTO piezoelectric composite - Ling Yu; Mengxiao Liu; Hanbin Wu; Li Zeng; Yang Yu (Journal of Environmental Chemical Engineering, 2026)

Differentiated biogeochemical pathways of antimony and arsenic immobilization: A comparative study on soil amendments under different remediation strategies - Yuezhong Chen; Han Tu; Pan Wu; Xuexian Li; Ling Li (Journal of Environmental Chemical Engineering, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

High prevalence and diverse patterns of multi-serotype Salmonella contamination in individual food samples in China - Xiaojuan Yang; Jiahui Huang; Ling Chen; Tingting Liu; Chengsi Li; Hui Zhao; Jumei Zhang; Qingping Wu (Food Bioscience, 2026)

Structure-driven bioaccumulation of legacy and emerging PFAS across freshwater biota and tissues: Implications for dietary exposure and age-specific risks - Wu Wen; Qinghao Wang; Lijuan Gao; Jingling Liu; Bin Sun; Nannan Chen; Kun Bao; Li Ling; Xinghui Xia (Environmental Pollution, 2026)

From surface interception to biological stabilization: successional controls on lead immobilization and microbial resilience in biocrusts - Zijia Zhang; Keqiang Zhou; Yujing Bi; J. Viridiana Garcia-Meza; Li Wu; Zhenbin Wu; Ling Xia (Environmental Pollution, 2026)

Integrating hybrid life cycle assessment to quantify carbon footprint in mariculture: Overcoming truncation errors and unveiling macroeconomic drivers - Ting Jiang; Kangni Wu; Yuanchao Hu; Guobao Song; Weiwei Sun; Gengyuan Liu; Zhaoyuan Yu; Ling Cao; Shaobin Li (Environmental Impact Assessment Review, 2026)

Functionalized polymer carbon dots with multi-level trapping structures for capacitive energy storage across extreme temperatures - Xue Li; Ling Weng; Lizhu Guan; Houyu Wang; Xiaoming Wang; Xiaorui Zhang; Ruiqun Pan; Lin Zhang; Yuhan Li; Zijian Wu (Chemical Engineering Journal, 2026)

Speciation and light-absorbing properties of carbonaceous aerosols in a typical industrial city, Taiyuan, China - Ziyong Guo; Chenhui Li; Fengxian Liu; Ying Wei; Jiajie Li; Yanting Qiu; Taomou Zong; Ling Mu; Zhijun Wu; Jiancheng Wang (Atmospheric Environment, 2026)

Correction to: Altitudinal effects on soil microbial diversity and composition in qinghai spruce forests of qilian mountain - Yiming Feng; Changming Zhao; Ling Wang; Jinhua Li; Tianwei Wu; Chunyan Lv; Ming Jin (Plant and Soil, 2026)

Benzalkonium chlorides compromise oocyte maturation and developmental competence by disrupting mitochondrial function and the SIRT3-SOD2 antioxidant axis - Khienduc Lay; Dandan Zhang; Hui Wang; Mengchan Li; Yongteng Zhang; Qimei Xu; Bo Jia; ThiHien Nguyen; Chunhuan Ren; Xiaoyan Zhou; Heng Tang; Yinghui Ling; et al. (Animal Reproduction Science, 2026)

Single-cell profiling and machine learning identify cuproptosis-related fibroblast subpopulations and fibrogenesis modulator AEBP1 in endometriosis - Erqing Huang; Jiang-Tian Li; Danhui Zuo; Ruijie Li; Qingyue Wu; Na Lin; Jinru Zhao; Huajing Wang; Yi Liu; Ling Zhang (Apoptosis, 2026)

Cryptophyllachora milletticola sp. nov., a Tar Spot‐Causing Fungus from Southwestern China - Yi‐Tong Wang; Hai‐Xia Wu; Nalin N. Wijayawardene; Cui‐Ling Gong; Zi‐Yi Li; Jia‐Yu Song (New Zealand Journal of Botany, 2026)
Cryptophyllachora milletticola sp. nov., a causal agent of tar spot, on living leaves of Millettia versicolor (Fabaceae), is described from Yunnan Province, China, based on morphological characteristics and multigene phylogenetic analysis. The current low number of described species of tar spot fungi and the scarcity of available molecular data have constrained robust and precise phylogenetic inference for this group. Future research should focus on discovering additional Cryptophyllachora and similar tar spot fungal species from diverse hosts and geographic regions, coupled with genomics datasets, to resolve their higher‐level classification and evolutionary relationships within the Sordariomycetidae. This work highlights the need to document understudied tar spot pathogens to advance the systematics of this morphologically complex group.

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Integrated in-situ electrochemical-membrane process for ammonia valorization and sustainable water reuse - Paula Jungwon Choi; Xinning Zhang; Wing Chi Au; Adel Tayara; Noman Khalid Khanzada; Yingying Xiang; Li Ling; Di Wu; Am Jang; Ho Kyong Shon; Chii Shang; Guanghao Chen; et al. (Water Research, 2026)

Plant bioavailable phosphorus content in animal manure- and sewage sludge-based char and ash: Effect of thermal treatment temperature and condition - Xuan Luo; Wei Ding; Adi Radian; Ling Tan; Yukun Sheng; Cheng Li; Zhenyu Wu; Keke Xiao (Waste Management, 2026)

Systemic inflammation moderate the association between urinary polycyclic aromatic hydrocarbon metabolites and hypertensive adults - Jing Liu; Ziwei Zhou; Xu Zhu; Gongchang Guan; Feipeng Li; Qianwei Cui; Rutai Hui; Junkui Wang; Runmiao Wu; Zhao Zhao; Hui Pang; Ling Zhu (Toxicology Letters, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Super retarding-flame wood - Sen Gao; Jing Ren; Baoping Zhang; Lixian Yang; Yiqiang Wu; Yingying Zhang; Leitao Cao; Qing Li; Chunlei Zhang; Mingyue Miao; Haipeng Yu; Shouxin Liu; et al. (Science Bulletin, 2026)

Altitudinal effects on soil microbial diversity and composition in qinghai spruce forests of qilian mountain - Yiming Feng; Changming Zhao; Ling Wang; Jinhua Li; Tianwei Wu; Chunyan Lv; Ming Jin (Plant and Soil, 2026)

Environmental triggers of acute Stanford type A aortic dissection: The roles of ambient temperature, air pollution, and workplace thermal conditions - Yeni Li; Ning Niu; Ling Zhu; Manli Wu; Xiaoxu Zhang; Xiaotong Tang (International Journal of Biometeorology, 2026)

Habitat complexity and spatial navigation: linking habitat to cognitive strategy in cyprinid fishes - Wu-Xin Li; Qing-Yin Wei; Ling-Qing Zeng; Shi-Jian Fu (Behavioral Ecology and Sociobiology, 2026)

Research on anomaly detection and correction method for remote sensing instrument calibration data based on TELSTM-ADC model - Jianhua Qu; Ping Qin; Ling Sun; Weichu Yu; Shengli Wu; Qing Wang; Dongqi Li (International Journal of Remote Sensing, 2026)

Research on forest and grassland fire detection algorithm based on Himawari-8 geostationary satellite - Shan Zhang; Yong Xue; Xiaolu Ling; Chunlei Wu; Liying Han; Zhenglong Li (International Journal of Remote Sensing, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Postharvest application of glutathione and selenium and their combination enhances quality performance of chestnut - Nannan Dong; Ling Wei; Wanfeng Wu; Yizhou Xiang; Qiannan Hu; Yaoqi Zhang; Zisheng Luo; Yunbin Jiang; Li Li (Postharvest Biology and Technology, 2026)

Development of a pH-responsive nanopesticide for efficient delivery of matrine and sustainable control of pine wood nematode - Linxi He; Zhiyi Zhao; Xixiang Xie; Jiahui Chen; Yaoyu Han; Bi Wu; Yang Li; Ling Ma; Jinsong Peng; Chunxia Chen (Pesticide Biochemistry and Physiology, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Occurrence, landscape impact, and risk assessments of pesticides in a major river basin of a tropical island, South China - Ling Mo; Bin Tang; Li-Ke Chen; Jun Xiang; Ming-Yang Wang; Kai-Yi Wu; Ming-Zhong Ren; Qiao Xing; Li-Cheng Wang; Jing Zheng (Environmental Pollution, 2026)

Multi-head attention driven aggregation-differentiation network for probabilistic groundwater depth forecasting and depth-stratified early warning: A multi-site efficient framework - Jing Xu; Siyuan Liu; Jinran Wu; Yuming Mo; Kun Wang; Qingfeng Ji; You-Gan Wang; Ling Li (Environmental Modelling & Software, 2026)

Paper garland-inspired 2D single-phase spiral folded-rod elastic metamaterial for extremely low-frequency vibration isolation - Kai Miao; Leilei Wang; Wencheng Yin; Rui Zhang; Shuyuan Liu; Facheng Song; Jian Zhu; Lingling Wu; Jianhui Liang; Dichen Li; Ling Wang (Engineering Structures, 2026)

Enhanced metal-organic framework-driven deep learning-assisted magnetic crystal paper aptsensor for two-step sensitization and in-situ detection of pathogenic bacteria - Lulu Cao; Yuwei Ren; Shengshi Jiang; Hui Li; Maoling Hu; Xin Zhang; Xiaoyu Yu; Weichao Wu; Mengyu Li; Zhao Liang; Na Ling; Hongzhou Chen; et al. (Chemical Engineering Journal, 2026)

Pullulan-stabilized gliadin nanocomplexes loaded with astragaloside IV: Fabrication, characterization and treatment of ulcerative colitis - Kaipei Luo; Qiuxia Li; Siyin Chen; Qingya Jia; Yuxin Wu; Weiwei Liao; Yufei Su; Liping Chen; Xiao Wang; Zhimin Chen; Xiaofang Li; Ling Li; et al. (Carbohydrate Polymers, 2026)

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Global Potential and Trade‐Offs of Conservation Tillage for Crop Productivity and Ecosystem Services - Wanyang Zhang; Linchuan Fang; Wenju Zhang; Chaoqun Wang; Tianyi Qiu; Xiaokun Li; Min Huang; Bolin Li; Ling Xia; Lai Peng; Yifeng Xu; Xiaoyong Wu; et al. (Global Change Biology, 2026)
Conservation Agriculture (CA) is pivotal to achieve sustainable intensification, yet the global efficacy of its core practice, conservation tillage (CT), remains debated regarding the trade‐offs between crop productivity and ecosystem services across diverse environmental contexts. Here, we conducted a second‐order meta‐analysis, synthesizing 69 published meta‐analyses, to elucidate the context‐dependent drivers regulating the “win‐win” outcomes of CT. Globally, CT reduced greenhouse gas (GHG) emissions by 5%, increased soil organic carbon sequestration by 21%, increased soil fertility by 11%, and reduced soil erosion by 12%, all while maintaining crop yields comparable to conventional tillage. However, CT can also emerge as a partial trade‐off between crop yields and ecosystem services, notably between crop yield and GHG mitigation. These trade‐offs were strongly regulated by climatic and edaphic conditions as well as management intensity. For instance, strong synergies between crop productivity and multiple ecosystem services were more pronounced in (semi‐)arid regions characterized by low temperatures and low precipitation, as well as in coarse‐textured alkaline soils. Furthermore, integrating CT with residue retention and crop rotations maximized these synergies, mitigating potential yield penalties. Collectively, our synthesis demonstrates that context‐specific refinement of CT implementation is essential to reconcile agricultural productivity with ecosystem services, thereby advancing climate‐resilient agricultural systems globally.

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Comparative analysis of PRV-induced neuropathology and blood–brain barrier disruption identifies C57BL/6 as the most susceptible mouse model - Tong Xu; Hanyu Li; Baoling Liu; Lei Zhao; Yangming Dai; Xin Wu; Siyuan Lai; Jian-Bo Huang; Ling Zhu; Zhi-Wen Xu (Veterinary Microbiology, 2026)

Accelerating cultivated meat bioprocess innovation: Rational design of cost-effective serum-free media via the convergence of data-driven analytics and synthetic biology platforms - Nuo Chen; Qinya Niu; Qinghua Ye; Qingping Wu; Yuwei Wu; Xinyu Zhao; Qihui Gu; Youxiong Zhang; Xianhu Wei; Ying Li; Ling Chen (Trends in Food Science & Technology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Decoupling of antimony and arsenic migration in a deep neutral legacy Technosol profile with implications for remediation - Yidan Shi; Ling Li; Han Tu; Xuexian Li; Pan Wu (Journal of Environmental Sciences, 2026)

Photooxidation and ozonolysis of α-pinene and limonene mixtures: Mechanisms of secondary organic aerosol formation and cross-dimerization - Yingqi Zhao; Ya Zhao; Chong Wang; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2026)

Isolation and characterization of two novel lytic Salmonella bacteriophages and their application as a cocktail in foods - Jinzhi Qi; Xiaojuan Yang; Zekun Liu; Shiyuan Yang; Jumei Zhang; Ying Li; Qinghua Ye; Shi Wu; Qihui Gu; Xianhu Wei; Youxiong Zhang; Ling Chen; et al. (Food Control, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Multifunctional pomelo peel cellulose/lysine/ZIF-8 porous foam with honeycomb structure: Adsorption performance and mechanism - Haize Su; Weipeng Qiu; Tenggen Hu; Shaohua Luo; Jinling Wu; Xiaowen Zhong; Na Li; Hao Su; Zhizhou Ling; Zhenlin Xu; Hong Wang; Peng Wen (Carbohydrate Polymers, 2026)

Multiscale Numerical and Experimental Evaluation of Microindentation Tests for Characterizing the Strength and Failure Mechanisms of Black Shale - Xiaoning Li; Enjian Wu; Wu Bo; Gen Zhang; Gopi Krishna Basyal; Sixiang Ling; Tangyao Wang; Chunwei Sun (Rock Mechanics and Rock Engineering, 2026)

Long-term organic amendments regulate cbbL-harboring bacterial community via soil physicochemical properties and enzyme activities in a paddy soil - Jiangbing Xu; Boxuan Li; Yuhao Wu; Lei Liu; Guoyi Zhou; Xiaoli Liu; Ling Chen; Meng Wu; Xiaoyan Ma; Catherine Preece; Daming Li; Ming Liu (Journal of Soils and Sediments, 2026)

Salvia miltiorrhiza (Danshen) and its extracts in the alternative treatment of diabetic nephropathy: mechanisms and clinical perspectives - Lu Song; Yan Li; Huakui Zhan; Ling Wu; Li Tang; Xinyu Wang; Qinyuan Deng (Journal of Natural Medicines, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

A viral masterstroke: Geminivirus C4 protein reprograms auxin transport to attract its insect vector - Mingjun Li; Lyuxin Wang; Gentu Wu; Ling Qing (Molecular Plant, 2026)

Moss biocrusts enhance hydrological functionality on engineered slopes: pore restructuring, water retention, and hydrophobicity compensation in humid subtropical ecosystems - Chen Wang; Jiaqi Tan; Zhou Fang; Yingjie Zhang; Ming Luo; Binbin He; Shaoxian Song; Li Wu; María Luciana Montes; Delong Meng; Ling Xia (Journal of Hydrology, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Band structure-dependent performance of TiO2 and g-C3N4 in photocatalytic chlorine activation: A comparative efficiency–cost–risk assessment - Haofei Yang; Wu Wen; Jinxin Wang; Zihang Cheng; Chunzhao Chen; Yun Yang; Gang Yu; Li Ling (Journal of Cleaner Production, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Bayesian-optimized transfer learning for ammonia nitrogen prediction in SBR systems: Seamless knowledge transfer from domestic to industrial-mixed wastewater - Qiu Cheng; Li Qingchuan; Huang Xingjun; Hu Junjie; Xu Jinpeng; Wu Ling; Fan Shoubo; Zhan Chunhong; Li Qianglin; Xu Lingjie; Xie yishang (Journal of Environmental Management, 2026)

B doped C3N4 enhancement built-in electric field and coupling NiS to construct interfacial electric field for boosting photogenerated carrier separation to enhance hydrogen evolution - Mengjiao Xu; Yongping Luo; Zheyuan Fan; Jiaqi Huang; Yuxiu Wang; Jian Li; Yun Ling; Yu Xie; Zhenkai Wu (Fuel, 2026)

Fixation of atmospheric nitrogen on present-day Mars during dust events - Wenshuo Mao; Xiaohui Fu; Zhongchen Wu; Jiang Zhang; Zongcheng Ling; Yang Liu; Yu-Yan Sara Zhao; Jiacheng Liu; He Cui; Hitesh G. Changela; Yuheng Ni; Lifang Li; et al. (Earth and Planetary Science Letters, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Decreasing internal reorganization energy via inactivating iodine defects to optimize Marcus-Gerischer charge mobility for high-performance carbon-based perovskite solar cells - Cai-Xia Li; Wen-Wu Liu; Shi-Ji Da; Ling-Bin Kong (Chemical Engineering Journal, 2026)

Development and application of integrated adsorption–fluidized-bed desorption–RTO process for high-flowrate rubber vulcanization exhaust - Shanshan Guo; Boxian Chen; Yufei Cai; Cui Li; Ling Ma; Zhentao Wang; Yuting Huang; Weibing Wu; Ke Jin; Xingyu Jiang; Weirong Zhao (Chemical Engineering Journal, 2026)

In situ self-assembled Nb/Cu co-doped air electrode with enhanced electrocatalytic activity for protonic ceramic cells - Tong Wei; Kaiyuan Ling; Yan Fang; Renhong Li; Wenlong Xu; Zhiwei Peng; Peng Qiu; Tianyu Zhu; Yanying Lu; Lei Wu (Chemical Engineering Journal, 2026)

Clay-microbe synergy for biocrust development: field evidence from sepiolite-assisted inoculation with natural biocrusts and cultured cyanobacteria - Junfang Xiong; Shiqi Wang; Peng Liu; Ashiwin Vadiveloo; Longkat Ayuba Gufwan; Zhaojun Wang; Shubin Lan; Ling Xia; Shaoxian Song; Lie Yang; Li Wu (Bioresource Technology, 2026)

Error characterization and analysis of aerosol products from the geostationary environment monitoring spectrometer (GEMS) - Guanghao Du; Xiaoqing Tian; Ling Gao; Jing Li; Chengcai Li; Jun Li; Angnuo Tian; Muqian Li; Zhaolong Wu (Atmospheric Research, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Three new species of Scleroderma from Southern China - Ling Li; Hua Qu; Rong-Qian Bi; Rui Wu; Hai-Jiao Li; Zai-Wei Ge (Mycological Progress, 2026)

Carboxymethyl cellulose-stabilized microbial synthesis of FeS-based biocomposite materials: Synthesis, characterization and photocatalytic reduction of hexavalent chromium - Ming Fan; Xilin Li; Ling Liu; Meini Wu; Shuhua Wang; Wei Ji; Yuan Gao (Water Research, 2026)

Direct conversion of fly ash into monolithic composite aerogels with robust heat-insulating and fire-resistant properties - Ke Zhang; Dahao Liu; Jie Wang; Huiquan Liu; Yongchen Song; Yanghui Li; Lanlan Jiang; Peng Wu; Luyuan Gong; Kun Zhang; Zheng Ling (Waste Management, 2026)

Microplastics and nanoplastics, emerging pollutants, increased the risk of pulmonary fibrosis in vivo and in vitro: A comparative evaluation of their potential toxicity effects with different polymers and size - Jia-Yi Dou; Sen Liu; Chen-Yu Wang; Xu Dai; Li-Hua Lian; Zhen-Yu Cui; Ji-Xing Nan; Yan-Ling Wu (Toxicology, 2026)

Algae: A considerable regulator of methylmercury in mercury-contaminated paddy fields - Ling Su; Guangjun Luo; Tianrong He; Pan Wu; Ping Li; Deliang Yin; Yuping Xiang; Xian Zhou (Journal of Environmental Sciences, 2026)

Coupled salt and nitrogen dynamics in coastal reservoir-adjacent aquifer systems under extreme rainfall event - Yuming Mo; Jing Xu; Yuhang Tian; Senlin Zhu; Jinran Wu; Tong Li; Guangqiu Jin; Ling Li (Journal of Contaminant Hydrology, 2026)

A targeted mass spectrometry-based method for the simultaneous detection of four pathogenic Vibrio species in aquatic products - Li Ling; Zuqing Wu; Wenchuan Weng; Jingwen Liu; Yuyin Xian; Muyun Yuan; Chengdong Huang; Wenrui Chen; Qing Liu; Jie Dong; Mengqi Chen (Food Control, 2026)

High-uniformity strain sensor via droplet morphology engineering for anterior cruciate ligament diagnosis - Zhanfeng Guo; Jinyi Wang; Jiasi Gao; Yifan Li; Daixuan Wu; Yihan Xu; Shourui Ji; Boyi Zhu; Yuhan Zhao; Yuhong Wei; Weiwei Hou; Zijie Zhang; et al. (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Unveiling the synergistic mechanisms of multi-ionic removal in microbial desalination cells: Ion transfer, electrochemical behavior and microbial response - Chongtao Liu; Ran Ju; Chunxiao Han; Zhuangzhuang Liu; Yangyang Li; Xiaomei Jiang; Ling Wang; Yunfan Yang; Houkai Wu; Xiuping Tao (Bioresource Technology, 2026)

SHANK3 Deficiency in AgRP Neurons Inhibits Diet-Induced Obesity by Activating p38α - Shanshan Wu; Yixiao Liang; Yang Xu; Yueping Ge; Jing Wang; Lu Wang; Xinchen Jin; Huidong Zhan; Li Peng; Ling Gao; Jiajun Zhao; Zhao He (Neuroscience Bulletin, 2026)

Inhibition of TRPV1 Ameliorates Depression-Like Behaviors in Male Mice by Regulating Neuroinflammation and Neurogenesis via the JAK2/STAT3 Pathway - Junjie Huang; Chen Li; Hailong Ge; Lan Wu; Ling Xiao; Yinping Xie; Gaohua Wang (Molecular Neurobiology, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Occurrence of Benzophenone-Type Ultraviolet Filters in Indoor Dust from Chinese Homes and University Dormitories: Implications for Human Exposure - Bo-Wen Li; Geng-Chen Wu; Hui-Ling Zhao; Chao Li (Bulletin of Environmental Contamination and Toxicology, 2026)

Comparisons of machine learning models for landslide susceptibility mapping in the Jiuzhaigou earthquake-affected area, China - Zuhao Lin; Sixiang Ling; Fei Luo; Fengxing Gao; Yanbing Pu; Minxuan Li; Xiaoyang Liu; Xiaoning Li; Chunwei Sun; Xiyong Wu (Bulletin of Engineering Geology and the Environment, 2026)

Smartphone-integrated luminescent Europium-organic framework sensor for on-off ratiometric identification of levofloxacin in water and milk samples - Lei-Ming Dai; Ling Li; Sheng-Yong You; Li Zhang; Mei-Feng Wu; Ji-Yong Zou (Analytica Chimica Acta, 2026)

Novel interface-enhanced bimetallic nanozyme-mediated magnetic integrated nanoplatform for integrated prevention and control of pathogenic bacteria - Xiaoyu Yu; Xin Zhang; Yuwei Ren; Rui Jiao; Hui Li; Mengyu Li; Weichao Wu; Na Ling; Danfeng Zhang; Jianghua Cheng; Yingwang Ye (Analytica Chimica Acta, 2026)

Hexafluoropropylene oxide homologues, the novel alternatives to PFOA, induce mitochondrial dysfunction and cytotoxicity in Leydig cells through disrupting SIRT1/PGC-1α signaling pathway - Mei-Ling Le; Jia-Yu Xue; Li-Hai Wu; Xin-Yuan Zhao; Jing Ding; Yang-Yang Yuan; Yi-Qi Wan; Da-Lei Zhang (Toxicology, 2025)

Optimization of substrate-plant combinations in constructed wetlands for livestock wastewater treatment and greenhouse gas mitigation - Wen Liu; Dengming Wang; Ling Wang; Qiongrou Huang; Junhong Yu; Hongyu Wu; Yaying Li; Dan A (Journal of Water Process Engineering, 2025)

Influence of artificially-induced biocrust development on soil matrix infiltration: insights from a long-term field experiment and random forest modeling - Mingquan Zhao; Vincent J.M.N.L. Felde; Peng Liu; Xinwen Xu; Ling Xia; Li Wu; Shubin Lan (Journal of Hydrology, 2025)

Rainfall-dependent influence of water parameter interactions and land use on lake water quality: A hybrid ensemble approach and management implications - Jing Xu; Yuming Mo; Qihao Jiang; Lingzhong Kong; Jinran Wu; Zhe Ding; Guangqiu Jin; Ling Li (Journal of Hydrology, 2025)

A colorimetric and electrochemical dual-mode sensor based on the morphological evolution of Au@Ag nanostars for quantitative silver ion detection - Junyao Li; Yujie Wang; Ling Cai; Zheyuan Lin; Zhengxiao Jiang; Peiming Liu; Wenrong Cai; Datong Wu; Zheng-Zhi Yin; Yong Kong (Journal of Environmental Chemical Engineering, 2025)

Comparative studies of the NOx impacts on the photooxidation mechanisms of isomeric monoterpenes of β-pinene and limonene - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2025)

Enhancement of stability and hydrogel properties of type-A gelatin-dextran mixtures via incorporation of whey protein isolate fibrils - Ling Wu; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Yisu Yang; Meng Zhao; Bo Cui (Food Research International, 2025)

Mechanism of monosodium fumarate in inhibiting Bacillus cereus spore growth and its implications for food safety control - Yangfu Li; Xiang Li; Juan Wang; Ling Chen; Yuecong Li; Huixian Wang; Chuang Cui; Fuyuan Chen; Qihui Gu; Youxiong Zhang; Xianhu Wei; Jinxuan Cao; et al. (Food Research International, 2025)

Glycyrrhiza uralensis Fisch: A novel source of analgesic activity through NaV1.8 sodium channel modulation - Yalan Han; Shutong Wu; Hejiang Zhou; Xiancui Lu; Susu Cheng; Jiaojiao Li; Meiquan Li; Yin Nian; Ling-Yan Su (Food Research International, 2025)

Identification and exploration of sleep-enhancing peptides from goat milk casein by peptidomics and virtual screening - Ling Mo; Shan Wang; Beiqi Wu; Chaochao Zhao; Yimeng Yu; Jie Li; Hongxin Wang (Food Research International, 2025)

Identification of new coumarin-cinnamic acid hybrid FtsZ inhibitors as potential bactericides for enhancing the yield and quality of rice - Ling Zhang; Si-yue Ma; Wan Chen; Lin-li Yang; Yue Ding; Xiang Zhou; Li-wei Liu; Zhi-bing Wu; Song Yang (Food Chemistry, 2025)

Engineering fast-response thermal control for dynamic gene expression design in Halomonas - Jian-Lian Wu; Ya-Ge Xiao; Bao-Wen Liu; Ling-Fan Tian; Ling-Fei Tian; Yu-Xi Li; Jia-Wen Peng; Hai-Fan Zhu; You-Yang Wang; Zhe-Yi Kuang; Jiang-Jie Tian; Shuai Zheng; et al. (Chemical Engineering Journal, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Ag-doped Bi2Se3 optoelectronic synapse with dynamic activation function enabling fully functional single-layer neural network - Lei Chen; Wen He; Guojiang Xi; Duoduo Ling; Yinze Zhang; Wei Wu; Zhaoqi Shi; Qiudan Geng; Xiangqian Fan; Bangsheng Li; Dongbo Wang; Jinzhong Wang (Chemical Engineering Journal, 2025)

Geochemical investigations on black shale weathering profiles in contrasting terrains: Role of topography on chemical weathering - Junjie Feng; Wei Wei; Sixiang Ling; Xiaoning Li; Chunwei Sun; Xin Liao; Xiyong Wu (CATENA, 2025)

Methionine in embryonic development: metabolism, redox homeostasis, epigenetic modification and signaling pathway - Chang Yan; Biyan He; Chenjun Wang; Wanzhen Li; Siming Tao; Jingqing Chen; Yuquan Wang; Ling Yang; Yingjie Wu; Zhenlong Wu; Ning Liu; Yinghe Qin (Critical Reviews in Food Science and Nutrition, 2025)

Comparative life cycle assessment of four clean coal power generation technologies in Anhui province, China - Huijun Wu; Weixin Fang; Ling Zhang; Yuanyuan Ye; Li Yang; Zhanfeng Dong (The International Journal of Life Cycle Assessment, 2025)

Cortical Control of Itch Sensation by Vasoactive Intestinal Polypeptide-Expressing Interneurons in the Anterior Cingulate Cortex - Yiwen Zhang; Jiaqi Li; You Wu; Jialin Si; Yuanyuan Zhu; Meng Nian; Chen Chen; Ningcan Ma; Xiaolin Zhang; Yaoyuan Zhang; Yiting Lin; Ling Liu; et al. (Neuroscience Bulletin, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Design of a ball screw for the electric control rod drive mechanism in nuclear reactors - Chaoqun Qian; Yi Ou; Yongjun Bai; Changguang Zhou; Ling Li; Junwan Shen; Hutian Feng; Jian Wu (Annals of Nuclear Energy, 2025)

Food-derived alcohol dehydrogenase activating peptides: production, identification, structure-activity relationship, and mechanism of action - Mengyao Li; Junjia Zhang; Lilin Cheng; Xiaoyu Chen; Xinya Yin; Ling Zhu; Hui Zhang; Gangcheng Wu (Critical Reviews in Food Science and Nutrition, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Bidirectional ion-electric field synergy via in situ grown BiOCl/Bi heterostructure enabling ultra-stable zinc anodes across wide temperatures - Miaomiao Wu; Xingchao Wang; Yong Guo; Haixia Li; Fei Zhang; Zhibo Liu; Lijuan Hai; Jixi Guo; Ling Huang; Dianzeng Jia (Science Bulletin, 2025)

Genistein: A promising botanical fungicide candidate for enhancing tomato yield and quality by controlling Alternaria solani - Ling Zhang; Yu Long; Long-Fei Li; Xiang-Wei Xin; Xiao-Di Chen; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; Song Yang (Pesticide Biochemistry and Physiology, 2025)

Effects of seawater salinity variations on nitrogen transport in the coastal reservoir and adjacent aquifer - Yuming Mo; Jing Xu; Kun Wang; Beibei Xu; Jinran Wu; Qihao Jiang; Guangqiu Jin; Ling Li (Journal of Hydrology, 2025)

Labile heavy metals in sediments controlled by terrestrial organic matter based on isotopic and molecular signatures in an anthropogenic estuary - Ling Zhang; Yunchao Wu; Pengju Li; Jia Yang; Zhixin Ni; Zhijian Jiang; Xiaoping Huang; Ding He (Journal of Hazardous Materials, 2025)

Inhibitory effect of licochalcone A on dual-species biofilms of Listeria monocytogenes and Staphylococcus aureus: mechanism involved in quorum sensing and application in beef - Ling Jiang; Yilin Han; Xianxuan Li; Kai Zhong; Yanping Wu; Hong Gao (International Journal of Food Microbiology, 2025)

Construction of Er2O3/ZnIn2S4 heterojunction with enhanced oxygen vacancies and upconversion luminescence property for photocatalytic CO2 reduction - Duhui Sun; Shaoxiong Zhu; Zheng Ji; Xiantuo Chen; Jiang Wu; Hao Liu; Yang Ling; Ahmad Hosseini-Bandegharaei; Zehan Li; Qizhen Liu (Fuel, 2025)

Effect of different aroma types of baijiu on the quality of Sichuan paocai - Lihui Huang; Ling Li; Lianqun Wu; Huan Guo; Yanping Wu; Kai Zhong; Hong Gao (Food Chemistry, 2025)

Fe-Mn bimetallic loaded sludge biochar as a novel periodate activator for sulfamethoxazole removal: The combination of radical and non-radical mechanisms - Yingjian Yu; Xiaolong Chen; Ling Tao; Yulong Li; Li Wu; Zhuqi Chen; Xiaoman He; Yuting Luo; Lie Yang (Environmental Research, 2025)

Pretrain-finetune neural operator for multi-fidelity surrogate modeling of structural dynamic systems - Pei-Lin Li; Shi-Fu Liu; Yi-Qing Ni; Jian-Ming Ling; You-Wu Wang (Engineering Structures, 2025)

The impact of nitrogen forms on the ecological function and community assembly of biocrusts in Gurbantunggut Desert - Long Qian; Jingshang Xiao; Shiqi Wang; Ling Xia; Shaoxian Song; Xiaoyan Liu; Yan Gong; Li Wu (Plant and Soil, 2025)

Carbon emissions and economic performance of high-density versus traditional Ctenopharyngodon idella aquaculture: evidence from life cycle assessment methodology and field measurements - Liang Xiao; Qiaomei Yuan; Wenhan Li; Jinghua Wu; Yueshi Li; Sijie Chen; Guodong Yuan; Tao Wang; Jiayin Ling; Fengxiang Han (Aquaculture International, 2025)

Benthic foraminiferal community structure and response to environmental factors revealed through eDNA and eRNA metabarcoding in Beiji Archipelago, China - Junting Chen; Jianping Zhao; Tiejun Li; Ling Qiao; Yuanming Guo; Yuqi Wu (Environmental Monitoring and Assessment, 2025)

Interaction effects of organic mulch application rates and rainfall intensities on soil and water loss in karst sloping farmlands: Insights from a laboratory simulation experiment - Panpan Wu; Rui Li; Feiyang Cai; Ling Xiong; Zhengyi Tang; Linlv Xiao (Soil and Tillage Research, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

CloudRuler: Rule-based transformer for cloud removal in Landsat images - Jun Li; Yihui Wang; Qinghong Sheng; Zhaocong Wu; Bo Wang; Xiao Ling; Xiang Liu; Yang Du; Fan Gao; Gustau Camps-Valls; Matthieu Molinier (Remote Sensing of Environment, 2025)

A WRKY transcriptional factor, BrWRKY70, involves in stem lignification in postharvest Chinese flowering cabbage by regulating lignin synthesis - Fengjun Li; Ling Wang; Meiting Wu; Yulong Chen; Lilang Li; Hai Liu (Postharvest Biology and Technology, 2025)

Rice endosperm starch regulator1 controls starch granule formation and amylopectin synthesis in rice endosperm - Wang Li; Fengsheng Wu; Xiaokang Nie; Yufei Xiong; Yi Bao; Sheng Ling; Xiaocong Sun; Xin Wang; Jialing Yao (Plant Science, 2025)

Autophagy and glycolysis synergistically mediate Cd²⁺ transport to enhance Cd tolerance in Arabidopsis - Hanchen Tang; Shoujian Zang; Xingyue Hong; Ruiyuan Jiang; Hezi Huang; Shengwei Hu; Mengqi Wu; Qinghua Li; Jicheng Wang; Ling Sun; Yupeng Zhang; Dekai Chen; et al. (Journal of Hazardous Materials, 2025)

Comparative analysis of machine learning based dissolved oxygen predictions in the Yellow River Basin: The role of diverse environmental predictors - Lingling Liu; Xiaoli Zhao; Lingfeng Zhou; Jiangtao Liu; Wenjing Li; Bolun Zhang; Junhong Ling; Fengchang Wu (Journal of Environmental Management, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Rice protein-derived hypoglycemic peptides IQP,VEP and IPQ alleviate obesity-related metabolic disorders in high-fat diet (HFD)-induced C57BL/6J mice through activation of AMPK and modulation of gut microbiota and related metabolites - Ling Liu; Jiahong Jian; Songfeng Yu; Shanshan Li; Jing Wang; Tingting Bu; Jianping Wu (Food Bioscience, 2025)

Hydrodynamics and dissolved organic matter regulate partitioning behaviour of heavy metals in seawater in a human-impacted subtropical estuary - Ling Zhang; Yunchao Wu; Jia Yang; Pengju Li; Zhixin Ni; Xiaoping Huang (Environmental Pollution, 2025)

Seasonal changes-facilitated release of phosphorus and tungsten from the Lake Taihu sediments through reductive dissolution of Fe/Mn (hydr)oxides and competitive adsorption with dissolved organic matter - Xiang Chen; Yan Wang; Minjuan Li; Xiangyu He; Qi Li; Junliang Jin; Tingfeng Wu; Yichun Shao; Jingwei Wu; Gaoxiang Li; Ling Liu; Wenming Yan (Environmental Pollution, 2025)

Controlled cracking of δ-MnO2 into ultra-fine nanocrystals to improve the cathode performance for aqueous magnesium-ion batteries - Caili Suo; Bo Zhang; Jinwang Huang; Yuxiang Zhao; Wanzhen Zhang; Hongbo Zhang; Yulong Qian; Xiafang Ji; Ling Suo; Yue Ma; Jinbo Zeng; Wu Li (Chemical Engineering Journal, 2025)

Tough and fatigue-resistant functional elastomer enabled by hierarchical nanophase-separated microparticle-reinforced strategy - Jingping Wu; Ke Li; Zhouhu Jiang; Ling Hu; Liaobo Chang; Yong Zheng; Jian Hu; Qiang Chen (Chemical Engineering Journal, 2025)

Defect-rich carbon nanofiber membranes as metal-free catalysts for flow-through peroxymonosulfate activation: toward efficient antibiotic removal and water remediation - Jiaqiang Wang; Linghui Li; Xiaoben Yang; Qianglin Li; Ling Wu; Binghua Zhou; Zhipeng Wang; Zheng-Hong Huang; Ming-Xi Wang (Chemical Engineering Journal, 2025)

High-performance triboelectric nanogenerator based on mangosteen peel-derived carbon for energy harvesting and self-powered sensing - Jie Wu; Yunchao Li; Ao Song; Dingkun Yuan; Shahong Zhu; Zhongqian Ling; Jiangrong Xu (Chemical Engineering Journal, 2025)

RUSLE tends to overestimate soil erosion in revegetated conditions: Evidence from long-term runoff plots monitoring on China’s Loess Plateau - Jun Liao; Jiaxi Wang; Juying Jiao; Zeng Yan; Jianjun Li; Ziqi Zhang; Mengmeng Li; Qian Xu; Xiaohan Jiang; Wenting Zhao; Qi Ling; Hanyuan Sheng; et al. (CATENA, 2025)

Tongxinluo alleviates myocardial ischemia–reperfusion injury by inhibiting the pyroptosis of endothelial cells via the NLRP3/Caspase-1/GSDMD signaling pathway - Xuan Wu; Yun-long Hou; Tong-xing Wang; Li-ping Chang; Hong-ru Zhou; Ming-ye Wang; Yi-ling Wu (Journal of Molecular Histology, 2025)

Correction to: Links between personality, metabolic rates, brain size, and spatial learning ability of goldfish (Carassius auratus) under two conditions of spatial learning - Wu-Xin Li; Shi-Jian Fu; Ling-Qing Zeng (Behavioral Ecology and Sociobiology, 2025)

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

CDIP-ChatGLM3: A dual-model approach integrating computer vision and language modeling for crop disease identification and prescription - Changqing Yan; Zeyun Liang; Han Cheng; Shuyang Li; Guangpeng Yang; Zhiwei Li; Ling Yin; Junjie Qu; Jing Wang; Genghong Wu; Qi Tian; Qiang Yu; et al. (Computers and Electronics in Agriculture, 2025)

SHAPAttention: A novel approach to enhance model performance and interpretability in agricultural spectral data analysis - Ting Wu; Longhui Zhu; Lei Li; Leian Liu; Weidong Bai; Li Lin; Ling Yang (Computers and Electronics in Agriculture, 2025)

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Round-the-clock degradation of pharmaceutical pollutants by photocatalytic and catalytic ozonation based on bifunctional MIL-100(Fe) catalyst - Shizhen Zhang; Jiajia Wu; Shujing Yang; Hongjing Li; Yang Li; Mingxi Wang; Xuanke Li; Ling Wu (Water Research, 2025)

Discovery of novel pathogens causing black spots on Torreya grandis cv. Merrillii nut and fungicide effectiveness during post-ripening - Sisi Lai; Caoliang Jin; Haojie Ye; Ling Li; Yuhui Chen; Mohamed A. Farag; Tao Liu; Zuying Zhang; Jiasheng Wu; Lili Song; Yuanyuan Hu (Physiological and Molecular Plant Pathology, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Study on the impact of microplastic characteristics on ecological function, microbial community migration and reconstruction mechanisms during saline-alkali soil remediation - Yifei Li; Wei Ling; Jian Yang; Yi Xing; Qi Zhang; Lihui Feng; Jiachen Hou; Chang Hou; Qingbin Lu; Tianqi Wu; Ziyuan Gao; Yifei Li (Journal of Hazardous Materials, 2025)

Identifying the driving factors of soil nitrate nitrogen via MLs-GIS framework in an intensive plain agricultural area, China - Hui Chen; Jianwei Liu; Shuo Qiao; Shilong Zhao; Donghao Li; Yong Wu; Ling Li; Ping Liu (Journal of Cleaner Production, 2025)

Regulating 2e− ORR on Ag clusters modified CdS nanosheets for enhancing photocatalytic HMF directional oxidation coupled with H2O2 evolution - Jinqi Li; Yuewei Deng; Yingzhang Shi; Jiayi Guo; Shuang Li; Chen Huang; Wenda Zhang; Zhiwen Wang; Yujie Song; Ling Wu (Chemical Engineering Journal, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Mitochondrial energy reprogramming via dECM/GP@EVs@Gpnmb to prevent post-myocardial infarction heart failure - Na Li; Ying Wang; Ling Yuan; Shuang Peng; Zhansheng Hu; Baoquan Wang; Dan Zhang; Longxiang Su; Huiping Wu (Chemical Engineering Journal, 2025)

Reflective yellow-to-green switching electrochromic adaptive camouflage devices with high stability based on new triazatruxene polymers - Ling Zhang; Jiahao Wang; Qida Wu; Wenna Xie; Tao Yang; Wang Zhan; Jin Li; Mi Ouyang; Yujie Dong; Weijun Li; Cheng Zhang (Chemical Engineering Journal, 2025)

Engineering microfluidic human liver-islet crosstalk platform for recapitulating MASLD - Jingbo Li; Zhuhao Wu; Jingjing Gan; Yue Zhi; Yuanjin Zhao; Ling Li (Chemical Engineering Journal, 2025)

Extracellular vesicles based contrast agent for precisely diagnosing metastatic breast cancer - Wanjia Wu; Yuanyuan You; Peiru Lin; Zibin Song; Xiaoqiang Li; Guanjun Chen; Ling Lu; Peng Zhao; Yikai Xu; Jia Tao; Bingquan Lin (Chemical Engineering Journal, 2025)

Anthropogenic effects on Δ3-carene photooxidation: Different oxidants induce significant changes of secondary organic aerosol formation mechanisms - Ya Zhao; Chong Wang; Yingqi Zhao; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2025)

Reducing Phosphorus Fertilizer Application in the Typical Pomelo Production Region of China Improves Fruit Quality Traits via Metabolic Reprogramming - Huilan Luo; Muhammad Ishfaq; Minwen Yan; Jing Zhang; Siwen Zhang; Xue Zhang; Ling Tong; Mahmood Ul Hassan; Haifang Liao; Jiuliang Xu; Delian Ye; Liangquan Wu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Inhibition of USP5 Attenuates Atherosclerosis by Suppressing PDCD4-Mediated Endothelial Dysfunction: Evidence from In Vitro HUVEC and In Vivo Models - Yali Chen; Yihuan Wang; Tingting Wu; Xiaolei Guo; Xueyang Bai; Lirui Wang; Peipei Yan; Zhe Zheng; Lili Xiao; Ling Li (Cardiovascular Toxicology, 2025)

Smartphone-assisted portable electrochemical sensing platform for point-of-care detection of thiocyanate using a laser-induced graphene composite electrode - Xiaoming Yuan; Linlin Chen; Ruwei Liu; Shilin Li; Xiu-wen Wu; Yunhan Ling (Analytica Chimica Acta, 2025)

Benthic foraminiferal community structure and its response to heavy metals revealed using environmental DNA/RNA metabarcoding in Yueqing Bay, East China Sea - Ling Qiao; Yuqi Wu; Chengzhe Ren; Tiejun Li; Yuanming Guo; Anran Zhao (Marine Pollution Bulletin, 2025)

Evaluating N-acetylcysteine for mitigating cisplatin-induced oxidative stress and ionocyte damage in a zebrafish model - Szu-Jung Chen; Ciao-Ling Wu; Li-Yih Lin; Jiun-Lin Horng (Toxicology and Applied Pharmacology, 2025)

Residual tau-fluvalinate, a beehive acaricide, disrupts growth and metabolism in the greater wax moth, Galleria mellonella - Shengyun Li; Ling-Hsiu Liao; Wen-Yen Wu; May R. Berenbaum (Pesticide Biochemistry and Physiology, 2025)

Path planning algorithm for unmanned surface vessels based on COLREGs and Meta-TD3 - Xu Sun; Gangsheng Li; Zhaokai Liu; Ling Zhang; Haibo Yu; Dalei Song; Q.M. Jonathan Wu (Ocean Engineering, 2025)

Research status and prospects of using machine learning for promoting carbon emission reduction in wastewater treatment processes: A review - Jiahao Chen; Junjian Li; Yong He; Shenglong Chen; Lipeng Wu; Yanchao He; Yuxiang Lu; Haisheng Ling; Chengyuan Su (Journal of Water Process Engineering, 2025)

Renewable electrochemical sensors based on copper-organic frameworks for highly sensitive and selective detection of tetrabromobisphenol A - Caoling Li; Ling Lei; Wenbo Huang; Junxing Hao; Kangbing Wu (Journal of Hazardous Materials, 2025)

Polarization of dryland vegetation response to spring flood - Shouguo Zhang; Han Wang; Xiwen Zhang; Guanglei Li; Ling Zhang; Chang Ge; Jiabin Wang; Jiansheng Wu; Jian Peng (Journal of Environmental Management, 2025)

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

CSSF: Collaborative spatial-spectral fusion for generating fine-resolution land cover maps from coarse-resolution multi-spectral remote sensing images - Zhixiang Yin; Xinyan Li; Penghai Wu; Jie Lu; Feng Ling (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Tailoring a donor-acceptor structure in oxygen and cyano group co-modified carbon nitride for enhanced photocatalytic imidacloprid degradation - Ling Li; Hao Zeng; Liqiao Zhong; Hao Wu; Jin Zheng; Zhanpeng Zhou; Jiawei Liu; Rongdi Tang; Yaocheng Deng; Ying Huang (Chemical Engineering Journal, 2025)

Large-scale identification and association analysis of wheat grain weight genes using rice orthologs - Wensha Zhao; Shusong Zheng; Aoyan Zhang; Meng Yuan; Pengbo Song; Kefeng Song; Yueyue Li; Yuanhang Xing; Huiling Zhao; Jianqing Niu; Jianhui Wu; Hong-Qing Ling; et al. (Theoretical and Applied Genetics, 2025)

Genetic variants of OsWRKY70 modulate ROS levels to improve rice stress adaptation - Xiaoping Ding; GongYe Cheng; Di Zhang; Zhijun Wang; Mingchan Liu; Wenyu Li; Lingling Li; Ling Liu; Cheng Zheng; HouXiong Wu; Dingyang Yuan; Meijuan Duan; et al. (Theoretical and Applied Genetics, 2025)

Genomic and chromosomal architectures underlying fertility maintenance in the testes of intergeneric homoploid hybrids - Li Ren; Yiyan Zeng; Qizhi Liu; Xiaolong Tu; Fayi Chen; Hao Wu; Chuan Wang; Chang Wu; Mengxue Luo; Yakui Tai; Hailu Zhou; Mengdan Li; et al. (Science China Life Sciences, 2025)

Hierarchical assessment of the environmental trade-offs in global agricultural trade - Binbin Li; Ling Zhang; Xin Liu; Huijun Wu (Food Security, 2025)

Cytokine profiling in COVID-19 patients by using ion mobility-mass spectrometry-based parallel reaction monitoring - Ling Yan; Chenrui Yuan; Runhou Zhou; Li Zhong; Kelvin Kai-Wang To; Na Liu; Xin Diao; Guangshan Xie; Hongzhi Zhao; Haijiang Wu; Lin Zhu; Zhiwei Chen; et al. (Analytica Chimica Acta, 2025)

The role of multiple C2 domain and transmembrane region proteins in mediating tomato development - Siyi Li; Ribin Ling; Xuexia Wu; Lu Liu; Hui Zhang; Lijie Xuan (Plant Science, 2025)

Linaggrenoids A−I, structurally diverse lindenane sesquiterpenoids with anti-hepatic fibrosis effects from Lindera aggregata - Wen-Xian Li; Lu Gan; Yi-Ling Liao; Yu-Wei Wu; Bai-Hui Zhang; De-an Guo; Wei Li (Phytochemistry, 2025)

Global distribution characteristics and ecological risk assessment of microplastics in aquatic organisms based on meta-analysis - Yifei Li; Wei Ling; Chang Hou; Jian Yang; Yi Xing; Qingbing Lu; Tianqi Wu; Ziyuan Gao (Journal of Hazardous Materials, 2025)

Does promoting new urbanization help mitigate environmental pollution: Evidence from China's pilot policies for new urbanization - Ling Li; Ji Guo; Xianhua Wu; Jiqiang Zhao (Journal of Environmental Management, 2025)

Intensified human activities shape the dynamics of sediment organic matter in a highly-disturbed estuary - Jia Yang; Yunchao Wu; Bowen Shang; Jinglong Li; Pengju Li; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Journal of Environmental Management, 2025)

Unripe apple polyphenols extract improves intestinal inflammation and restructures gut microbiota in spontaneously hypertensive rats - Juan Li; Qiming Wu; Xiaomeng Ling; Xiaomin Ma; Xiaona Gan; Wei Wei; Jun Du; Leyan Zhou; Xue Jia; Juntao Kan; Min Zhao (Food Research International, 2025)

Optimal storage capacity for building photovoltaic-energy storage systems considering energy flexibility management - Yaling Wu; Zhongbing Liu; Benjia Li; Haixia Liu; Ruimiao Liu; Ling Zhang (Energy and Buildings, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Milk vetch (Astragalus sinicus L.) affects microbial-driven rice straw decomposition in multiple stages - Xinling Ma; Qingjun Dai; Wenjing Qin; Jia Liu; Xiaoli Liu; Ling Chen; Jianbo Fan; Meng Wu; Daming Li; Ming Liu (Plant and Soil, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Rhizosphere endophytes as allies in plant defense against heavy metals and organic pollutants in soil: Advances and applications - Sicheng Hang; Chen Wu; Guanwei Peng; Feng Li; Fei Ge; Jie Gan; Ling Li; Jie Li (Applied Soil Ecology, 2025)

Codon usage pattern and genetic diversity in chloroplast genomes of Zanthoxylum species (Sapindales: Rutaceae) - Changle Li; Songping Wu; Jiangbo Nie; Ling Zhou; Yonghong Liu; Yulin Liu (Acta Physiologiae Plantarum, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Identifying and prioritizing organic toxicants in treated flowback and produced water from shale gas exploitation sites using an integrative effect-directed analysis and nontarget screening method - Liwei He; Fei Cheng; Fan Wu; Keshuo Zhang; Ling Zhang; Yingqi Du; Zhimin Zhou; Huizhen Li; Jiangmeng Kuang; Xiangying Zeng; Zhiqiang Yu; Jing You (Water Research, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Discrete element analysis of the influence of grinding media shape on the grinding process - Xin Fang; Caibin Wu; Ningning Liao; Jiuxiang Zhong; Riqian Liu; Ji Wu; Li Ling; Xuqian Duan (Minerals Engineering, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Optimization of surface modification conditions of jute powder and study of its adsorption behavior and mechanism for Pd(II) - Man Lu; Manman Ge; Yong Li; Guozhen Wang; Xinke Kang; Haiyan Wu; Ling Tan; Haigang Dong; Jianping Xie; Bo He (Journal of Environmental Chemical Engineering, 2025)

A highly stable zinc phosphonate for efficient heterogeneous catalytic CO2 cycloaddition and ring-opening reaction - Chao-Ying Gao; Yakun Wu; Ling Ding; Yang Li; Wenbo Wang; Ning Xu; Jinghai Liu; Yang Yang (Journal of Environmental Chemical Engineering, 2025)

Strategy for stepwise removal of silicon and tungsten from alkaline solution containing vanadium and preparation of high-purity NH4VO3 - Zhen Wu; Wenbin Hu; Chenye Wang; Shengyue Ma; Chi Wang; Ling Wang; Baozhong Ma; Yanbin Li; Kelin Huang (Journal of Environmental Chemical Engineering, 2025)

Structural modulation and potassium ion redistribution in α-MnO2 for efficient VOCs oxidation - Yuhang Wu; Ji Mei; Yuzhen Cao; Yuanming Li; Hao Wang; Rumeng Zhang; Jingkai Zhao; Ling Zhang; Jian Yu; Kelong Li; Weifeng Kong; Jianrong Chen (Journal of Environmental Chemical Engineering, 2025)

Catalytic oxidation of crystal violet by using Ni-Cu@BC catalyst/NaClO system: Performance, kinetics and mechanism - Yuansha Xie; Wu Chen; Chao Yang; Ling Ding; Zheng Zhang; Yuhan Zheng; Yiting Luo; Wenjing Li; Jianshe Bai (Journal of Environmental Chemical Engineering, 2025)

Livistona chinensis leaves bioorganic frame derived porous carbon material containing Fe-Nx active site as oxygen reduction electrocatalyst for zinc-air batteries - Kun Fang; Chen Ling; Yan-Fang Yao; Hao Zhang; Jia-Jie Wu; Li-Ping Si; Hai-Yang Liu (Journal of Environmental Chemical Engineering, 2025)

Hg0 to Hg2+ via photocatalysis by Bismuth-based photocatalysts: A review - Yifan Liu; Hengzhong Chen; Wenquan Zhou; Wencai Qian; Kai Huang; Xiaojing Liu; Mei Ma; Yang Ling; Jiang Wu; Fangqin Li (Journal of Environmental Chemical Engineering, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Nitrogen‑phosphorus responses and Vis/NIR prediction in fresh tea leaves - Qing Luo; Ting Tang; Yuxin Duan; Junlin Li; Caijin Ling; Ting Gao; Weibin Wu (Food Chemistry, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

DSSAT modeling of oilseed flax (Linum usitatissimum L.): Sensitivity analysis of yield to weather variability and nitrogen application - Zechen Lin; Yue Li; Gerrit Hoogenboom; Yuhong Gao; Bing Wu; Ling Wu; Lili Wu; Hui Zhou; Bin Yan; Peina Lu; Jie Tang; Shunchang Su; et al. (Field Crops Research, 2025)

The release of antimony from soils surrounding the smelters in Karst Areas and its Environmental Implications - Zaiju Jiang; Lu Liao; Xuexian Li; Shaozhang Yang; Ling Li; Pan Wu (Environmental Pollution, 2025)

Perylene Diimide-Based A-D-A-Type Organic Additives for Efficient and Stable Inverted Perovskite Solar Cells - Shaojian Li; Kai Chen; Haiqian Ling; Desheng Li; Weixu Duan; Zedong Lin; Cong Liu; Xiangwen Guo; Liwei Zhou; Fan Wu; Tao Liu; Bingsuo Zou (Chemical Engineering Journal, 2025)

Acute toxicity, bioconcentration, and metabolomic profiling of agrochemical organosilicone spray adjuvants in Zebrafish - Tianyou Feng; Jianling Liu; Ling Wu; Yuanqiang Luo; Ling Liu; Fen Li; Guangbin Wu; Ping Lu; Yuping Zhang (Aquatic Toxicology, 2025)

TSPO activation ameliorates maternal immune activation induced PV interneuron deficits via BDNF/TrkB signaling - Ming-Jie Mao; Hui-Ling Yu; Qing-Zhen Liu; Ya-Zhou Wen; Ming Jiang; Hong-Mei Yuan; Hua-Bei Zeng; Li-Dong Zhang; Shan-Wu Feng (Psychopharmacology, 2025)

Transcriptomic analysis of wrinkled leaf development of Tai-cai (Brassica rapa var. tai-tsai) and its synthetic allotetraploid via RNA and miRNA sequencing - Xinli Zhang; Wen Zheng; Zhiyu Zhu; Xiaocan Guo; Jinbao Hu; Li’ai Xu; Huihui Fang; Yunshuai Huang; Zhengyan Ling; Zhujun Zhu; Yunxiang Zang; Jianguo Wu (Plant Molecular Biology, 2025)

Identification of the oncogenic role of centromere protein M in non-small cell lung cancer via CDC20/MYBL2/Wnt signaling pathways - Ling Wu; Jun Li; Haoyu Wang; Xu Chang; Qinglong Kong (Journal of Molecular Histology, 2025)

Hydrogen peroxide regulated split-type electrochemiluminescence sensing platform for non-invasive detection of gastric cancer-associated D-amino acids - Juan Li; Ming-Chun Lai; Ya-Meng Zhong; Ya-Ling Chen; Na Wu; Wei Chen; Hua-Ping Peng (Analytica Chimica Acta, 2025)

Links between personality, metabolic rates, brain size, and spatial learning ability of goldfish (Carassius auratus) under two conditions of spatial learning - Wu-Xin Li; Shi-Jian Fu; Ling-Qing Zeng (Behavioral Ecology and Sociobiology, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Construction and evaluation of recombinant rabies virus encoding three copies codon-optimized G genes as inactivated rabies vaccine in dogs and cats - Ying Wu; Haoqi Li; Zongmei Wang; Tao Pei; Qinghua Shang; Jianqing Zhao; Ming Zhou; Zhen F. Fu; Chengguang Zhang; Ling Zhao (Veterinary Microbiology, 2025)

Association of long-term ozone exposure with the incidence and progression of hypertension, diabetes, and chronic kidney disease: A national retrospective cohort study - Yu-Ling Li; Po-Ya Chang; Ting-Wu Chuang; Yi-Chen Hsieh; Bo-Sian Wang; Szu-Ying Chen; Hung-Yi Chiou (Science of The Total Environment, 2025)

Experimental demonstration of reconstructing quantum states with generative models - Xuegang Li; Wenjie Jiang; Ziyue Hua; Weiting Wang; Xiaoxuan Pan; Weizhou Cai; Zhide Lu; Jiaxiu Han; Rebing Wu; Chang-Ling Zou; Dong-Ling Deng; Luyan Sun (Science Bulletin, 2025)

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Corrigendum to “Ship_YOLO: General ship detection based on mixed distillation and dynamic task-aligned detection head” [Ocean Eng. 323 (15) (2025) 120616] - Chun-Ming Wu; Jin Lei; Zuo-Qing Li; Mei-Ling Ren (Ocean Engineering, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Polygonatum cyrtonema Hua polysaccharide alleviates ulcerative colitis via gut microbiota-independent modulation of inflammatory immune response - Jin-Yang Shi; Yong-Jian Wang; Qian-Wen Bao; Ya-Min Qin; Pei-Pei Li; Qiao-Qiao Wu; Cheng-Kai Xia; De-Ling Wu; Song-Zi Xie (Carbohydrate Polymers, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

ZmYSL2 affects the physiological function of iron deficiency in maize - Yikai Wang; Hongmei Hu; Binyang Li; Shuhao Zhang; Lisong Liu; Jingxiao Qi; Wei Zhao; Yulu Su; Yarong Wang; Jin Liu; Dan Liu; Ling Wu; et al. (Planta, 2025)

Blood and cloacal microbiome profile of captive green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata): Water quality and conservation implications - Xin Li Ching; Syamsyahidah Samsol; Mohd Uzair Rusli; Mohamad Aqmal-Naser; Joseph Anak Bidai; Christian Sonne; Xin Wu; Nyuk Ling Ma (Chemosphere, 2025)

A learning-based dual-population optimization algorithm for hybrid seru system scheduling with assembly - Yuting Wu; Ling Wang; Rui Li; Yuxiang Xu; Jie Zheng (Swarm and Evolutionary Computation, 2025)

Ship_YOLO: General ship detection based on mixed distillation and dynamic task-aligned detection head - Chun-Ming Wu; Jin Lei; Zuo-Qing Li; Mei-Ling Ren (Ocean Engineering, 2025)

Mineral-dependent release, migration and enrichment of toxic elements during black shale weathering: An integrated study from profile scale to mineral scale - Wei Wei; Sixiang Ling; Xiaoning Li; Chunwei Sun; Junjie Feng; Jiawei Luo; Xiyong Wu; Chuan He (Journal of Hazardous Materials, 2025)

Invasion risk of typical invasive alien plants in mountainous areas and their interrelationship with habitat quality: A case study of Badong County in central China - Shuya Wu; Junchen Chen; Shuqi Jiang; Ruiqi Zhang; Zhaohua Li; Ling Wang; Kun Li (Journal of Environmental Management, 2025)

Metagenomic assembly insight into the antibiotic resistance genes and antibiotic resistant bacteria in packaged drinking water system - Xiyang Xia; Qihui Gu; Ling Chen; Jumei Zhang; Weipeng Guo; Zhenjie Liu; Aimei Li; Xinhui Jiang; Meiqing Deng; Jiahui Zeng; Xiuhua Lin; Feiting Peng; et al. (Journal of Environmental Chemical Engineering, 2025)

Effects of isoprene on the ozonolysis of Δ3-carene and β-caryophyllene: Mechanisms of secondary organic aerosol formation and cross-dimerization - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Journal of Environmental Sciences, 2025)

Capillary water absorption characteristics of sandstone in Nankan Grotto: impacts from salt types and concentrations - Xuening Zhang; Jiawen Xie; Xiyong Wu; Sixiang Ling; Wei Wei; Xiaoning Li (Bulletin of Engineering Geology and the Environment, 2025)

Understanding the spatio-temporal dynamics of ecosystem services under multiple future scenarios to assess the progress of Sustainable Development Goals implementation - Ze Zhang; Weiguo Jiang; Ziyan Ling; Kaifeng Peng; Zhifeng Wu; Zhuo Li (Journal of Geographical Sciences, 2025)

Flame-retardant effect of scalable all clay composite films - Yixuan Fu; Zhaoyi Wang; Huiquan Liu; Ke Zhang; Lunxiang Zhang; Yongchen Song; Peng Wu; Yanghui Li; Zheng Ling (Applied Clay Science, 2025)

Mid-to-late Cenozoic tectonostratigraphic archives of the Qingshuihe Basin, NW China: tracing northeastward stepwise growth of the Tibetan Plateau - Jingxiong Tian; Han Zheng; Yanyun Ma; Wenzhong Wu; Yu Ma; Shengjin Huang; Ling He; Mingtao Li; Fang Liu; Xuedong Ma (International Geology Review, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Perspectives on the application of remote sensing technology in the cultivation of medicinal plants - Liwen Zhong; Xuemei Wu; Rong Ding; Chenghui Wang; Ling Li; Jieling Zhang; Jie Zhang; Rui Gu; Shihong Zhong (International Journal of Remote Sensing, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Corrigendum to “Distribution characteristics of terrestrial PGEs and its trend into the sea around Hainan Island, China” [Sci. Total Environ. 963 (2025) 178372] - Ling Wang; Yuyan Liu; Zhixin Li; Hongwei Yi; Zefeng Wang; Haofeng Liu; Dan Wu; Ye Li; Min Liu (Science of The Total Environment, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

An intelligent biomass aerogel label loaded with anthocyanin from wasted peanut seed coat for monitoring chilled chicken freshness - Ling Li; Chaomei Zhou; Yongju Xu; Xu Zheng; Yanping Wu; Bin Yan; Kai Zhong; Hong Gao (Food Hydrocolloids, 2025)

miR-9a and miR-10482-5p regulate the expression of chitin synthase and chitinase genes, enhancing lufenuron tolerance in Spodoptera frugiperda - Shanshan Ling; Zhimin Guo; Mengyan Wu; Jiahui Tang; Haixiang Lv; Jianhong Li; Kangsheng Ma (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Enhancement of electrocaloric strength by grain configuration design - Cuiping Xu; Xiaofan Sun; Peiqi Ji; Min Zhao; Tingfeng Li; Peng Chen; Hong-Ling Cai; X.S. Wu (Chemical Engineering Journal, 2025)

Genetic dissection for seedling root-related traits using multiple-methods in bread wheat (Triticum aestivum L.) - Naicui Wei; Yuqiong Hao; Jinbo Tao; Jiajia Zhao; Bangbang Wu; Ling Qiao; Xiaohua Li; Xingwei Zheng; Juanling Wang; Jun Zheng (Theoretical and Applied Genetics, 2025)

Electroacupuncture Promotes the Generation of Intestinal Treg Cells After Ischemic Stroke by Foxp3 Acetylation Regulation - Yonglin Chen; Ling Ouyang; Xinyi Yang; Bufan Wu; Lingling Meng; Jialin Gu; Yaling Wang; Juan Li; Jingjing Zhang; Xinyue Jing; Shengfeng Lu; Lanying Liu; et al. (Molecular Neurobiology, 2025)

Distribution characteristics of terrestrial PGEs and its trend into the sea around Hainan Island, China - Ling Wang; Yuyan Liu; Zhixin Li; Hongwei Yi; Zefeng Wang; Haofeng Liu; Dan Wu; Ye Li; Min Liu (Science of The Total Environment, 2025)

Deterministic quantum state and gate teleportation between distant superconducting chips - Jiawei Qiu; Yang Liu; Ling Hu; Yukai Wu; Jingjing Niu; Libo Zhang; Wenhui Huang; Yuanzhen Chen; Jian Li; Song Liu; Youpeng Zhong; Luming Duan; et al. (Science Bulletin, 2025)

Detection of Salmonella enterica in food using targeted mass spectrometry - Mengqi Chen; Miaoxi Peng; Muyun Yuan; Chengdong Huang; Jingwen Liu; Zuqing Wu; Wenrui Chen; Songqing Hu; Qing Liu; Jie Dong; Li Ling (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Enhanced fermentation of radish paocai with Lactiplantibacillus plantarum CBPC and shelf-life extension using e-beam irradiation - Ling Li; Qian Zhou; Zimeng Zheng; Luzhou Cai; Yanping Wu; Kai Zhong; Hong Gao (Food Bioscience, 2025)

3D high-density ambient noise imaging of the Nankou-Sunhe buried active fault in Beijing - Xu Liu; Ketong Hu; Rongyi Qian; Shuai Zhao; Jun Zhang; Jianyu Ling; Zhenning Ma; Zhiyong Wu; Yinhu Huang; Yongqi Meng; Zhanfei Li; Dongya Zhang (Engineering Geology, 2025)

Eco-friendly 2,4-D ionic cocrystal with enhanced release and reduced non-target losses - Zhiqing Li; Yuntian Xiao; Xiaoyang Qiu; Guozhong Zhang; Chuanhua Wu; Yongkang Liu; Ling Zhou; Junbo Gong; Qiuxiang Yin (Chemical Engineering Journal, 2025)

Creating rich closed nanopores in anthracite-derived soft carbon enables greatly-enhanced sodium-ion storage in the low-working-voltage region - Jiawei Gu; Yiwei You; Miao Liu; Ling Huang; Zhefei Sun; Junjie Liu; Liyuan Sha; Minghui Chen; Sha Li; Shunqing Wu; Qiaobao Zhang; Li Zhang (Chemical Engineering Journal, 2025)

Achieving efficient multifunctional platform utilizing sugarcane for water-electricity cogeneration and dyes reduction - Haitao Li; Qifan Qian; Xuan Li; Hui Cheng; Bingquan Wu; Xing Yi Ling; Jie Han (Chemical Engineering Journal, 2025)

Multifunctional microneedle patch synergized with electrical stimulation to regulate microenvironment for enhanced healing of infected diabetic wounds - Weikun Li; Xin Tan; Yanling Liang; Nuoya Chen; Diyi Feng; Yinghua Tao; Tao Liu; Xiaojing Wu; Huiqing Lu; Ling Liu; Feiling Feng; Liqin Ge (Chemical Engineering Journal, 2025)

Enhancement of the yield of poly (ethylene terephthalate) hydrolase production using cell membrane protection strategy - Xiao-Qian Chen; De-Ming Rao; Xing-Yu Zhou; Yang Li; Xiao-min Zhao; De-min Kong; Han Xu; Chu-Qi Feng; Lei Wang; Ling-Qia Su; Zheng-Fei Yan; Jing Wu (Bioresource Technology, 2025)

Metabolomics Analysis of Root Exudates of Cotton Seedling Under Cadmium Stress and the Alleviating Effect of Citric Acid - Xiang Wu; Yanxin Huang; Yan Cao; Xuyu Yan; Ling Li (Journal of Plant Growth Regulation, 2025)

Transcriptome analysis reveals genetic regulation of growth diversity in F2 intergeneric hybrids of Megalobrama amblycephala and Culter alburnus - Mengxue Luo; Yakui Tai; Mengdan Li; Yiyan Zeng; Chang Wu; Ling Liu; Hong Zhang; Li Ren; Shaojun Liu (Aquaculture, 2025)

Nitrogen and phosphorus budgets of the bullfrog (Aquarana catesbeiana) in different body weights - Xinyuan Li; Nan Jin; Weiqiang Wu; Xueshan Li; Kangle Lu; Kai Song; Peng Li; Zexiong Chen; Mohamed Mohsen; Ling Wang; Chunxiao Zhang (Aquaculture, 2025)

The inclusion of clay minerals accelerates biocrust formation and potentially boosts carbon storage capabilities - Shiqi Wang; Xinyu Li; Yuqing Li; Fanjian Zeng; Longkat Ayuba Gufwan; Lie Yang; Ling Xia; Shaoxian Song; María Luciana Montes; Mariela Alejandra Fernandez; Bin Zheng; Li Wu (Soil and Tillage Research, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Versatile electrospun cobalt-doped carbon films for rapid antibiotic degradation - Hao Wang; Yuzhen Cao; Liguo Shen; Xi-Lin Wu; Die ling Zhao; Renjie Li; Hongjun Lin (Journal of Environmental Management, 2025)

The aroma transformation of Japanese sea bass (Lateolabrax japonicas) through endogenous enzyme incubation during the lag phase of attached microorganisms - Xinru Liu; Junlan Guan; Yuanfan Yang; Ling Wu; Hui Ni; Qingbiao Li; Feng Chen (Food Chemistry, 2025)

The dynamic changes in physicochemical properties, functionalities, and gel properties of the starch-konjac gum mixture during the melting process: Based on three typical melting temperatures of DSC - Chen Zhang; Xin-Yu Li; Jing-Jing Li; Yu-Yan Zhang; Chu-Yun Wu; Zhi-Juan Wang; Ling-Zhi Zhang; Chunsen Wu; Qiao-Quan Liu; Jian-Ya Qian (Food Hydrocolloids, 2025)

Inactivation of Salmonella Typhimurium on mung bean seeds by combined application of microbubbles and disinfections and its effect on sprouting - Hsiu-Ling Chen; Shih-Kao Chou; Rachelle D. Arcega; Chih-Yao Hou; Jong-Shinn Wu; Chih-Tung Liu; Chun-Ping Hsiao; Li-Yun Hung; Chia-Min Lin (Food Control, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Improved free iodine capture by light-driven carbon-halogen bond cleavage in perovskite solar cells with dynamic self-healing ability - Cai-Xia Li; Wen-Wu Liu; Shi-Ji Da; Ling-Bin Kong (Chemical Engineering Journal, 2025)

Genetic dissection of flag leaf morphology traits and fine mapping of a novel QTL (Qflw.sxau-6BL) in bread wheat (Triticum aestivum L.) - Ling Qiao; Xingwei Zheng; Jiajia Zhao; Bangbang Wu; Yuqiong Hao; Xiaohua Li; Md Mostofa Uddin Helal; Jun Zheng (Theoretical and Applied Genetics, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Multi-omics Analysis Reveals Key Gut Microbiota and Metabolites Closely Associated with Huntington’s Disease - Shu-Xia Qian; Yu-Feng Bao; Xiao-Yan Li; Yi Dong; Xiao-Ling Zhang; Zhi-Ying Wu (Molecular Neurobiology, 2025)

RO4929097 inhibits NICD3 to alleviate pulmonary hypertension via blocking Notch3/HIF-2α/FoxM1 signaling pathway - Hao Zhu; Cheng Li; Fang Hu; Lifu Wu; Ling Wu; Meihua Zhou; Wei Liu; Aiguo Dai (In Vitro Cellular & Developmental Biology - Animal, 2025)

Clay minerals accelerate the formation of indoor biocrusts: Effects and mechanism - Long Qian; Jiping Wang; Jingshang Xiao; Lie Yang; Ling Xia; Shaoxian Song; María E. Farías; Zhaojun Wang; Li Wu (Soil and Tillage Research, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Integrating desertification control and wastewater treatment: Novel insights from the induction of artificial biocrusts using municipal wastewater-cultivated cyanobacterium - Jingshang Xiao; Jianhua Ji; Zulin Zhang; Ling Xia; Shaoxian Song; Shubin Lan; Ashiwin Vadiveloo; María Luciana Montes; Li Wu (Science of The Total Environment, 2024)

Combined effects of polyvinyl chloride or polypropylene microplastics with cadmium on the intestine of zebrafish at environmentally relevant concentrations - Huan Li; Zhongchao Yang; Yuxuan Liu; Peipei Sun; Bing Wu; Ling Chen (Science of The Total Environment, 2024)

Steady existence of Escherichia coli co-resistant to carbapenem and colistin in an animal breeding area even after the colistin forbidden - Yanyu Guan; Zhongyi Wang; Zhenhua Shang; Huiyun Zou; Ling Zhao; Xinjiao Hou; Tianle Wu; Min Meng; Xuewen Li (Journal of Environmental Management, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

The combination of oxalic acid and uric acid degrading probiotic from traditional Chinese fermented food reduces calcium accumulation and prevents kidney stones formation in rats - Yanyi Chen; Zhenmin Ling; Jing Ji; Zemin Wang; Ying Wu; Jingjing Fan; El-Sayed Salama; Sourabh Kulshreshtha; Pu Liu; Xiangkai Li (Food Bioscience, 2024)

The roles of organic amendments and plant treatments in soil polychlorinated biphenyl dissipation under oxic and sequential anoxic–oxic conditions - Meng Yan; Tingting Peng; Ling Zhao; Qigang Li; Ruini Wu; Yiming Wang; Yucheng Wu; Ying Teng; Xingjia Xiang; Jun Zeng; Xiangui Lin (Environmental Research, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

PinX1 plays multifaceted roles in human cancers: a review and perspectives - Dian You; Kaiwen Tong; Yuan Li; Ting Zhang; Yongqiang Wu; Ling Wang; Guangming Chen; Xiaoying Zhang (Molecular Biology Reports, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

Identification and culture of functional salivary gland ductal epithelial cells - Han-Shu Zhang; You-Wei Zhao; Xin-Yi Tao; Xin Cong; Li-Ling Wu; Guang-Yan Yu; Yan Zhang (Histochemistry and Cell Biology, 2024)

Long-term exposure to low-level ozone and the risk of hypertension: A prospective cohort study conducted in a low-pollution region of southwestern China - Fuyan Zhang; Ziyun Wang; Ling Li; Xu Su; Yuandong Hu; Yu Du; Qingqing Zhan; Tianlin Zhang; Qinyu An; Tao Liu; Yanli Wu (Science of The Total Environment, 2024)

Transcriptional responses of detoxification genes to coumaphos in a nontarget species, Galleria mellonella (greater wax moth) (Lepidoptera: Pyralidae), in the beehive environment - Shengyun Li; Wen-Yen Wu; Ling-Hsiu Liao; May R. Berenbaum (Pesticide Biochemistry and Physiology, 2024)

Reseeding increased plant biomass production and soil fertility, but not plant species diversity in degraded grasslands in China - Hasbagan Ganjurjav; Mingjie Li; Ling Han; Yubao Sha; Zheng Li; Xuyang Han; Guoxu Ji; Rihan Wu; Yandan Ma; Guozheng Hu; Elise Gornish; Qingzhu Gao (Journal of Environmental Management, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Effects of NOx and NH3 on the secondary organic aerosol formation from α-pinene photooxidation - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2024)

A CRISPR/RfxCas13d-mediated strategy for efficient RNA knockdown in mouse embryonic development - Lin Zhang; Shi-Meng Cao; Hao Wu; Meng Yan; Jinsong Li; Ling-Ling Chen (Science China Life Sciences, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Association between dust exposure and lung function levels in steelworkers: mediation analysis of inflammatory biomarkers - Yizhan Zheng; Jiaqi Hu; Jiaqi Chen; Huan Wang; Ziqi Zhao; Hongmin Zhu; Zheng Li; Nan Wang; Xinyang Chen; Mingyue Liu; Zhenghao Luo; Shangmingzhu Zhang; et al. (International Archives of Occupational and Environmental Health, 2024)

Genotypic and phenotypic correlations in tooth agenesis: insights from WNT10A and EDA mutations in syndromic and non-syndromic forms - Youmei Wu; Ling Lai; Junyang Chen; Xinzhu Li; Jin Hou (Human Genetics, 2024)

A transfer learning-based network model integrating kernel convolution with graph attention mechanism for point cloud segmentation of livestock - Shi Yuanyuan; Wang Yuxiao; Yin Ling; Wu Zhenfang; Lin Junyong; Tian Xuhong; Huang Qiong; Zhang Sumin; Li Zhiying (Computers and Electronics in Agriculture, 2024)

Heat acclimation alleviates the heat stress-induced impairment of vascular endothelial cells - Jirui Wen; Zhengdong Lin; Juan Cheng; Can Li; Ling Wang; Yuhao Zou; Xuehong Wan; Jifeng Liu; Jiang Wu (Tissue and Cell, 2024)

Imbalance of mitochondrial quality control regulated by STING and PINK1 affects cyfluthrin-induced neuroinflammation - Ji Zhao; Yi-kai Qiu; Yong-xing Xie; Xiao-yu Li; Yu-bin Li; Bing Wu; Yu-wen Wang; Xue-yan Tian; Yan-ling Lv; Ling-he Zhang; Wen-li Li; Hui-fang Yang (Science of The Total Environment, 2024)

Green synthesis of a superhydrophobic porous organic polymer for the removal of volatile organic compounds at high humidity - Hongxia Zhu; Li Gong; Ling Jiang; Xianyu Liu; Laigang Hu; Wenhao Wu; Daohui Lin; Kun Yang (Science of The Total Environment, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Excellent electrocaloric performance achieved by the high-entropy strategy - Xiaofan Sun; Cuiping Xu; Yanzhou Lu; Min Zhao; Shulin Jiao; Zheng Tang; Dong Li; Hong-Ling Cai; X.S. Wu (Chemical Engineering Journal, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Spatial differentiation of the leaf area index in forests in ecological transition zones and its environmental response - Geyang Li; Chengzhang Zhao; Dingyue Liu; Lei Ling; Chenglu Huang; Peixian Zhang; Suhong Wang; Xianshi Wu (European Journal of Forest Research, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

Effects of Dietary Supplementation of Zinc Oxide Quantum Dots on Growth Performance and Gut Health in Broilers - Lei Shi; Meng-Ling Ruan; Bing-Bing Zhang; Guo-Xin Gong; Xue-Wu Li; Alainaa Refaie; Lv-Hui Sun; Zhang-Chao Deng (Biological Trace Element Research, 2024)

Distribution characteristics and ecological risk analysis of microplastics in sediments and effluents related to offshore oil and gas activities in the Bohai Sea, China - Yuxia Li; Lingna Kong; Zhongxiu Li; Qing Su; Ling Qu; Xiaomeng Wang; Jianbo Han; Jiayi Cheng; Liang Wu; Naidong Zhang (Marine Pollution Bulletin, 2024)

Immunosuppressive alkaloids from Narcissus tazetta subsp. Chinensis and the mechanism of (+)-narciclasine in vitro and in vivo - Wen-Ling Wang; Xiu-Yin Wu; Xing-Yan Luo; Yu-Qin Tang; Jia Cui; Xin-Yue Huang; Yu-Chen Jiang; Yang Liu; Li-Mei Li (Phytochemistry, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

In silico degradation of fluoroquinolones by a microalgae-based constructed wetland system - Fuxing Wu; Meijin Du; Jianglong Ling; Renjie Wang; Ning Hao; Zini Wang; Xixi Li (Journal of Hazardous Materials, 2024)

Subchronic oral toxic effects of 2,4-dinitroaniline in wistar rats: A comprehensive toxicity evaluation - Ling Hu; Xiaoxu Wu; Jinjin Peng; Biao Yan; Jinquan Li; Yongyong Guo; Jian Han (Food and Chemical Toxicology, 2024)

Digitalising BIPV energy simulation: A cross tool investigation - Rebecca Jing Yang; Yusen Zhao; Sujan Dev Sureshkumar Jayakumari; Astrid Schneider; S. Prithivi Rajan; Jonathan Leloux; Philippe Alamy; Gavin Prasetyo Raharjo; Fedele Rende; Tharushi Samarasinghalage; Ana Marcos Castro; Nuria Martin Chivelet; et al. (Energy and Buildings, 2024)

Enhancement of chlorine-resistant bacteria inactivation via coupling Magnéli phase Ti4O7-based electrochemical oxidation and chlorination - Sheng-Nan Li; Shu-Xian Zheng; Zi-Xuan Zheng; Yu Ling; Hai-Ming Wu; Hai Liu (Chemical Engineering Journal, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Assessment and driving factor analysis of total nitrogen loads: a case study of counties from 2000 to 2020 in Henan Province, China - Xingming Li; Ling Li; Shuaiqi Chen; Yuanyi Shang; Yong Wu; Donghao Li; Xiuli Wang (Stochastic Environmental Research and Risk Assessment, 2024)

Deamidation enables pathogenic SMAD6 variants to activate the BMP signaling pathway - Ling Li; Lei Lu; Ziqi Xiao; Jingyi Lv; Hefeng Huang; Bo Wu; Tongjin Zhao; Chengtao Li; Weimin Wang; Hongyan Wang (Science China Life Sciences, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

The secondary visual cortex mediated the enhancement of associative learning on methamphetamine self-administration behaviors - Cai-ling Wang; Dan-ni Cao; Ning Wu; Ying-jie Zhu; Jin Li (Psychopharmacology, 2024)

Identification and characterization of a novel type II toxin-antitoxin system in Aeromonas veronii - Caihong Ji; Ting He; Binbin Wu; Xiaomei Cao; Xiaping Fan; Xia Liu; Xiaodan Li; Miao Yang; Jihan Wang; Ling Xu; Shengbiao Hu; Liqiu Xia; et al. (Archives of Microbiology, 2024)

CircPDSS1 (hsa_circ_0017998) silencing induces ferroptosis in non-small-cell lung cancer cells by modulating the miR-137/SLC7A11/GPX4/GCLC axis - Ling Wu; Ni Li; Linwen Zhu; Guofeng Shao (Toxicology in Vitro, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Reduction of the exchangeable cadmium content in soil by appropriately increasing the maturity degree of organic fertilizers - Bing Zhao; Zhi Xu; Shaoming Li; Zhixin Yang; Wen Ling; Zhicheng Wu; Jiangfei Gao; Yuyun Wang (Journal of Environmental Management, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Multi-core@shell double confinement of carbon dots for giant enhancement of thermal Stability: Photoluminescence and lasing up to 1000 K - Shaofeng Zhang; Jiatong Wang; Zhenhui Chen; Jingsong Chen; Zefeng Wu; Ling Li; Peiguang Yan; Wenfei Zhang (Chemical Engineering Journal, 2024)

A novel bimetallic-polyanion Na4Fe2.82Ni0.18(PO4)2P2O7 cathode with superior rate performance and long cycle-life for sodium-ion batteries - Wenbin Fei; Yian Wang; Xiaoping Zhang; Jiuxiang Zhang; Shengxing Lu; Kexin Rao; Keyi Sun; Mengting Deng; Yuxuan Liu; Qingqiang Li; Ling Wu; Yulei Sui (Chemical Engineering Journal, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and the Risk of Leukoaraiosis in a South Chinese Han Population: A Case–Control Study - Dong-can Mo; Xiao-ju Wu; Xiao-ling Li; Liu-yu Liu; Yi-ying Jiang; Guo-qiu Zhou; Li-jie Chen; Jiao-xing Li; Man Luo (Biochemical Genetics, 2024)

Multi‐omics analyses reveal the signatures of metabolite transfers across trophic levels in a high‐ CO 2 ocean - Mengcheng Ye; Jiale Zhang; Mengting Xiao; Jiali Huang; Yunyue Zhou; John Beardall; John A. Raven; Guang Gao; Xiao Liang; Fenghuang Wu; Baoyi Peng; Leyao Xu; et al. (Limnology and Oceanography, 2024)
Although the diverse impacts of elevated dissolved CO 2 and warming on organisms within various trophic levels in marine food webs are well documented, we have yet to explore the biological links across different levels of biological organization from primary producers to secondary producers on an evolutionary time scale in a high‐CO 2 ocean. Here, we cultured a model marine diatom Phaeodactylum tricornutum (primary producer) in predicted future high‐CO 2 and/or warming conditions for ~ 1250 d with an experimental evolution approach and then fed them to the clam Coelomactra antiquata (secondary producer). We present an in‐depth multi‐omics analysis along the methylome (primary producer)–transcriptome (primary producer)–metabolome (primary producer)–metabolome (secondary producer) continuum. Our results showed that the downregulated terpenoid backbone biosynthesis in the methylome and transcriptome lead to decreased pyruvate levels and upregulation of some pathways (such as phenylalanine metabolism) in the metabolome of the primary producer in the long‐term warming conditions. These changes in metabolomic profile in the primary producer were then transferred to the secondary producer, resulting in changes in abundance of some metabolites, such as decreases in pyruvate, and in pyruvaldhyde (also known as methylglyoxal), and increases in 2‐hydroxylamino‐4,6‐dinitrotoluene. Our study provides a new insight into the molecular mechanisms underlying the trophic transfer from primary to secondary producers in a future high‐CO 2 ocean and may provide more accurate projections of marine ecosystem services and functions over the next century.

A reinforcement learning-driven adaptive decomposition algorithm for multi-objective hybrid seru system scheduling considering worker transfer - Yuting Wu; Ling Wang; Rui Li; Jing-fang Chen (Swarm and Evolutionary Computation, 2024)

Hydrodynamics and dissolved organic matter components shaped the fate of dissolved heavy metals in an intensely anthropogenically disturbed estuary - Ling Zhang; Yunchao Wu; Jinlong Li; Zhixin Ni; Yuzheng Ren; Jizhen Lin; Xiaoping Huang (Science of The Total Environment, 2024)

A deep learning-based approach for fully automated segmentation and quantitative analysis of muscle fibers in pig skeletal muscle - Zekai Yao; Jingjie Wo; Enqin Zheng; Jie Yang; Hao Li; Xinxin Li; Jianhao Li; Yizhi Luo; Ting Wang; Zhenfei Fan; Yuexin Zhan; Yingshan Yang; et al. (Meat Science, 2024)

A multi-source proxies approach to identifying local processes in lower Permian black shale impacting on the sedimentary environment of eastern Palaeo-Tethys Ocean - Chunwei Sun; Sixiang Ling; Xiaoning Li; Xiyong Wu; Marc-Henri Derron; Michel Jaboyedoff (Marine and Petroleum Geology, 2024)

Mangrove mud clam as an effective sentinel species for monitoring changes in coastal microplastic pollution - Yinglin Wu; Zitong Li; Yanxia Deng; Bingbing Bian; Ling Xie; Xianye Lu; Jingqiu Tian; Ying Zhang; Liyun Wang (Journal of Hazardous Materials, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Safety assessment of polypropylene self-heating food container: The release of microplastics and volatile organic compounds - Can Xu; Jia-ling Hu; Ben Dong; Qin-bao Lin; Si-liang Wu; Jie Chen; Jing Wang; Dan Li; Huai-ning Zhong (Food Packaging and Shelf Life, 2024)

In-situ constructed interface buffer layer enabled highly reversible Zn Deposition/Stripping for long-lifespan aqueous zinc metal anodes - Li Zhou; Weibin Zhou; Hongrui Wang; Qi Deng; Xingtong Ai; Xian-Xiang Zeng; Xiongwei Wu; Congshan Zhou; Wei Ling (Chemical Engineering Journal, 2024)

Efficient nutrient recycling from wastewater to deserts: A comparative study on biocrust cyanobacteria performance - Li Wu; Cheng Zhang; Ashiwin Vadiveloo; María L. Montes; Ling Xia; Shaoxian Song; Mariela A. Fernandez; Shubin Lan (Chemical Engineering Journal, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Exploring the phosphorus–starch content balance mechanisms in maize grains using GWAS population and transcriptome data - Bowen Luo; Haiying Zhang; Zheng Han; Xiao Zhang; Jianyong Guo; Shuhao Zhang; Xianfu Luo; Jin Zhao; Wei Wang; Guohui Yang; Chong Zhang; Jing Li; et al. (Theoretical and Applied Genetics, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

On-road evaluation and regulatory recommendations for NOx and particle number emissions of China VI heavy-duty diesel trucks: A case study in Shenzhen - Weixia Li; Zhurong Dong; Ling Miao; Guoyuan Wu; Zhijun Deng; Jianfeng Zhao; Wenwei Huang (Science of The Total Environment, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Mapping the spatial distributions of oxide abundances and Mg# on the lunar surface using multi-source data and a new ensemble learning algorithm - Chaofa Bian; Kefei Zhang; Yunzhao Wu; Suqin Wu; Yu Lu; Hongtao Shi; Huaizhan Li; Dongsheng Zhao; Yabo Duan; Ling Zhao; Huajing Wu (Planetary and Space Science, 2024)

Multiple pathway exposure risks and driving factors of heavy metals in soil-crop system in a Pb/Zn smelting city, China - Jianwei Liu; Shuo Qiao; Hui Chen; Shilong Zhao; Chang Li; Yong Wu; Donghao Li; Ling Li (Journal of Cleaner Production, 2024)

Efficient detection of geosmin and 2-methylisoborneol in natural/drinking water by UIO66-NH2 composite-derived porous carbon - Wei Liu; Ming Yang; Shuang Wang; Yan-Sai Bao; Yong-He Cui; Ling-Xu Meng; Liang-Cheng Li; Yang Wu; Yu-Yang Zhang (Journal of Environmental Chemical Engineering, 2024)

Using untargeted metabolomics and GC-IMS to analysis the influence of fat distribution on the flavor formation of bacon - Yang Yufei; Li Pan; Cheng Jia; Wu Guofei; Ren Hongqiang; Wang Ling; Lu Hongzhao; Zeng Wenxian; Zhang Tao (Food Bioscience, 2024)

Efficient Cr(VI) remediation by electrospun composite porous nanofibers incorporating biomass with metal oxides and metal-organic framework - Ronggang Luo; Ruiqi Li; Zhangzhi Zheng; Lianpeng Zhang; Linkun Xie; Chunhua Wu; Siqun Wang; Xijuan Chai; Nyuk Ling Ma; Mu. Naushad; Guanben Du; Kaimeng Xu (Environmental Pollution, 2024)

Enzyme-driven converter and amplifier for inert double-stranded DNA without sequence restrictions - Xiaolong Li; Minghao Hu; Tianci Xie; Zixuan Zhu; Chen Ling; Tongbo Wu (Chemical Engineering Journal, 2024)

High capacity and long service in sodium-ion batteries achieved by the refinement of BiOCl from lamellar to flower-like in ether electrolyte - Sheng-Li Wei; Yan-Ling Yang; Xiao-Lei Shi; Yu Sun; Jin-Geng Chen; Xue-Feng Tian; Yuan-Ting Wu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Paeoniflorin exerts anti-PTSD effects in adult rats by modulating hippocampus and amygdala histone acetylation modifications in response to early life stress - Hanfang Xu; Tiange Zhang; Ling Li; Yue Qu; Lanxin Li; Yuqi Yan; Lili Wu; Can Yan (Chemico-Biological Interactions, 2024)

Residual networks without pooling layers improve the accuracy of genomic predictions - Zhengchao Xie; Xiaogang Xu; Ling Li; Cuiling Wu; Yinxing Ma; Jingjing He; Sidi Wei; Jun Wang; Xianzhong Feng (Theoretical and Applied Genetics, 2024)

Deep-injected straw incorporation enhances subsoil quality and wheat productivity - Jun Ling; Jie Zhou; Gong Wu; De-Qiang Zhao; Zhi-Tong Wang; Yuan Wen; Shun-Li Zhou (Plant and Soil, 2024)

Microscopic weathering characteristics and deterioration mechanisms of sandstone in the Nankan Grotto, northern Sichuan, China - Xuening Zhang; Xiyong Wu; Sixiang Ling; Wei Wei; Fengrui Wang; Jie Wang; Shengming Li (Bulletin of Engineering Geology and the Environment, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Probiotics Pediococcus acidilactici GR-1 promotes the functional strains and remodels gut microbiota to reduce the Cr(VI) toxicity in a dual-chamber simulated intestinal system - Xing Wang; Zemin Wang; Shaochen Su; Ying Wu; Jingjing Fan; Xiaoxiao Hou; Kunyue Zhang; El-Sayed Salama; Saurabh Kulshrestha; Zhenmin Ling; Pu Liu; Xiangkai Li (Chemosphere, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Rotavirus infection inhibits SLA-I expression on the cell surface by degrading β2 M via ERAD-proteasome pathway - Zhaoyang Jing; Ling Wu; Yudi Pan; Liaoyuan Zhang; Xin Zhang; Da Shi; Hongyan Shi; Jianfei Chen; Zhaoyang Ji; Jiyu Zhang; Tingshuai Feng; Jin Tian; et al. (Veterinary Microbiology, 2024)

Iron-modified biochar effectively mitigates arsenic-cadmium pollution in paddy fields: A meta-analysis - Beilei Wei; Dongliang Zhang; Paramsothy Jeyakumar; Lukáš Trakal; Hailong Wang; Keke Sun; Ying Wei; Xiaoqi Zhang; Huarong Ling; Shijie He; Hanqian Wu; Zhigang Huang; et al. (Journal of Hazardous Materials, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Investigation on microwave pyrolysis mechanism and synergism of seaweed and rice husk with comprehensive experimental and theoretical study - Shengxian Xian; Qing Xu; Haowei Li; Yujian Wu; Jinshan Ling; Longwei Jiang (Fuel, 2024)

Characterization of ultrasound-assisted covalent binding interaction between β-lactoglobulin and dicaffeoylquinic acid: Great potential for the curcumin delivery - Gongshuai Song; Fang Li; Xiaotong Shi; Jiayuan Liu; Yong Cheng; Yuhan Wu; Zexu Fang; Yuxiao Zhu; Danli Wang; Tinglan Yuan; Ruikang Cai; Ling Li; et al. (Food Chemistry, 2024)

Utilization of unrejected ammonium for fouling prevention in a forward osmosis process tested with real primary wastewater from Hong Kong - Paula Jungwon Choi; Xinning Zhang; Noman Khalid Khanzada; Di Wu; Ling Li; Am Jang; Alicia Kyoungjin An (Desalination, 2024)

Core-shell DOPO/caramel nano-polymer with desirable UV shielding and flame retardancy for polyamide 6 fabric - Wen-Jie Jin; Xian-Wei Cheng; Sheng-Nan Ma; Ling Li; Rui-Kai Wu; Jin-Ping Guan (Chemical Engineering Journal, 2024)

Joint toxicity of cadmium (II) and microplastic leachates on wheat seed germination and seedling growth - Ling Du; Dongming Wu; Xi Yang; Li Xu; Xu Tian; Youping Li; Lijuan Huang; Yanmei Liu (Environmental Geochemistry and Health, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Exploring the impact of cadmium stress on morphophysiological traits and GhPCS gene expression in upland cotton seedlings - Xuyu Yan; Xiang Wu; Juan Li; Ling Li (South African Journal of Botany, 2024)

Simplified estimates of soil nematode body mass using maximum diameter: Insights from large-scale grasslands across China - Quanhui Ma; Yu Zhu; Ying Chen; Wenjia Wu; Xue Qing; Ting Liu; Yibo Li; Yao Wang; Yanan Li; Deli Wang; Jushan Liu; Ling Wang (Soil Biology and Biochemistry, 2024)

Pijx confers broad-spectrum seedling and panicle blast resistance by promoting the degradation of ATP β subunit and OsRbohC-mediated ROS burst in rice - Ning Xiao; Yunyu Wu; Xiaoxiang Zhang; Zeyun Hao; Zichun Chen; Zefeng Yang; Yue Cai; Ruyi Wang; Ling Yu; Zhiping Wang; Yue Lu; Wei Shi; et al. (Molecular Plant, 2024)

Degradation of prometryn during UV/persulfate process: Kinetics and disinfection by-product formation - Chen-Yan Hu; Hao Liu; Ling Xu; Yi-Li Lin; Qiang-Bing Wang; Dan-Dan Huang; Yi-Hui Wu; Zi-Yi Dong; Sheng-Jie Ji (Journal of Water Process Engineering, 2024)

Existing levels of biodiversity and river location may determine changes from small hydropower developments - Qingyi Luo; Shuyin Li; Tsuyoshi Kinouchi; Naicheng Wu; Xiaocheng Fu; Chang Ling; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Journal of Environmental Management, 2024)

In situ bismuth ion exchange plating micro-electrochemical sensor based on laser-induced graphene for trace Cd2+ and Pb2+ detection - Xiaoming Yuan; Xiuwen Wu; Yunhan Ling; Shilin Li; Jianyue Chen; Zhengjun Zhang (Journal of Environmental Chemical Engineering, 2024)

Functional exploration of lunasin peptide in transgenic maize (Zea mays L.) and its role in controlling mitophagy in MDA-MB-231 cells - Yuqiong Hao; Bangbang Wu; Meiru Li; Mingyang Yuan; Ling Qiao; Jiajia Zhao; Xingwei Zheng; Xiaohua Li; Yuzhi Wang; Yanbin Wang; Jun Zheng (Food Bioscience, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Intrauterine and early postnatal exposures to submicron particulate matter and childhood allergic rhinitis: A multicity cross-sectional study in China - Yachen Li; Lifeng Zhu; Jing Wei; Chuansha Wu; Zhuohui Zhao; Dan Norbäck; Xin Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Ling Zhang; et al. (Environmental Research, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Toward highly-robust MXene hybrid memristor by synergetic ionotronic modification and two-dimensional heterojunction - Songtao Ling; Shengran Lin; Yinzhong Wu; Yang Li (Chemical Engineering Journal, 2024)

Effect of mixture microstructure/compatibility on the properties of type-A gelatin-dextran edible films - Ling Wu; Bo Cui; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Katsuyoshi Nishinari; Meng Zhao (Carbohydrate Polymers, 2024)

Advances in Atmospheric Radiation: Theories, Models, and Their Applications. Part II: Radiative Transfer Models and Related Applications - Hua Zhang; Feng Zhang; Lei Liu; Yuzhi Liu; Husi Letu; Yuanjian Yang; Zhengqiang Li; Kun Wu; Shuai Hu; Ming Li; Tie Dai; Fei Wang; et al. (Journal of Meteorological Research, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Strategies for regulating the intensity of different cyanobacterial blooms: Insights from the dynamics and stability of bacterioplankton communities - Baohai Zheng; Peichang Dong; Teng Zhao; Yuting Deng; Jie Li; Lirong Song; Jinna Wang; Ling Zhou; Junqiong Shi; Zhongxing Wu (Science of The Total Environment, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Metabolomics reveals how spinach plants reprogram metabolites to cope with intense stress responses induced by photoaged polystyrene nanoplastics (PSNPs) - Daofen Huang; Ling Ding; Shuhua Wang; Rui Ding; Xinran Qiu; Jianlong Li; Zhengdong Hua; Shasha Liu; Renren Wu; Xujun Liang; Xuetao Guo (Journal of Hazardous Materials, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Intelligent multi-objective optimization of 3D printing low-carbon concrete for multi-scenario requirements - Song-Yuan Geng; Qi-Ling Luo; Bo-Yuan Cheng; Li-Xiao Li; Dong-Chang Wen; Wu-Jian Long (Journal of Cleaner Production, 2024)

Modelling monthly-gridded carbon emissions based on nighttime light data - Ruxing Wan; Shuangyue Qian; Jianhui Ruan; Li Zhang; Zhe Zhang; Shuying Zhu; Min Jia; Bofeng Cai; Ling Li; Jun Wu; Ling Tang (Journal of Environmental Management, 2024)

Semisolid medium internal phase emulsions stabilized by dendritic-like mushroom cellulose nanofibrils: Concentration effect and stabilization mechanism - Ling Zhang; Xiang Li; Xianbing Xu; Liang Song; Anqi Bi; Chao Wu; Yunjiao Ma; Ming Du (Food Chemistry, 2024)

Dynamic surface-enhanced Raman spectroscopy and positively charged probes for rapid detection and accurate identification of fungal spores in infected apples via deep learning methods - Jinghong Wang; Rui Zhu; Yehang Wu; Le Tang; Cong Wang; Mengqing Qiu; Ling Zheng; Pan Li; Shizhuang Weng (Food Control, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

The effect of the mitochondria-targeted antioxidant Mito-tempo during sperm ultra-rapid freezing - Chun-Yuan Li; Juan Liu; Qi-Yuan Zheng; Nian Liu; Xi-Ling Huang; Yu-Yin Wu; Xing-Feng Yao; Qing-Ying Tan; Ying Huang; Chuan-Huo Hu; Chang-Long Xu (Cryobiology, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Multiple thermal events recorded in the Acasta Gneiss Complex: Evidence from in-situ dating of zircon, titanite, and apatite - Qingfeng Mei; Jinhui Yang; Jinfeng Sun; Qiuli Li; Shitou Wu; Xiaoxiao Ling; Peng Peng; Hao Wang (Science China Earth Sciences, 2024)

TON1 recruiting motif 21 positively regulates the flavonoid metabolic pathway at the translational level in Arabidopsis thaliana - Ling Wu; Xuan Chen; Ping Zhang; Shaowei Yan; Tingzhi Zhang; Yuanyuan Li (Planta, 2024)
Main conclusion This study reveals that TRM21 acts as a positive regulator of flavonoid biosynthesis at the translational level in Arabidopsis , impacting both secondary metabolites and genes associated with root hair growth. Abstract TRM (TONNEAU1-recruiting motif) superfamily proteins are reported to be involved in microtubule assembly. However, the functions of this protein family are just beginning to be uncovered. Here, we provide metabolomic and genetic evidence that 1 of the 34 TRM members, TRM21 , positively regulates the biosynthesis of flavonoids at the translational level in Arabidopsis thaliana . A loss-of-function mutation in TRM21 led to root hair growth defects and stunted plant growth, accompanied by significant alterations in secondary metabolites, particularly a marked reduction in flavonoid content. Interestingly, our study revealed that the transcription levels of genes involved in the flavonoid biosynthesis pathway remained unchanged in the trm21 mutants, but there was a significant downregulation in the translation levels of certain genes [ flavanone 3-hydroxylase ( F3H ), dihydroflavonol-4-reductase ( DFR ), anthocyanidin reductase ( ANR ), flavanone 3’-hydroxylase ( F3'H ), flavonol synthase ( FLS ), chalcone synthase ( CHS )]. Additionally, the translation levels of some genes related to root hair growth [ RHO-related GTPases of plant 2 ( ROP2 ), root hair defective 6 ( RHD6 ), root hair defective 2 ( RHD2 )] were also reduced in the trm21 mutants. Taken together, these results indicate that TRM21 functions as a positive regulator of flavonoid biosynthesis at the translational level in Arabidopsis .

Angelica dahurica extract and its effective component bergapten alleviated hepatic fibrosis by activating FXR signaling pathway - Chong Gao; Zhong-He Hu; Zhen-Yu Cui; Yu-Chen Jiang; Jia-Yi Dou; Zhao-Xu Li; Li-Hua Lian; Ji-Xing Nan; Yan-Ling Wu (Journal of Natural Medicines, 2024)

Brittleness ductility transition depth of new fracture in the Baodi Miaozhuang Uplift - He Li; Yi-Bing Dong; Yi-Xi Wang; Wu-Ping Gao; Cheng-Guo Yan; Ling-Ling Cai; Bo-Yang Wu; Peng Zhao (Applied Geophysics, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Efficient electrochemical oxidation of refractory organics in actual petrochemical reverse osmosis concentrates by Ti/SnO2-Sb mesh anode - Chunxia Zhao; Zefeng Wu; Junda Lai; Ling Liu; Hui Li; Hongjie Wang (Process Safety and Environmental Protection, 2024)

Enhanced atmospheric water harvesting (AWH) by Co-based MOF with abundant hydrophilic groups and open metal sites - Sihan Li; Peng Wu; Long Chen; Yiwen Tang; Yanhe Zhang; Ling Qin; Xiaofei Qin; Haibo Li (Journal of Water Process Engineering, 2024)

Yield compensation among plant regions improves soybean adaptation to short-term high-temperature stress during the reproductive period - Fang Li; Yiping Shao; Zhitong Wang; Zhenyuan Chen; Jun Ling; Gong Wu; Xin Wang; Shunli Zhou (Journal of Plant Physiology, 2024)

Improvement of mechanical properties and corrosion resistance of SLM-AlSi10Mg alloy by an eco-friendly electric pulse treatment - Ling Xue; Chengzhi Liao; Mingxia Wu; Qiang Li; Zhenshang Hu; Yi Yang; Jian Liu (Journal of Cleaner Production, 2024)

Carbon fiber powder in sustainable asphalt pavements: Improving microwave self-healing capacity and low-temperature performance - Xueyuan Ren; Aimin Sha; Jiange Li; Wei Jiang; Wenxiu Jiao; Wangjie Wu; Xianwu Ling (Journal of Cleaner Production, 2024)

Effects of NO2 and SO2 on the secondary organic aerosol formation from β -pinene photooxidation - Xiangyu Zang; Zhaoyan Zhang; Yingqi Zhao; Gang Li; Hua Xie; Weiqing Zhang; Guorong Wu; Xueming Yang; Ling Jiang (Journal of Environmental Sciences, 2024)

Study on the decarbonization mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Shuning Qin; Ling He; Yawen Wu; Qingrui Liu; Yan Jin (Fuel, 2024)

Fe-Ni bimetallic adsorbent for efficient As2O3 removal from coal-fired flue gas under a wide temperature range: Experimental and DFT study - Xin Zhang; Bowen Zhang; Qilin Zhang; Jiang Wu; Lingyu Ye; Shuai Li; Yang Ling; Guangqian Luo; Hong Yao; Biao Wu (Fuel, 2024)

Methylglyoxal scavenging capacity of fiber-bound polyphenols from highland barley during colonic fermentation and its modulation on methylglyoxal-interfered gut microbiota - Jinxin Li; Hao Zhang; Wei Liu; Xijuan Yang; Ling Zhu; Gangcheng Wu; Hui Zhang (Food Chemistry, 2024)

Inputs and transport of acid mine drainage-derived heavy metals in karst areas of Southwestern China - Shichan Qin; Xuexian Li; Jiangxun Huang; Wei Li; Pan Wu; Qingguang Li; Ling Li (Environmental Pollution, 2024)

Reversible hydrochromic CsPbBr3/Cs4PbBr6@MCM-41 to enable organic solvent polarity detection - Yan Chen; Ying Liu; Junhao Li; Chunli Zhao; Yougui Yang; Ling He; Meng Wu; Qi Wang; Yong Yang; Chunjian Wang; Dacheng Zhou; Jianbei Qiu (Chemical Engineering Journal, 2024)

On-microparticle construction of endothelialized liver microtissues for drug testing - Zengnan Wu; Yajing Zheng; Jin-Ming Lin; Yuxuan Li; Yongning Lin; Xiaorui Wang; Ling Lin (Chemical Engineering Journal, 2024)

Effects of NO and SO2 on the secondary organic aerosol formation from isoprene photooxidation - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Atmospheric Environment, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Source-oriented risk assessment of heavy metal(loid)s in agricultural soils around a multimetal smelting area near the Yellow River, China - Hui Chen; Shuo Qiao; Chang Li; Yong Wu; Donghao Li; Ling Li; Jianwei Liu (Environmental Geochemistry and Health, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Correlation study of SNP of glycogen degradation metabolism related genes and glycogen content in Haliotis discus hannai - Xueying Tang; Sisi Li; Ling Zhuo; Qingya Zhang; Fucun Wu; Siheng Lin (Aquaculture, 2024)

Identification of point and nonpoint emission sources of neonicotinoid pollution in regional surface water - Yuanchen Chen; Jun Ling; Wenfei Yu; Li Zhang; Ruxin Wu; Dan Yang; Jiajia Qu; Hangbiao Jin; Zhen Tao; Yuexin Shen; Ruirui Meng; Jingtong Yu; et al. (Water Research, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Insight into the enhanced catalytic performance of phosphate-modified ZrO2/SBA-15 for the conversion of biobased 2,5-dimethylfuran and ethylene into p-xylene - Chengming Wu; Quan Wang; Jifan Li; Chun-Ling Liu; Wen-Sheng Dong (Chemical Engineering Journal, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Aureusidin ameliorates 6-OHDA-induced neurotoxicity via activating Nrf2/HO-1 signaling pathway and preventing mitochondria-dependent apoptosis pathway in SH-SY5Y cells and Caenorhabditis elegans - Kun Hu; Susu Zhu; Fanyu Wu; Yongzhen Zhang; Minyue Li; Ling Yuan; Wenjing Huang; Yichi Zhang; Jie Wang; Jie Ren; Hao Yang (Chemico-Biological Interactions, 2024)

Identification of antibiotic resistant bacteria communities and a GeoChip based study of resistome in Fusarium wilt diseased and healthy soil - Haiyan Wu; Shanguo Chen; Lin Zhu; Yifei Xu; Jing Li; Ning Ling; Jun Yuan; Chao Xue; Qirong Shen (Applied Soil Ecology, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Curcumin induces mitophagy by promoting mitochondrial succinate dehydrogenase activity and sensitizes human papillary thyroid carcinoma BCPAP cells to radioiodine treatment - Li Zhang; Ling Qiu; Shichen Xu; Xian Cheng; Jing Wu; Yunping Wang; Wenjing Gao; Jiandong Bao; Huixin Yu (Toxicology in Vitro, 2023)

Gut microbes consume host energy and reciprocally provide beneficial factors to sustain a symbiotic relationship with the host - Ying Wu; Liang Peng; Pengya Feng; Rong Han; Aman Khan; Sourabh Kulshreshtha; Zhenmin Ling; Pu Liu; Xiangkai Li (Science of The Total Environment, 2023)

High temperature exacerbates ozone-induced airway inflammation: Implication of airway microbiota and metabolites - Fei Xu; Qiong Wu; Yishu Yang; Ling Zhang; Zhen Yan; Huijun Li; Juan Li; Zhen An; Hui Wu; Jie Song; Weidong Wu (Science of The Total Environment, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Hydraulic circulation technology remediates the contaminated groundwater with petroleum hydrocarbon: Evidence from laboratory and field tests - Zhan Chen; Yu-Lin Wu; Tao Li; Yi-Xiang Wang; Ling-Kang Xuan; Shi-Feng Lu (Journal of Cleaner Production, 2023)

LuxS-deficiency reduces persistence of Cronobacter to low-moisture but contributes to virulence after rehydration - Na Ling; Zongyang Li; Yuhang Wang; Qingping Wu; Yingwang Ye; Jumei Zhang (Food Research International, 2023)

Effect of melting combined with ice recrystallization on porous starch preparation: Pore-forming properties, granular morphology, functionality, and multi-scale structures - Chen Zhang; Shi-Yi Wang; Chu-Yun Wu; Jing-Jing Li; Ling-Zhi Zhang; Zhi-Juan Wang; Qiao-Quan Liu; Jian-Ya Qian (Food Research International, 2023)

Thiol-ene click derivatization reaction coupled with ratiometric surface-enhanced Raman scattering for reproducible and accurate determination of acrylamide - Siqi Wei; Ling Li; Lichen Gou; Li Wu; Xiandeng Hou (Food Chemistry, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Tuning defect chemistry of vertical graphene arrays toward highly stable and dendrite-free sodium metal anodes - Haiyu Wang; Ping Wang; Ling Wu; Hui Duan; Yu Chen; Tong Li; Kequan Chen; Mingliang He; Zhipeng Wang (Chemical Engineering Journal, 2023)

Insights into hydrangea-like NiCo2S4 activating peroxymonosulfate for efficient degradation of atrazine - Ziling Zhu; Jiabao Yan; Mingxi Wang; Hui Zhu; Xuanke Li; Ling Wu (Chemical Engineering Journal, 2023)

An Improved Soft Subspace Clustering Algorithm Based on Particle Swarm Optimization for MR Image Segmentation - Lei Ling; Lijun Huang; Jie Wang; Li Zhang; Yue Wu; Yizhang Jiang; Kaijian Xia (Interdisciplinary Sciences: Computational Life Sciences, 2023)

A Sedentary Lifestyle Changes the Composition and Predicted Functions of the Gut Bacterial and Fungal Microbiota of Subjects from the Same Company - Longwei Xu; Wenkun Li; Lu Ling; Ziran Zhang; Zilu Cui; Jiang Ge; Yun Wang; Qianlong Meng; Yadan Wang; Kuiliang Liu; Jun Zhou; Fanxin Zeng; et al. (Current Microbiology, 2023)
A sedentary lifestyle affects the diversity and composition of the gut microbiota, but previous studies have mainly focused on bacteria instead of fungi. Here, we compared both the fecal bacterial and fungal microbiota compositions and functions in sedentary persons and controls. Subjects from the China Railway Corporation, including 99 inspectors and 88 officials, were enrolled in our study. Fecal microbiota communities were analyzed using 16S rRNA gene sequencing for bacteria and ITS sequencing for fungi. We found that the diversity of the gut microbiota of the sedentary group was significantly lower than that of the control group ( P < 0.05). The sedentary group had a higher abundance of Firmicutes, a lower abundance of Actinobacteria and Proteobacteria and a higher abundance of Ascomycota, and a lower abundance of Basidiomycota. Furthermore, functional prediction analysis of the fungal microbiota revealed more L-tryptophan degradation to 2-amino-3-carboxymuconate semialdehyde, more phospholipid remodeling (phosphatidylethanolamine, yeast), and more L-tyrosine degradation I, as well as less pentose phosphate pathway (non-oxidative branch), less adenosine nucleotide biosynthesis and less L-valine biosynthesis in the sedentary group ( P < 0.05). Thus, a sedentary lifestyle changes the composition and function of the gut microbiota. It may change the pentose phosphate pathway (non-oxidative branch), nucleic acid and amino acid biosynthesis and phospholipid metabolism in fungi.

Dynamic and static changes of amplitude of low-frequency fluctuations in anti‑N‑methyl‑D‑aspartate receptor encephalitis - Dongpeng Wu; Yuanyuan Guo; Chenglong Li; Xiaonan Pang; Si Xu; Juanjuan Zhang; Ling Wei; Qianqian Li; Jing Du; Yanghua Tian; Kai Wang (Brain Imaging and Behavior, 2023)

Essential and non-essential elements in tuna and billfish around the world: Distribution patterns and influencing factors - Jingqian Xie; Qiang Wu; Ling Tao; Feng Wu; Shuyi Tu; Duofu Chen; Tian Lin; Tiejun Li (Marine Pollution Bulletin, 2023)

Landscape genomics analysis provides insights into future climate change-driven risk in rhesus macaque - Ruifeng Wu; Jiwei Qi; Wenbo Li; Ling Wang; Ying Shen; Jiawen Liu; Yang Teng; Christian Roos; Ming Li (Science of The Total Environment, 2023)

Occurrence and ecological risks of flonicamid and its metabolites in multiple substrates from intensive rice–vegetable rotations in tropical China - Huadong Tan; Licheng Wang; Ling Mo; Chunyuan Wu; Qiao Xing; Xiaoying Zhang; Xiao Deng; Yi Li; Qinfen Li (Science of The Total Environment, 2023)

Effects of biochar and zero valent iron on the bioavailability and potential toxicity of heavy metals in contaminated soil at the field scale - Qian Li; Juan Yin; Lingling Wu; Shaolin Li; Ling Chen (Science of The Total Environment, 2023)

Pijx confers broad-spectrum seedling and panicle blast resistance by promoting the degradation of ATP β subunit and OsRbohC-mediated ROS burst in rice - Ning Xiao; Yunyu Wu; Xiaoxiang Zhang; Zeyun Hao; Zichun Chen; Zefeng Yang; Yue Cai; Ruyi Wang; Ling Yu; Zhiping Wang; Yue Lu; Wei Shi; et al. (Molecular Plant, 2023)

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

Cost-benefits analysis of ultra-low emissions standard on air quality and health impact in thermal power plants in China - Ruxing Wan; Ling Tang; Jing Guo; Wenhui Zhai; Ling Li; Yang Xie; Xin Bo; Jun Wu (Journal of Environmental Management, 2023)

A machine learning prediction model for quantitative analyzing the influence of non-radiative voltage loss on non-fullerene organic solar cells - Di Huang; Kuo Wang; Zhennan Li; Haixin Zhou; Xiaojie Zhao; Xinyu Peng; Jipeng Wu; Jiaojiao Liang; Juan Meng; Ling Zhao (Chemical Engineering Journal, 2023)

Primary open-angle glaucoma risk prediction with ABCA1 and LOC102723944 variants and their genotype–phenotype correlations in southern Chinese population - Zhenggen Wu; Chukai Huang; Yuqian Zheng; Xiang-Ling Yuan; Shaowan Chen; Yanxuan Xu; Li Jia Chen; Chi Pui Pang; Mingzhi Zhang; Tsz Kin Ng (Molecular Genetics and Genomics, 2023)

Fenton pretreatment to mitigate membrane distillation fouling during treatment of landfill leachate membrane concentrate: Performance and mechanism - Zhichao Zhao; Yong Zhang; Ling Yu; Deyin Hou; Xiaohui Wu; Kuiling Li; Jun Wang (Water Research, 2023)

Mitigating greenhouse gas emissions by replacing inorganic fertilizer with organic fertilizer in wheat–maize rotation systems in China - Yajin Hu; Donghao Li; Yong Wu; Siyuan Liu; Ling Li; Weiqiang Chen; Shufang Wu; Qingxiang Meng; Hao Feng; Kadambot H.M. Siddique (Journal of Environmental Management, 2023)

Tracking spatio-temporal distribution and transmission of antibiotic resistance in aquatic environments by using ESBL-producing Escherichia coli as an indicator - Qi Li; Huiyun Zou; Di Wang; Ling Zhao; Min Meng; Zhongyi Wang; Tianle Wu; Shuang Wang; Xuewen Li (Journal of Environmental Management, 2023)

Impact of bentonite on greenhouse gas emissions during pig manure composting and its subsequent application - Jia-Ping Wu; Meng-Ling Li; Yan Wang; Shan Lin; Rong-Gui Hu; Rong-Biao Xiang (Journal of Environmental Management, 2023)

Hydrothermal carbonization of sewage sludge coupled with Fenton oxidation pretreatment: Moderate oxidation to enhance hydrochar yield and properties - Chenyu Wang; Biao Gui; Chaoyue Wu; Chao He; Lucheng Li; Xiaolong Ling; Xiaojun Zuo (Journal of Environmental Chemical Engineering, 2023)

Transcriptomic analysis reveals novel desiccation tolerance mechanism of Cronobacter based on type VI secretion system inhibition - Yang Wang; Na Ling; Rui Jiao; Xiyan Zhang; Yuwei Ren; Hui Li; Wenhua Zhao; Qingping Wu; Yingwang Ye (Food Research International, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Effect of pH treatment on physical stability and antioxidant activity of buckwheat protein/soybean polysaccharide nanocomplex embedded pterostilbene - Dongze Li; Ling Zhu; Qiming Wu; Yiling Chen; Gangcheng Wu; Hui Zhang (Food Bioscience, 2023)

Long non-coding RNAs mediate the association between short-term PM2.5 exposure and circulating biomarkers of systemic inflammation - Qinqin Diao; Xiaodi Qin; Ningdong Hu; Yihui Ling; Qiuhan Hua; Meizhen Li; Xun Li; Hanyu Zhou; Yufei Liu; Huixian Zeng; Jihuan Liang; Yongxian Wu; et al. (Environmental Pollution, 2023)

Experimental and theoretical insights into metal-free catalytic reduction of nitrophenols over porous nitrogen-doped reduced graphene oxide - Meng-Yao Qi; Yuexing Zhang; Qianni Li; Ling Wu; Binghua Zhou; Zhipeng Wang; Zheng-Hong Huang; Ming-Xi Wang (Chemical Engineering Journal, 2023)

Highly selective transfer hydrogenation of biomass-derived furfural to furfuryl alcohol over a zirconium-melamine coordination catalyst without Brønsted acid sites - Lei Hu; Keru Chen; Jiacheng Li; Ling Zhang; Yetao Jiang; Xiaoyu Wang; Zhen Wu; Aiyong He; Jiaxing Xu; Jinliang Song (Chemical Engineering Journal, 2023)

Space charge region induced self-evolution dehydrogenation of polymorphic magnesium-based hydrides - Qinke Tang; Jiangchuan Liu; Mengran Li; Rui Shi; Yunfeng Zhu; Yao Zhang; Jiguang Zhang; Yana Liu; Yijin Wu; Ling Li; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

Stable cerium isotope analysis of geological materials by MC-ICP-MS - Fang Liu; Mingxing Ling; Zhaofeng Zhang; Wenning Lu; Jianbing Xu; Xin Li; Di Yang; Jiaojiao Wu; Hong Yang (Chemical Geology, 2023)

Different Burial-Cooling History of Triassic Strata between the Western Weibei Uplift and the Northwestern Weihe Basin in Northwest China - Qiang Yu; Zhanli Ren; Rongxi Li; Chung Ling; Tao Ni; Wanshan Lei; Baojiang Wang; Xiaoli Wu; Xiaoli Qin; Xianghe Lei (Journal of Earth Science, 2023)

Low-computation GNSS post-correlation signal parameter estimation method based on the complex signal phase in a high-dynamic environment - Chao Wu; Jian Xie; Ling Wang; Mingkun Su; Junna Shang; Haiquan Wang; Minhong Sun; Yafeng Li; Liyan Luo (GPS Solutions, 2023)

Exploration of glycosyltransferases mutation status in cervical cancer reveals PARP14 as a potential prognostic marker - Hui Wang; Shen Luo; Xin Wu; Yuanyuan Ruan; Ling Qiu; Hao Feng; Shurong Zhu; Yanan You; Ming Li; Wenting Yang; Yanding Zhao; Xiang Tao; et al. (Glycoconjugate Journal, 2023)
This study investigates the potential role of Glycosyltransferases (GTs) in the glycosylation process and their association with malignant tumors. Specifically, the study focuses on PARP14, a member of GTs, and its potential as a target for tumors in the diagnosis and treatment of cervical cancer. To gather data, the study used somatic mutation data, gene expression data and clinical information from TCGA-CESE dataset as well as tissue samples from cervical cancer patients. Further verification was conducted through RT-qPCR and immunohistochemistry staining on cervical cancer tissues to confirm the expression of PARP14. The study utilized Kaplan-Meier for survival analysis of cervical cancer patient and found significant mutational abnormalities in GTs. The high frequency mutated gene was identified as PARP14. RT-qPCR revealed significantly higher mRNA expression of PARP14 compared to precancerous tissue. Using IHC combined with Kaplan-Meier,patients in the PARP14 high expression group had a better prognosis than the low expression group. The study identified PARP14 as a frequently mutated gene in cervical cancer and proposed its potential role in diagnosis and treatment.

Research on carbon emission quota allocation scheme under “Double Carbon” target: a case study of industrial sector in Henan Province - Peizhe Shi; Ling Li; Yuping Wu; Yun Zhang; Zhaohan Lu (Environmental Science and Pollution Research, 2023)

Coal slime as a good modifier for the restoration of copper tailings with improved soil properties and microbial function - Zhou Zhou; Ling Xia; Xizhuo Wang; Chenyu Wu; Jiazhi Liu; Jianbo Li; Zijing Lu; Shaoxian Song; Jiang Zhu; María Luciana Montes; Mostafa Benzaazoua (Environmental Science and Pollution Research, 2023)

Antiviral effect of prodigiosin isolated from fish intestinal bacteria against Micropterus salmoides rhabdovirus - Kaige Song; Jing Li; Fei Yang; Zhibin Wu; Weichao Chen; Pengfei Li; Fei Ling; Gaoxue Wang (Aquaculture, 2023)

Study on influencing factors of hole-filling performance of rice precision direct seed-metering device with hole ejection - Hanqing Li; Bingxin Yan; Zhijun Meng; Lin Ling; Yanxin Yin; Anqi Zhang; Chunjiang Zhao; Guangwei Wu (Biosystems Engineering, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

The interaction mechanisms, biological activities and digestive properties between Tartary buckwheat protein and phenolic extract under pH-driven methods - Dongze Li; Ling Zhu; Gangcheng Wu; Hui Zhang (Food Chemistry, 2023)

Corrigendum to “Effects of gelatin-based antifreeze peptides on cell viability and oxidant stress of Streptococcus thermophilus during cold stage” [Food Chem. Toxicol. 136 (2020) 111056] - Xu Chen; Ling Li; Fujia Yang; Jinhong Wu; Shaoyun Wang (Food and Chemical Toxicology, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Heterostructure α-Fe2O3(0 0 1)/g-C3N4(0 0 2) adsorbent to remove As2O3 in simulated coal flue gas: Experimental and DFT study - Biao Wu; Jiang Wu; Jiachen Li; Zhanwei Qiao; Peng Shen; Qilin Zhang; Bowen Zhang; Yang Ling (Chemical Engineering Journal, 2023)

Assessment of climate simulation over the Tibetan Plateau based on high-resolution multi-RCM within CORDEX-EA-II - Ping Li; Xiaorui Niu; Yanjin Mao; Rongchang Wu; Xiaolu Ling (Atmospheric Research, 2023)

Genetic analysis of stripe rust resistance in the common wheat line Kfa/2*Kachu under a Chinese rust environment - Yuruo Yin; Chan Yuan; Yichen Zhang; Shunda Li; Bin Bai; Ling Wu; Yong Ren; Ravi P. Singh; Caixia Lan (Theoretical and Applied Genetics, 2023)

Immunopathogenesis and immunomodulatory therapy for myocarditis - Wu He; Ling Zhou; Ke Xu; Huihui Li; James Jiqi Wang; Chen Chen; DaoWen Wang (Science China Life Sciences, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Persistent transmission of carbapenem-resistant, hypervirulent Klebsiella pneumoniae between a hospital and urban aquatic environments - Huiyun Zou; Ziyu Zhou; Björn Berglund; Beiwen Zheng; Min Meng; Ling Zhao; Hui Zhang; Zhongyi Wang; Tianle Wu; Qi Li; Xuewen Li (Water Research, 2023)

Winners take all: competition for carbon resource determines grain fate - Si Shen; Si Ma; Limin Wu; Shun-Li Zhou; Yong-Ling Ruan (Trends in Plant Science, 2023)

MaizeNetome: A multi-omics network database for functional genomics in maize - Jia-Wu Feng; Linqian Han; Hao Liu; Wen-Zhao Xie; Hanmingzi Liu; Lin Li; Ling-Ling Chen (Molecular Plant, 2023)

Public perception of microplastics on a popular Chinese social media platform - Yinglin Wu; Donghui Mo; Jing Liu; Zitong Li; Xiaoli Chen; Ling Xie (Journal of Cleaner Production, 2023)

Homogenization of microplastics in alpine rivers: Analysis of microplastic abundance and characteristics in rivers of Qilian Mountain, China - Qian Liu; Xiong Xiong; Kehuan Wang; Hui Wang; Yiqin Ling; Quanliang Li; Fengyi Xu; Chenxi Wu (Journal of Environmental Management, 2023)

Different interactions between Tartary buckwheat protein and Tartary buckwheat phenols during extraction: Alterations in the conformation and antioxidant activity of protein - Dongze Li; Ling Zhu; Qiming Wu; Yiling Chen; Gangcheng Wu; Hui Zhang (Food Chemistry, 2023)

Effects of enzyme deactivation conditions on the structure, bound phenol content and antioxidant property of phenol modified Tartary buckwheat protein hydrolysate - Dongze Li; Ling Zhu; Qiming Wu; Yiling Chen; Gangcheng Wu; Hui Zhang (Food Bioscience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Critical Metals Ga, Ge and In in the Global Pb-Zn Deposits: Current Understanding, Challenges and Perspectives - Yi Zheng; Peng-Peng Yu; Zhan-Ke Li; Suo-Fei Xiong; Ling-Li Zhou; Jia-Xi Zhou; Chang-Ming Wang; Yu-Miao Meng; Yu Zhang; Ye-Jian Wang; Jing Xu; Yue Wu; et al. (Journal of Earth Science, 2023)

Straw return counteracts the negative effects of warming on microbial community and soil multifunctionality - Gong Wu; Jun Ling; De-Qiang Zhao; Zi-Xi Liu; Yi-Ping Xu; Yakov Kuzyakov; Karina Marsden; Yuan Wen; Shun-Li Zhou (Agriculture, Ecosystems & Environment, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

High-entropy alloy nanoparticles/biochar as an efficient catalyst for high-performance treatment of organic pollutants - Ling-Zhen Miao; Yu-Xin Guo; Zi-Yi Liu; Yang Li; Jie Zhu; Lei Wu (Chemical Engineering Journal, 2023)

Integrating polygenic and clinical risks to improve stroke risk stratification in prospective Chinese cohorts - Qingmei Cui; Fangchao Liu; Jianxin Li; Xiaoge Niu; Zhongying Liu; Chong Shen; Dongsheng Hu; Keyong Huang; Shufeng Chen; Jie Cao; Xiaoqing Liu; Ling Yu; et al. (Science China Life Sciences, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Chlorella sorokiniana FK-montmorillonite interaction enhanced remediation of heavy metals in tailings - Jiaqi Tan; Xizhuo Wang; Min Zhang; Delong Meng; Yaxi Hu; Yinta Li; Shaoxian Song; Li Wu; Rosa María Torres Sánchez; María Eugenia Farías; Ling Xia (Science of The Total Environment, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Assessment of the impact of wetland changes on carbon storage in coastal urban agglomerations from 1990 to 2035 in support of SDG15.1 - Ze Zhang; Weiguo Jiang; Kaifeng Peng; Zhifeng Wu; Ziyan Ling; Zhuo Li (Science of The Total Environment, 2023)

Changes in biochemical metabolites in manila clam after a temporary culture with high-quality microalgal feed mixed with the dinoflagellate species Karlodinium veneficum and K. zhouanum - Yuanbo Pan; Ran Meng; Yanrong Li; Ling Yang; Limin Mei; Yanhua Wu; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2023)

The fiber-bound polyphenols from highland barley with inhibitory effects against carbonyls during in vitro digestion of cookies and French fries - Jinxin Li; Hao Zhang; Xijuan Yang; Ling Zhu; Gangcheng Wu; Hui Zhang (Food Bioscience, 2023)

A notable reversible thermochromic (3,3-difluoropyrrolidinium)2[CuCl4] with ferroelectricity and ferroelasticity - Shulin Jiao; Zheng Tang; Dong Li; Cuiping Xu; Zhu Yang; Peng Chen; Xiaofan Sun; Hong-Ling Cai; Xiaoshan Wu (Chemical Engineering Journal, 2023)

A single fluorescent probe reveals changes in endoplasmic reticulum–mitochondria contact in hepatocytes during ferroptosis - Ling-Li Wang; Ya-Ru Zhang; Ming-Hua Zheng; Xuan Wang; Xue Wu; Jing-Yi Jin (Chemical Engineering Journal, 2023)

Combined Chemical Fertilizers with Molasses Increase Soil Stable Organic Phosphorus Mineralization in Sugarcane Seedling Stage - Qihua Wu; Wenling Zhou; Yinglin Lu; Shuang Li; Dachun Shen; Qiuping Ling; Diwen Chen; Junhua Ao (Sugar Tech, 2023)

Impact of different nitrogen additions on microbes and exopolysaccharides excretion in cyanobacterial biocrusts - Long Qian; Jingshang Xiao; Zulin Zhang; Lie Yang; Ling Xia; María E. Farías; Rosa María Torres; Li Wu (Plant and Soil, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

In-situ constructed indirect Z-type heterojunction by plasma Bi and BiO2-X–Bi2O2CO3 co-modified with BiOCl@Bi–MOF for enhanced photocatalytic efficiency toward antibiotics - Yu Zhang; Fengyan Ma; Meihua Ling; Hong Zheng; Yutong Wu; Li Li (Chemical Engineering Journal, 2023)

A microscopic diffusion-induced discrete element model for swellable particles - Jiawei Hu; Wen Li; Ling Zhang; Chuan-Yu Wu (Chemical Engineering Journal, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Genome-Wide Identification of the BvCBL Genes in Sugar Beet (Beta vulgaris L.) and Their Expression Under Salt and Drought Conditions - Ling-Ling Xie; Guo-Qiang Wu; Min Wei; Sha-Jia Li (Journal of Plant Growth Regulation, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Uncommonly efficient degradation performance of photocatalytic ozonation towards tetracycline over synthesizing 3-D g-C3N4 nanosheet based on Si-O-Co framework - Yu Ling; Biqing Li; Hai Liu; Heping Hu; Yixiao Wu; Biaojun Zhang; Tianyu Zhao; Shaobin Huang; Lishan Niu (Process Safety and Environmental Protection, 2023)

AaWIN1, an AP2/ERF protein, positively regulates glandular secretory trichome initiation in Artemisia annua - Chen Wang; Tiantian Chen; Yongpeng Li; Hang Liu; Wei Qin; Zhangkuanyu Wu; Bowen Peng; Xiuyun Wang; Xin Yan; Xueqing Fu; Ling Li; Kexuan Tang (Plant Science, 2023)

Two new dicyclic C-geranylflavanones isolated from Paulownia fortunei and their cytotoxicity - Wei-guo Liu; Cheng-mei Xiao; Jun Li; Su-ying Wu; Wen-chao Zhang; Ling-tao Kong; Wen-Zhao Tang; Xian-hui Jia (Phytochemistry Letters, 2023)

Saltwater intrusion regulates the distribution and partitioning of heavy metals in water in a dynamic estuary, South China - Ling Zhang; Yunchao Wu; Zhixin Ni; Jinlong Li; Yuzheng Ren; Jizhen Lin; Xiaoping Huang (Marine Environmental Research, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

A Tiered Ecological Risk Assessment of Caffeine by Using Species Sensitivity Distribution Method in the Nansi Lake Basin - Lei Zheng; Juan Zhang; Yinan Wu; Linlin Li; Junhong Ling; Sai Wang; Wenlong Yang; Yezhu Yin; Liang Dong; Yizhang Zhang (Bulletin of Environmental Contamination and Toxicology, 2023)

Self-assembled DNA nanoparticles enable cascade circuits for mRNA detection and imaging in living cells - Zhe Dong; Debo Gao; Yuancheng Li; Kang An; Jing Ni; Ling Meng; Han Wu (Analytica Chimica Acta, 2023)

Arbuscular mycorrhizal fungi decrease soil ammonium availability and nitrous oxide emissions under nitrogen input - Xiang Zheng; Qi Liu; Xinli Chen; Minmin Cao; Fan Wu; Weiyang Li; Ling Zhang; Shenglong Liu; Jiang Jiang (Agricultural and Forest Meteorology, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Isotopic compositions (δD, δ18O) and end-member mixing for the control interface in a complex tidal region - Rongrong Xie; Ling Zhen; Xianzhong Wu; Jiabing Li (Science of The Total Environment, 2023)

Perfluorobutanesulfonate exposure induces metabolic disturbances in different regions of mouse gut - Ling Chen; Mengyuan Zhu; Yafeng Liu; Zhongchao Yang; Huan Li; Hongxin Mu; Su Liu; Bing Wu (Science of The Total Environment, 2023)

R-loopAtlas: An integrated R-loop resource from 254 plant species sustained by a deep-learning-based tool - Kuan Li; Zhenzhen Wu; Jincong Zhou; Wei Xu; Ling Li; Chao Liu; Wei Li; Chengjun Zhang; Qianwen Sun (Molecular Plant, 2023)

First evidence of neonicotinoid insecticides in human bile and associated hepatotoxicity risk - Yuanchen Chen; Wenfei Yu; Li Zhang; Linping Cao; Jun Ling; Kaizhen Liao; Guofeng Shen; Wei Du; Kangjie Chen; Meirong Zhao; Jian Wu; Hangbiao Jin (Journal of Hazardous Materials, 2023)

Developing a hydroxyl-functionalized magnetic porous organic polymer combined with HPLC-MS/MS for determining 31 amide herbicides in fruit wine - Can Zhang; Shuo Li; Jing Wu; Tengteng Ping; Ling Ma; Ke Wang; Kaoqi Lian (Food Chemistry, 2023)

Sustained-release antibacterial gelatin films: Effects of diatomite/carvacrol complex on their structure, physicochemical and antibacterial properties - Hejun Wu; Ling Ma; Sen Li; Jie Wang; Ting Li; Lu Peng; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang; Yuntao Liu (Food Packaging and Shelf Life, 2023)

Response characteristics of antibiotic resistance genes and bacterial communities during agricultural waste composting: Focusing on biogas residue combined with biochar amendments - Yuewei He; Xiaowei Yin; Fanghong Li; Bo Wu; Ling Zhu; Dabing Ge; Nanyi Wang; Anwei Chen; Lihua Zhang; Binghua Yan; Hongli Huang; Lin Luo; et al. (Bioresource Technology, 2023)

Identification of structural variations related to drought tolerance in wheat (Triticum aestivum L.) - Jiajia Zhao; Xiaohua Li; Ling Qiao; Xingwei Zheng; Bangbang Wu; Meijun Guo; Meichen Feng; Zengjun Qi; Wude Yang; Jun Zheng (Theoretical and Applied Genetics, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Fumigation activity of essential oils of Cinnamomum loureirii toward red imported fire ant workers - Huanling Xing; Yingqi Hu; Liupeng Yang; Jianhao Lin; Haiyi Bai; Yanqun Li; Rezwan Tanvir; Ling Li; Mei Bai; Zhixiang Zhang; Hanhong Xu; Hong Wu (Journal of Pest Science, 2023)

Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Nanocomplexation is a promising strategy to enhance the solubility and anti-Ichthyophthirius multifiliis activity of magnolol - Shenye Qu; Jietao Liu; Zhibin Wu; Jing Li; Pengfei Li; Gaoxue Wang; Fei Ling (Aquaculture, 2023)

A comprehensive study of the source, occurrence, and spatio-seasonal dynamics of 12 target antibiotics and their potential risks in a cold semi-arid catchment - Hanyu Ju; Ling Liu; Xuemei Liu; Yao Wu; Lei Li; Karina Yew-Hoong Gin; Guangxin Zhang; Jingjie Zhang (Water Research, 2023)

The shared NDM-positive strains in the hospital and connecting aquatic environments - Huiyun Zou; Jingyi Han; Ling Zhao; Di Wang; Yanyu Guan; Tianle Wu; Xinjiao Hou; Hui Han; Xuewen Li (Science of The Total Environment, 2023)

Functional analysis of 3 genes in xenobiotic detoxification pathway of Bursaphelenchus xylophilus against matrine - Yang Li; Bi Wu; Xin Hao; Jian Diao; Jingxin Cao; Ruina Tan; Wei Ma; Ling Ma (Pesticide Biochemistry and Physiology, 2023)

Digestion, absorption, and transport properties of soy-fermented douchi hypoglycemic peptides VY and SFLLR under simulated gastrointestinal digestion and Caco-2 cell monolayers - Songfeng Yu; Wenjun Wang; Tingting Bu; Runan Zhao; Ruihao Niu; Ling Liu; Jiaheng Li; Jianping Wu; Donghong Liu (Food Research International, 2023)

High-performance methanol electrolysis towards energy-saving hydrogen production: Using Cu2O-Cu decorated Ni2P nanoarray as bifunctional monolithic catalyst - Ling Li; Longcheng Zhang; Lichen Gou; Siqi Wei; Xiandeng Hou; Li Wu (Chemical Engineering Journal, 2023)

Insights into the mechanism of elemental mercury removal via ferric chloride modified carbon Aerogel: An experimental and theoretical research - Jiachen Li; Tong Li; Fengting Li; Tao Jia; Jiang Wu; Sikai Wu; Yang Ling; Ping He; Xu Mao; Jie Dong (Chemical Engineering Journal, 2023)

Emerging materials and engineering strategies for performance advance of radiative sky cooling technology - Junwei Liu; Yunfei Zhang; Shuai Li; Cristian Valenzuela; Shukuan Shi; Chongxu Jiang; Shiqiang Wu; Long Ye; Ling Wang; Zhihua Zhou (Chemical Engineering Journal, 2023)

Effects of composition, starch structural orders, and kernel structure on starch in vitro digestion of highland barley - Xiaoyu Chen; Ling Zhu; Hui Zhang; Gangcheng Wu; Lilin Cheng; Jinxin Li (Carbohydrate Polymers, 2023)

Collateral-Core Ratio as a Novel Predictor of Clinical Outcomes in Acute Ischemic Stroke - Jinhao Lyu; Sa Xiao; Zhihua Meng; Xiaoyan Wu; Wen Chen; Guohua Wang; Qingliang Niu; Xin Li; Yitong Bian; Dan Han; Weiting Guo; Shuai Yang; et al. (Translational Stroke Research, 2023)

Codon usage bias and genetic diversity in chloroplast genomes of Elaeagnus species (Myrtiflorae: Elaeagnaceae) - Changle Li; Ling Zhou; Jiangbo Nie; Songping Wu; Wei Li; Yonghong Liu; Yulin Liu (Physiology and Molecular Biology of Plants, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Optimizing the Schoenemann Reaction for Colorimetric Assays of VX and GD - Shaoxiong Wu; Lianyuan Wang; Haiyan Zhu; Ling Yuan; Jian Li; Liang Ge; Hongpeng Zhang; Ting Miao; Zhenxing Cheng (Bulletin of Environmental Contamination and Toxicology, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Geochemical accumulation and source tracing of heavy metals in arable soils from a black shale catchment, southwestern China - Wei Wei; Sixiang Ling; Xiyong Wu; Xiaoning Li (Science of The Total Environment, 2023)

Review of research on migration, distribution, biological effects, and analytical methods of microfibers in the environment - Yifei Li; Qingbin Lu; Yi Xing; Kai Liu; Wei Ling; Jian Yang; Qizhen Yang; Tianqi Wu; Jiafu Zhang; Zengxin Pei; Ziyuan Gao; Xiaoyan Li; et al. (Science of The Total Environment, 2023)

Detection of multidrug resistant pathogenic bacteria and novel complex class 1 integrons in campus atmospheric particulate matters - Jiamin Hu; Ziyun Li; Ling Li; Yuqing Sun; Lulu Shi; Weiwei Li; Jian Zhang; Yan Wu; Hai Xu; Mingyu Wang (Science of The Total Environment, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

Mapping between density of states and energy band gap for bismuth-based semiconductors via machine learning prediction - Yang Ling; Zhengxin Chen; Site Li; Yunxiao Guan; Min Shi; Jun Zhu; Zhihai Cheng; Jiang Wu; Chaojie Yin; Mengjie Bai (Fuel, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Coupled carbon structure and iron species for multiple periodate-based oxidation reaction - Ling Xiang; Eydhah Almatrafi; Hailan Yang; Haoyang Ye; Fanzhi Qin; Huan Yi; Yukui Fu; Xiuqin Huo; Wu Xia; Hong Li; Ming Yan; Chengyun Zhou; et al. (Chemical Engineering Journal, 2023)

Corrigendum to “CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage” [Carbohydrate Polymers 193 (2018) 268–280] - Jing-Bo Hu; Shu-Juan Li; Xu-Qi Kang; Jing Qi; Jia-Hui Wu; Xiao-Juan Wang; Xiao-Ling Xu; Xiao-Ying Ying; Sai-Ping Jiang; Jian You; Yong-Zhong Du (Carbohydrate Polymers, 2023)

Genome-Wide Identification of CIPK Genes in Sugar Beet (Beta vulgaris) and Their Expression Under NaCl Stress - Guo-Qiang Wu; Ling-Ling Xie; Jin-Long Wang; Bei-Chen Wang; Zhi-Qiang Li (Journal of Plant Growth Regulation, 2023)

Retraction Note: Knockdown of long non‑coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA‑15a and repressing ROCK1 expression - Xia Li; Sheng‑Wu Wang; Xi‑Ling LI; Feng‑Yuan Yu; Hai‑Ming Cong (Inflammation Research, 2023)

Association between pyrethroid exposure and risk of depressive symptoms in the general US adults - Hui-ru Li; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Science and Pollution Research, 2023)

Airborne transmission as an integral environmental dimension of antimicrobial resistance through the “One Health” lens - Ling Jin; Jiawen Xie; Tangtian He; Dong Wu; Xiangdong Li (Critical Reviews in Environmental Science and Technology, 2022)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Paleomagnetic constraints on Paleogene-Neogene rotation and paleo-stress in the northern Qaidam Basin - Ling Sun; Junliang Ji; Bingshuai Li; Xingbo Li; Wujun Wu; Kexin Zhang (Science China Earth Sciences, 2022)

A bibliometric and content analysis of research trends on GIS-based landslide susceptibility from 2001 to 2020 - Junpeng Huang; Xiyong Wu; Sixiang Ling; Xiaoning Li; Yuxin Wu; Lei Peng; Zhiyi He (Environmental Science and Pollution Research, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

The critical role of the orbitofrontal cortex for regret in an economic decision-making task - Tingting Zhang; Qiuzhu Zhang; Jiaqi Wu; Min Wang; Wenjuan Li; Jing Yan; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Structure and Function, 2022)

Flowering characteristics and mating system of Fritillaria cirrhosa (Liliaceae), an endangered plant in China - Yanzhu Ma; Zhijia Cui; Chun Ya Cheng; Ran Li; Haixu Wu; Ling Jin; Yi Ma; Zhenheng Wang (Brazilian Journal of Botany, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Fine mapping of a stripe rust resistance gene YrZM175 in bread wheat - Jingchun Wu; Dengan Xu; Luping Fu; Ling Wu; Weihao Hao; Jihu Li; Yan Dong; Fengju Wang; Yuying Wu; Zhonghu He; Hongqi Si; Chuanxi Ma; et al. (Theoretical and Applied Genetics, 2022)

Genetic dissection of lutein content in common wheat via association and linkage mapping - Panfeng Guan; Xiaohua Li; Lei Zhuang; Bangbang Wu; Jinyong Huang; Jiajia Zhao; Ling Qiao; Jun Zheng; Chenyang Hao; Xingwei Zheng (Theoretical and Applied Genetics, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Two new clerodane diterpenoids and a new pyran-2-one derivative with anti-neuroinflammatory activities from Croton crassifolius - Zhi-Peng Ling; Qing Tang; Can-Jie Li; Jin-Lin Tan; Hai-Yue Zhao; Yi-Kun Hao; Zhao-Chun Zhan; Zhong-Nan Wu; Yu-Bo Zhang; Qing Zheng; Guo-Cai Wang (Journal of Natural Medicines, 2022)

UBR5 promotes migration and invasion of glioma cells by regulating the ECRG4/NF-κB pathway - Qiang Wu; Ling Liu; Yan Feng; Liqun Wang; Xin Liu; Yanan Li (Journal of Biosciences, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

Biomechanical Effects of Bone Atrophy, Implant Design, and Vertical or Tilted of Posterior Implant on All-on-Four Concept Implantation: Finite Element Analysis - Heng-Li Huang; Ting-Wei Lin; Hui-Ling Tsai; Yu-Ling Wu; Aaron Yu-Jen Wu (Journal of Medical and Biological Engineering, 2022)

Taxifolin blocks monosodium urate crystal-induced gouty inflammation by regulating phagocytosis and autophagy - Mei-Hua Piao; Hui Wang; Yin-Jing Jiang; Yan-Ling Wu; Ji-Xing Nan; Li-Hua Lian (Inflammopharmacology, 2022)

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Halomonas faecis sp. nov., a halophilic bacterium isolated from human faeces - Zhu-Xiang Liu; Jin-Hua Chen; Ling-Ling Yang; Yu-Zhou Feng; Li-Ying Deng; Jian-Wu He; Shu-Kun Tang; Yi-Guang Chen (Extremophiles, 2022)

The fate of flavonoids after oral administration: a comprehensive overview of its bioavailability - Abid Naeem; Yang Ming; Hu Pengyi; Kang Yong Jie; Liu Yali; Zhang Haiyan; Xiao Shuai; Li Wenjing; Wu Ling; Zhang Ming Xia; Liu Shan Shan; Zheng Qin (Critical Reviews in Food Science and Nutrition, 2022)

Ambient temperature exposure and risk of outpatient visits for dermatologic diseases in Xinxiang, China: a time-series analysis - Ling Chao; Mengxue Lu; Wenshan Gao; Zhen An; Juan Li; Yue Liu; Weidong Wu; Jie Song (International Journal of Biometeorology, 2022)

Influence of freeze–thaw cycling on the dynamic compressive failure of rocks subjected to hydrostatic pressure - Ying Xu; Bingqi Chen; Bangbiao Wu; Zhe Chen; Ling Yang; Pingfeng Li (Bulletin of Engineering Geology and the Environment, 2022)

Application of enzymatic hydrolysate of Ulva clathrata as biostimulant improved physiological and metabolic adaptation to salt-alkaline stress in wheat - Feiyu Li; Zhihua Wu; Siqi Zuo; Li Fan; Zhengpeng Wei; Ling Ma; Wenke Sun; Chunying Du; Ruizhi Liu; Peng Wang (Journal of Applied Phycology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Functional differentiation and complementation of alkaline phosphatases and choreography of DOP scavenging in a marine diatom - Kaidian Zhang; Jiashun Li; Jierui Wang; Xin Lin; Ling Li; Yanchun You; Xiaomei Wu; Zhi Zhou; Senjie Lin (Molecular Ecology, 2022)
Facing phosphate deficiency, phytoplankton use alkaline phosphatase (AP) to scavenge dissolved organophosphate (DOP). AP is a multitype (e.g., PhoA, PhoD) family of hydrolases and is known as a promiscuous enzyme with broad DOP substrate compatibility. Yet, whether the multiple types differentiate on substrates and collaborate to provide physiological flexibility remain elusive. Here we identify PhoA and PhoDs and document the functional differentiation between PhoA and a PhoD (PhoD_45757) in Phaeodactylum tricornutum . CRISPR/Cas9‐based mutations and physiological analyses reveal that (1) PhoA is a secreted enzyme and contributes the majority of total AP activity whereas PhoD_45757 is intracellular and contributes a minor fraction of the total AP activity, (2) AP gene expression compensates for each other after one is disrupted, (3) the DOP→PhoA→phosphate_uptake and the DOP_uptake→PhoD→phosphate pathways function interchangeably for some DOP substrates. These findings shed light on the underpinning of AP’s multiformity and have important implications in phytoplankton phosphorus‐nutrient niche differentiation, physiological plasticity, and competitive strategy.

Porewater-Derived Blue Carbon Outwelling and Greenhouse Gas Emissions in a Subtropical Multi-Species Saltmarsh - Peiyuan Zhu; Xiaogang Chen; Yan Zhang; Qianyu Zhang; Xuan Wu; Huawen Zhao; Liang Qi; Xuexin Shao; Ling Li (Frontiers in Marine Science, 2022)
Saltmarshes can sequester atmospheric CO 2 in sediments, but limited studies have quantified porewater-derived carbon exports and identified related carbon sources. Here, we estimated porewater exchange, carbon outwelling, and greenhouse gas emissions in a subtropical multi-species saltmarsh. The radon-based porewater exchange rate was estimated to be 5.60 ± 2.78 cm d -1 . As the most dominant (~90%) carbon species, dissolved inorganic carbon (DIC) fluxes through porewater exchange and outwelling were 447 ± 227 and 1200 ± 61 mmol m -2 d -1 , respectively, which were 1.2 and 3.2 times that of carbon burial. As most DIC can remain in the ocean for a long time, porewater-derived DIC outwelling represents another important carbon sink, in addition to carbon burial. CO 2 and CH 4 emissions from creek water were 54.6 ± 0.5 and 0.19 ± 0.01 mmol m -2 d -1 , respectively, which could offset 16% of carbon burial. The δ 13 C and C/N ratios suggest that saltmarsh organic carbon mainly originates from the C3 plant Scirpus mariqueter rather than the C4 plant Spartina alterniflora . Overall, we suggest that porewater-derived DIC outwelling is an important long-term carbon sink in multi-species saltmarshes, providing a scientific basis for the protection and restoration of saltmarshes in the context of global climate change.

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Isolation and characterization of 112 SNP markers in Yellowfin seabream (Acanthopagrus latus) using RAD sequencing - Ke-Cheng Zhu; Ya-Ling Li; Wei-Bin Wu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Liang Guo; Dian-Chang Zhang (Conservation Genetics Resources, 2022)

Maternal embryonic leucine zipper kinase serves as a potential prognostic marker and leads to sorafenib chemoresistance modified by miR-142-5p in hepatocellular carcinoma - Hualei Li; Ling Gai; Zhimei Wu; Feng Li (Molecular Biology Reports, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Screening and identification of HLA-A2-restricted neoepitopes for immunotherapy of non-microsatellite instability-high colorectal cancer - Ranran Shi; Yubing Li; Ling Ran; Yu Dong; Xiuman Zhou; Jingwen Tang; Lu Han; Mingshuang Wang; Liwei Pang; Yuanming Qi; Yahong Wu; Yanfeng Gao (Science China Life Sciences, 2022)

Optimal coupling combinations between dripper discharge and irrigation interval of maize for seed production under plastic film-mulched drip irrigation in an arid region - Shimeng Ma; Ling Tong; Shaozhong Kang; Sufen Wang; Xuanyi Wu; Xiaona Cheng; Qiangqiang Li (Irrigation Science, 2022)

Association between maternal exposure to PM10 and risk of anorectal atresia/stenosis in offspring: a population-based case-control study in Liaoning Province, China - Tie-Ning Zhang; Qi-Jun Wu; Yan-Hong Huang; Jing Li; Zong-Jiao Chen; Li-Li Li; Yan-Ling Chen; Shu Liu; Cheng-Zhi Jiang; Yu-Hong Zhao (Environmental Science and Pollution Research, 2022)

Effects of ambient temperature on outpatient visits for dermatitis in Xinxiang, China: a time-series analysis - Ling Chao; Yajun Sun; Zhen An; Juan Li; Weidong Wu; Yue Liu; Jie Song (Environmental Science and Pollution Research, 2022)

Effectiveness of Disinfectants Suitable for Inactivating SARS-CoV-2 at Cold-Chain Temperature - Xiaosong Wu; Yin Chen; Ling Wang; Xiling Guo; Lunbiao Cui; Yiming Shen; Fang Li; Hong Sun; Liubo Zhang; Jin Shen; Yan Xu (Food and Environmental Virology, 2022)

Fruit and vegetable consumption, cardiovascular disease, and all-cause mortality in China - Jun Wang; Fangchao Liu; Jianxin Li; Keyong Huang; Xueli Yang; Jichun Chen; Xiaoqing Liu; Jie Cao; Shufeng Chen; Chong Shen; Ling Yu; Fanghong Lu; et al. (Science China Life Sciences, 2022)

Blood transcriptome analysis revealed the immune changes and immunological adaptation of wildness training giant pandas - Miao Yang; Yan Huang; Honglin Wu; Caiwu Li; Shanshan Ling; Jie Sun; Haibo Shen; Bisong Yue; Xiuyue Zhang (Molecular Genetics and Genomics, 2022)

Correction to: Optimal coupling combinations between dripper discharge and irrigation interval of maize for seed production under plastic film-mulched drip irrigation in an arid region - Shimeng Ma; Ling Tong; Shaozhong Kang; Sufen Wang; Xuanyi Wu; Xiaona Cheng; Qiangqiang Li (Irrigation Science, 2022)

Technical methodologies for the assessment of the impacts of reclamation projects on marine ecology - Yurong Ouyang; Lin Wu; Juanjuan Dai; Yaojian Wu; Ling Cai; Qingsheng Li; Jianwei Wu; Shang Jiang (Environmental Science and Pollution Research, 2022)

Hyper-SUMOylation of SMN induced by SENP2 deficiency decreases its stability and leads to spinal muscular atrophy-like pathology - Yuhong Zhang; Xu Chen; Qiqi Wang; Congcong Du; Wenbin Lu; Hong Yuan; Zhenzhen Zhang; Danqing Li; Xing Ling; Xiang Ren; Yang Zhao; Qi Su; et al. (Journal of Molecular Medicine, 2021)

Ice-binding proteins: a remarkable ice crystal regulator for frozen foods - Xu Chen; Xiaodan Shi; Xixi Cai; Fujia Yang; Ling Li; Jinhong Wu; Shaoyun Wang (Critical Reviews in Food Science and Nutrition, 2021)

Pivotal role of the gut microbiota in congenital insensitivity to pain with anhidrosis - Mi Zhang; Yishun Hong; Wenyao Wu; Ningbo Li; Baowen Liu; Jiaoli Sun; Xueqin Cao; Ting Ye; Ling Zhou; Cunming Liu; Chun Yang; Xianwei Zhang (Psychopharmacology, 2021)

The influence of slopes on interrill erosion processes using loessial soil - Bing Wu; Ludi Li; Ling Xu; Xindong Wei; Xinlu Li (Journal of Soils and Sediments, 2021)

Effects of climate variables on the transmission of COVID-19: a systematic review of 62 ecological studies - Hu-Li Zheng; Ze-Li Guo; Mei-ling Wang; Chuan Yang; Shu-Yi An; Wei Wu (Environmental Science and Pollution Research, 2021)

Four genetic loci affecting swine lung lesions identified by whole-genome sequencing-based association studies - Xinkai Tong; Tao Huang; Mingpeng Zhang; Jiaqi Chen; Zhou Zhang; Jingquan Li; Huipeng Du; Ziqi Ling; Zhongzi Wu; Bin Yang; Shijun Xiao; Huashui Ai (Science China Life Sciences, 2021)

Co-editing PINK1 and DJ-1 Genes Via Adeno-Associated Virus-Delivered CRISPR/Cas9 System in Adult Monkey Brain Elicits Classical Parkinsonian Phenotype - Hao Li; Shihao Wu; Xia Ma; Xiao Li; Tianlin Cheng; Zhifang Chen; Jing Wu; Longbao Lv; Ling Li; Liqi Xu; Wenchao Wang; Yingzhou Hu; et al. (Neuroscience Bulletin, 2021)
Whether direct manipulation of Parkinson’s disease (PD) risk genes in the adult monkey brain can elicit a Parkinsonian phenotype remains an unsolved issue. Here, we used an adeno-associated virus serotype 9 (AAV9)-delivered CRISPR/Cas9 system to directly co-edit PINK1 and DJ-1 genes in the substantia nigras (SNs) of two monkey groups: an old group and a middle-aged group. After the operation, the old group exhibited all the classic PD symptoms, including bradykinesia, tremor, and postural instability, accompanied by key pathological hallmarks of PD, such as severe nigral dopaminergic neuron loss (>64%) and evident α-synuclein pathology in the gene-edited SN. In contrast, the phenotype of their middle-aged counterparts, which also showed clear PD symptoms and pathological hallmarks, were less severe. In addition to the higher final total PD scores and more severe pathological changes, the old group were also more susceptible to gene editing by showing a faster process of PD progression. These results suggested that both genetic and aging factors played important roles in the development of PD in the monkeys. Taken together, this system can effectively develop a large number of genetically-edited PD monkeys in a short time (6–10 months), and thus provides a practical transgenic monkey model for future PD studies.

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Heavy metal(loid) and Pb isotope compositions of black shale weathering profiles on the northern Yangtze Platform: insights into geochemical behavior, contamination assessment, and source apportionment - Wei Wei; Xiaoning Li; Sixiang Ling; Xiyong Wu; Xin Liao (Environmental Science and Pollution Research, 2021)

Effects of nFe3O4 capping on phosphorus release from sediments in a eutrophic lake - Xiang Chen; Ling Liu; Wenming Yan; Minjuan Li; Xiaolei Xing; Qi Li; Liangzhen Zhu; Tingfeng Wu; Xiangyu He (Environmental Science and Pollution Research, 2021)

Short-term effect of NO2 on outpatient visits for dermatologic diseases in Xinxiang, China: a time-series study - Ling Chao; Mengxue Lu; Zhen An; Juan Li; Yuchun Li; Qian Zhao; Yinbiao Wang; Yue Liu; Weidong Wu; Jie Song (Environmental Geochemistry and Health, 2021)

An improved convolution perfectly matched layer for elastic second-order wave equation - Ling-Yun Yang; Guo-Chen Wu; Qing-Yang Li; Zhan-Yuan Liang (Applied Geophysics, 2021)

Characteristics of airborne microbial community in Hefei, eastern China, under a good quality in mid-spring - Li Wang; Changnian Wu; Qi Ling; Jiangying Yu; Weihua Li; Weiyue Wang; Jinkang Zhao (Aerobiologia, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Fluid Mobility Evaluation of Tight Sandstones in Chang 7 Member of Yanchang Formation, Ordos Basin - Songtao Wu; Shixiang Li; Xuanjun Yuan; Zhi Yang; Aifen Li; Jingwei Cui; Songqi Pan; Zhiguo Mao; Ling Su; You Zhou (Journal of Earth Science, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

Lignin degradation by water buffalo - Qingbiao Xu; Huimin Zhong; Jiayan Zhou; Yong Wu; Zhenhua Ma; Liguo Yang; Zhen Wang; Chuqi Ling; Xiang Li (Tropical Animal Health and Production, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Resolvin D1 Attenuates Innate Immune Reactions in Experimental Subarachnoid Hemorrhage Rat Model - Guang-Jie Liu; Tao Tao; Xiang-Sheng Zhang; Yue Lu; Ling-Yun Wu; Yong-Yue Gao; Han Wang; Hai-Bin Dai; Yan Zhou; Zong Zhuang; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2021)

Ameliorative effect of graphene nanosheets against arsenic-induced toxicity in mice by oral exposure - Huan Li; Bing Wu; Jingli Zhang; Yue Yu; Ling Chen; Su Liu (Environmental Science and Pollution Research, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

Resveratrol-induced apoptosis is associated with regulating the miR-492/CD147 pathway in malignant melanoma cells - Shuang Zhao; Ling Tang; Wangqing Chen; Juan Su; Fangfang Li; Xiang Chen; Lisha Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Dysregulation of circulating follicular helper T cells in type 2 diabetic patients with diabetic retinopathy - Honghua Yu; Baoyi Liu; Guanrong Wu; Zijing Du; Qiaowei Wu; Xiaomin Zeng; Yu Xiao; Ying Fang; Ling Yuan; Suihong Ma; Tao Li (Immunologic Research, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Maternal exposure to ambient SO2 and risk of polydactyly and syndactyly: a population-based case-control study in Liaoning Province, China - Yu-Ting Jiang; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; Qi-Jun Wu (Environmental Science and Pollution Research, 2021)

Remediation of contaminated soil and groundwater using chemical reduction and solidification/stabilization method: a case study - Shi-Feng Lu; Yu-Lin Wu; Zhan Chen; Tao Li; Chao Shen; Lin-Kang Xuan; Ling Xu (Environmental Science and Pollution Research, 2021)

An Innovative Emergy Quantification Method for Eco-economic Compensation for Agricultural Water Rights Trading - Cuimei Lv; Huiqin Li; Minhua Ling; Xi Guo; Zening Wu; Changkuan Gu; Yang Li (Water Resources Management, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Marine natural products as antifouling molecules – a mini-review (2014–2020) - Ling-Li Liu; Chuan-Hai Wu; Pei-Yuan Qian (Biofouling, 2021)

Identification of Amino Acid Dysregulation as a Potential Biomarker for Autism Spectrum Disorder in China - Mingyang Zou; Dexin Li; Luxi Wang; Ling Li; Shu Xie; Yu Liu; Wei Xia; Caihong Sun; Lijie Wu (Neurotoxicity Research, 2020)

Clinical characteristics and plasma antibody titer of patients with COVID-19 in Zhejiang, China - Wei-ling Xiang; Jing-jing Cheng; Lian-peng Wu; Bing-yu Chen; Wen-xin Li; Dan-ying Qiu; Wei Zhang; Fei-hang Ge; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Population demographic history and adaptability of the vulnerable Lolokou Sucker Frog - Minghao Gong; Aaron B. A. Shafer; Xiaolong Hu; Yaohua Huang; Ling Zhang; Huixin Li; Ye Wu; Wanyu Wen; Gang Liu (Genetica, 2020)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

Particle Swarm Optimization (PSO) for improving the accuracy of ChemCam LIBS sub-model quantitative method - Li Zhang; Zhongchen Wu; Zongcheng Ling (Earth Science Informatics, 2020)

Spinal CCL2 Promotes Pain Sensitization by Rapid Enhancement of NMDA-Induced Currents Through the ERK-GluN2B Pathway in Mouse Lamina II Neurons - Hui Zhang; Sui-Bin Ma; Yong-Jing Gao; Jun-Ling Xing; Hang Xian; Zhen-Zhen Li; Shu-Ning Shen; Sheng-Xi Wu; Ceng Luo; Rou-Gang Xie (Neuroscience Bulletin, 2020)
Previous studies have shown that CCL2 (C–C motif chemokine ligand 2) induces chronic pain, but the exact mechanisms are still unknown. Here, we established models to explore the potential mechanisms. Behavioral experiments revealed that an antagonist of extracellular signal-regulated kinase (ERK) inhibited not only CCL2-induced inflammatory pain, but also pain responses induced by complete Freund’s adjuvant. We posed the question of the intracellular signaling cascade involved. Subsequent experiments showed that CCL2 up-regulated the expression of phosphorylated ERK (pERK) and N-methyl D-aspartate receptor [NMDAR] subtype 2B (GluN2B); meanwhile, antagonists of CCR2 and ERK effectively reversed these phenomena. Whole-cell patch-clamp recordings revealed that CCL2 enhanced the NMDAR-induced currents via activating the pERK pathway, which was blocked by antagonists of GluN2B and ERK. In summary, we demonstrate that CCL2 directly interacts with CCR2 to enhance NMDAR-induced currents, eventually leading to inflammatory pain mainly through the CCL2–CCR2–pERK–GluN2B pathway.

Structural Variability and Functional Prediction in the Epiphytic Bacteria Assemblies of Myriophyllum spicatum - Ling Xian; Tao Wan; Yu Cao; Junyao Sun; Ting Wu; Andrew Apudo Apudo; Wei Li; Fan Liu (Current Microbiology, 2020)

Associations of egg consumption with incident cardiovascular disease and all-cause mortality - Xue Xia; Fangchao Liu; Xueli Yang; Jianxin Li; Jichun Chen; Xiaoqing Liu; Jie Cao; Chong Shen; Ling Yu; Yingxin Zhao; Xianping Wu; Liancheng Zhao; et al. (Science China Life Sciences, 2020)

RETRACTED ARTICLE: Knockdown of long non-coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA-15a and repressing ROCK1 expression - Xia Li; Sheng-Wu Wang; Xi-Ling LI; Feng-Yuan Yu; Hai-Ming Cong (Inflammation Research, 2020)

Pentamidine sensitizes FDA-approved non-antibiotics for the inhibition of multidrug-resistant Gram-negative pathogens - Chenxuan Wu; Ling Xia; Wei Huang; Yangfan Xu; Yuanxin Gu; Chang Liu; Luting Ji; Wenyao Li; Yandong Wu; Kai Zhou; Xinxin Feng (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Autonomous Martian rock image classification based on transfer deep learning methods - Jialun Li; Li Zhang; Zhongchen Wu; Zongcheng Ling; Xueqiang Cao; Kaichen Guo; Fabao Yan (Earth Science Informatics, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Physiological and transcriptomic analyses of brassinosteroid function in moso bamboo (Phyllostachys edulis) seedlings - Zhe Zhang; Xuelian Yang; Ling Cheng; Zejun Guo; Huiyuan Wang; Weihuang Wu; Kihye Shin; Jinyao Zhu; Xiaoli Zheng; Jianghu Bian; Yangchen Li; Lianfeng Gu; et al. (Planta, 2020)

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Molecular evolution of GII.P17-GII.17 norovirus associated with sporadic acute gastroenteritis cases during 2013–2018 in Zhoushan Islands, China - Can Chen; Bing Wu; Hui Zhang; Ke-Feng Li; Rong Liu; Hong-Ling Wang; Jian-Bo Yan (Virus Genes, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Tracing mantle sources in the northern Lau back-arc basin by independent component analysis of basalt isotopic compositions - Xichang Wu; Liyan Tian; Xuan-Ce Wang; Fengyou Chu; Quanshu Yan; Fengyue Sun; Xiaohu Li; Wei Wang; Luyao Yu; Zhenggang Li; Ling Chen (International Geology Review, 2020)

Leukocyte immunoglobulin-like receptor B4 protects against cardiac hypertrophy via SHP-2-dependent inhibition of the NF-κB pathway - Heng Zhou; Ning Li; Yuan Yuan; Ya-Ge Jin; Qingqing Wu; Ling Yan; Zhou-Yan Bian; Wei Deng; Di-Fei Shen; Hongliang Li; Qi-Zhu Tang (Journal of Molecular Medicine, 2020)

Function of NHX-type transporters in improving rice tolerance to aluminum stress and soil acidity - Weihong Li; Jia Du; Huimin Feng; Qi Wu; Guohua Xu; Sergey Shabala; Ling Yu (Planta, 2020)

Plastid-expressed Bacillus thuringiensis (Bt) cry3Bb confers high mortality to a leaf eating beetle in poplar - Shijing Xu; Yiqiu Zhang; Shengchun Li; Ling Chang; Yuyong Wu; Jiang Zhang (Plant Cell Reports, 2020)

Anti-inflammatory bibenzyls from the stems of Dendrobium huoshanense via bioassay guided isolation - Qiang-Ming Li; Hui Jiang; Xue-Qiang Zha; De-Ling Wu; Li-Hua Pan; Jun Duan; Jian Liu; Jian-Ping Luo (Natural Product Research, 2020)

Utilization of pre-existing competent and barren quartz veins as hosts to later orogenic gold ores at Huangjindong gold deposit, Jiangnan Orogen, southern China - Liang Zhang; David I. Groves; Li-Qiang Yang; Si-Chen Sun; Roberto F. Weinberg; Jiu-Yi Wang; Sheng-Gang Wu; Lei Gao; Lan-Ling Yuan; Rong-Hua Li (Mineralium Deposita, 2020)

Disruption of tight junction structure contributes to secretory dysfunction in IgG4-related sialadenitis - Sai-Nan Min; Li-Ling Wu; Yan-Yan Zhang; Wen-Xuan Zhu; Xin Cong; Guang-Yan Yu (Journal of Molecular Histology, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Cytological, genetic, and proteomic analysis of a sesame (Sesamum indicum L.) mutant Siyl-1 with yellow–green leaf color - Tong-Mei Gao; Shuang-Ling Wei; Jing Chen; Yin Wu; Feng Li; Li-Bin Wei; Chun Li; Yan-Juan Zeng; Yuan Tian; Dong-Yong Wang; Hai-Yang Zhang (Genes & Genomics, 2020)
Background Both photosynthetic pigments and chloroplasts in plant leaf cells play an important role in deciding on the photosynthetic capacity and efficiency in plants. Systematical investigating the regulatory mechanism of chloroplast development and chlorophyll (Chl) content variation is necessary for clarifying the photosynthesis mechanism for crops. Objective This study aims to explore the critical regulatory mechanism of leaf color mutation in a yellow–green leaf sesame mutant Siyl - 1 . Methods We performed the genetic analysis of the yellow-green leaf color mutation using the F 2 population of the mutant Siyl - 1 . We compared the morphological structure of the chloroplasts, chlorophyll content of the three genotypes of the mutant F 2 progeny. We performed the two-dimensional gel electrophoresis (2-DE) and compared the protein expression variation between the mutant progeny and the wild type. Results Genetic analysis indicated that there were 3 phenotypes of the F 2 population of the mutant Siyl - 1 , i.e., YY type with light-yellow leaf color (lethal); Yy type with yellow-green leaf color, and yy type with normal green leaf color. The yellow-green mutation was controlled by an incompletely dominant nuclear gene, Siyl - 1 . Compared with the wild genotype, the chloroplast number and the morphological structure in YY and Yy mutant lines varied evidently. The chlorophyll content also significantly decreased ( P < 0.05 ). The 2-DE comparison showed that there were 98 differentially expressed proteins (DEPs) among YY, Yy, and yy lines. All the 98 DEPs were classified into 5 functional groups. Of which 82.7% DEPs proteins belonged to the photosynthesis and energy metabolism group. Conclusion The results revealed the genetic character of yellow-green leaf color mutant Siyl - 1 . 98 DEPs were found in YY and Yy mutant compared with the wild genotype. The regulation pathway related with the yellow leaf trait mutation in sesame was analyzed for the first time. The findings supplied the basic theoretical and gene basis for leaf color and chloroplast development mechanism in sesame.

Contribution of skeletal muscular glycine to rapid antidepressant effects of ketamine in an inflammation-induced mouse model of depression - Niannian Huang; Yue Wang; Gaofeng Zhan; Fan Yu; Shan Li; Dongyu Hua; Riyue Jiang; Shiyong Li; Yeshun Wu; Ling Yang; Bin Zhu; Fei Hua; et al. (Psychopharmacology, 2019)

All-trans-retinoic acid generation is an antidotal clearance pathway for all-trans-retinal in the retina - Qing-qing Xia; Ling-min Zhang; Ying-ying Zhou; Ya-lin Wu; Jie Li (Journal of Zhejiang University-SCIENCE B, 2019)

Geochemical behaviors of antimony in mining-affected water environment (Southwest China) - Ling Li; Han Tu; Shui Zhang; Linna Wu; Min Wu; Yang Tang; Pan Wu (Environmental Geochemistry and Health, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Expression of Ihh signaling pathway in condylar cartilage after bite-raising in adult rats - Hui-qing Long; Peng-fei Tian; Yu-xin Guan; Ling-xia Liu; Xiu-ping Wu; Bing Li (Journal of Molecular Histology, 2019)

Diversification of mitogenomes in three sympatric Altica flea beetles (Insecta, Chrysomelidae) - Rui‐E Nie; Jing Wei; Shou‐Ke Zhang; Alfried P. Vogler; Ling Wu; Alexander S. Konstantinov; Wen‐Zhu Li; Xing‐Ke Yang; Huai‐Jun Xue (Zoologica Scripta, 2019)
The Asian flea beetles Altica cirsicola , Altica fragariae and Altica viridicyanea are broadly sympatric and morphologically highly similar but feed on distantly related host plants. They have been suggested as a model for ecological speciation studies. However, their phylogeny and species limits remain uncertain. In this study, we added mitochondrial genomes from multiple individuals of each species to the growing database. Phylogenetic analyses based on 15 genes showed clear interspecific divergences of A. fragariae from the other species, but A. cirsicola and A. viridicyanea were not distinguishable by distance‐based or tree‐based methods of species delimitation due to non‐monophyly of mitogenomes relative to the morphologically defined entities, possibly affected by interspecific introgression. This was confirmed by wider sampling of mitochondrial COX1 (58 individuals) and the second internal transcribed spacer of nuclear ribosomal RNA cluster (ITS2; 68 individuals), which showed that ITS2, but not COX1, coincided with the morphological species limits. The full mitochondrial genomes are not able to shed further light on the species status, even with the most sensitive approach based on diagnostic characters, yet the whole mitogenome is useful to get improved estimates of intra‐ and interspecific variation, not affected by the stochastic error seen in individual genes.

Correction to: Accumulation of glycine betaine in transplastomic potato plants expressing choline oxidase confers improved drought tolerance - Lili You; Qiping Song; Yuyong Wu; Shengchun Li; Chunmei Jiang; Ling Chang; Xinghong Yang; Jiang Zhang (Planta, 2019)

Accumulation of glycine betaine in transplastomic potato plants expressing choline oxidase confers improved drought tolerance - Lili You; Qiping Song; Yuyong Wu; Shengchun Li; Chunmei Jiang; Ling Chang; Xinghong Yang; Jiang Zhang (Planta, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Early heading 7 interacts with DTH8, and regulates flowering time in rice - Maohong Cai; Saihua Chen; Mingming Wu; Tianhui Zheng; Liang Zhou; Chaonan Li; Huan Zhang; Jiachang Wang; Xinyang Xu; Juntao Chai; Yulong Ren; Xiuping Guo; et al. (Plant Cell Reports, 2019)

Elaboration in type, primary structure, and bioactivity of polysaccharides derived from mollusks - Ling Chong Wang; Liu Qing Di; Jun Song Li; Li Hong Hu; Jian Ming Cheng; Hao Wu (Critical Reviews in Food Science and Nutrition, 2019)

Expression Profiling of Notch Signalling Pathway and Gamma-Secretase Activity in the Brain of Ts1Cje Mouse Model of Down Syndrome - Hadri Hadi Yusof; Han-Chung Lee; Eryse Amira Seth; Xiangzhong Wu; Chelsee A. Hewitt; Hamish S Scott; Pike-See Cheah; Yue-Ming Li; De-Ming Chau; King-Hwa Ling (Journal of Molecular Neuroscience, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Novel mutation of type-1 insulin-like growth factor receptor (IGF-1R) gene in a severe short stature pedigree identified by targeted next-generation sequencing - Yu Yang; Hui Huang; Ka Chen; Li Yang; Li-ling Xie; Ting Xiong; Xian Wu (Journal of Genetics, 2019)

The reduction effects of riparian reforestation on runoff and nutrient export based on AnnAGNPS model in a small typical watershed, China - Kaixia Jiang; Zhaofu Li; Chuan Luo; Min Wu; Ling Chao; Quansuo Zhou; Haiyan Zhao (Environmental Science and Pollution Research, 2019)

Complete genome analysis of a novel phage GW1 lysing Cronobacter - Haiyan Zeng; Wenjing He; Chengsi Li; Jumei Zhang; Na Ling; Yu Ding; Liang Xue; Moutong Chen; Haoming Wu; Qingping Wu (Archives of Virology, 2019)

Novel Inhalable Ciprofloxacin Dry Powders for Bronchiectasis Therapy: Mannitol–Silk Fibroin Binary Microparticles with High-Payload and Improved Aerosolized Properties - Chunxia Liu; Ling Lin; Zhengwei Huang; Qiaoli Wu; Junhuang Jiang; Li Lv; Xiaoxia Yu; Guilan Quan; Guocheng Li; Chuanbin Wu (AAPS PharmSciTech, 2019)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Complete nucleotide sequence of a novel monopartite begomovirus infecting Ageratum conyzoides in China - Pengbai Li; Chenchen Jing; Rui Wang; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Archives of Virology, 2018)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Screening wheat genotypes for better performance on reduced phosphorus supply by comparing glasshouse experiments with field trials - De-Yong Zhao; Shu-Song Zheng; Muhammad Kashif Naeem; Jian-Qing Niu; Ning Wang; Zhong-Jian Li; Hui-Lan Wu; Hong-Qing Ling (Plant and Soil, 2018)

Promoters of Arabidopsis Casein kinase I-like 2 and 7 confer specific high-temperature response in anther - Yaoyao Li; Ling Min; Lin Zhang; Qin Hu; Yuanlong Wu; Jie Li; Sai Xie; Yizan Ma; Xianlong Zhang; Longfu Zhu (Plant Molecular Biology, 2018)

Responses of Patients with Disorders of Consciousness to Habit Stimulation: A Quantitative EEG Study - Jingqi Li; Jiamin Shen; Shiqin Liu; Maelig Chauvel; Wenwei Yang; Jian Mei; Ling Lei; Li Wu; Jian Gao; Yong Yang (Neuroscience Bulletin, 2018)

Negative regulation of MAVS-mediated innate immune response by ASC - Yue Han; Xiang He; Congwen Wei; Ting Song; Ling Zou; Zihui Li; Jiazhou Ye; Lunan Qi; Lequn Li; Hui Zhong; Feixiang Wu (Molecular and Cellular Biochemistry, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

First report of tobacco curly shoot virus infecting Malvastrum coromandelianum in China - Pengbai Li; Chenchen Jing; Ke Li; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Journal of Plant Pathology, 2018)

Comparison Study of Bone Defect Healing Effect of Raw and Processed Pyritum in Rats - Xingyu Zhu; Qianqian Gao; Genhua Zhao; Heng Wang; Ling Liu; Zhipeng Chen; Yijun Chen; Li Wu; Zisheng Xu; Weidong Li (Biological Trace Element Research, 2018)

Ideal cardiovascular health and incidence of atherosclerotic cardiovascular disease among Chinese adults: the China-PAR project - Chao Han; Fangchao Liu; Xueli Yang; Jichun Chen; Jianxin Li; Jie Cao; Ying Li; Chong Shen; Ling Yu; Zhendong Liu; Xianping Wu; Liancheng Zhao; et al. (Science China Life Sciences, 2018)

ELMOD3, a novel causative gene, associated with human autosomal dominant nonsyndromic and progressive hearing loss - Wu Li; Jie Sun; Jie Ling; Jiada Li; Chufeng He; Yalan Liu; Hongsheng Chen; Meichao Men; Zhijie Niu; Yuyuan Deng; Meng Li; Taoxi Li; et al. (Human Genetics, 2018)

Establishment of two basal-like breast cancer cell lines with extremely low tumorigenicity from Taiwanese premenopausal women - Wen-Ling Kuo; Shir-Hwa Ueng; Chun-Hsing Wu; Li-Yu Lee; Yun-Shien Lee; Ming-Chin Yu; Shin-Cheh Chen; Chi-Chang Yu; Chi-Neu Tsai (Human Cell, 2018)

OPEN GLUME1: a key enzyme reducing the precursor of JA, participates in carbohydrate transport of lodicules during anthesis in rice - Xiaohui Li; Yihua Wang; Erchao Duan; Qi Qi; Kunneng Zhou; Qiuyun Lin; Di Wang; Yunlong Wang; Wuhua Long; Zhigang Zhao; Zhijun Cheng; Cailin Lei; et al. (Plant Cell Reports, 2018)

Automated breast tumor detection and segmentation with a novel computational framework of whole ultrasound images - Lei Liu; Kai Li; Wenjian Qin; Tiexiang Wen; Ling Li; Jia Wu; Jia Gu (Medical & Biological Engineering & Computing, 2018)

Ca2+-CaMKKβ pathway is required for adiponectin-induced secretion in rat submandibular gland - Chong Ding; Zhi-Hao Du; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2018)

Persistence of SIV in the brain of SIV-infected Chinese rhesus macaques with or without antiretroviral therapy - Stefanie Perez; Ann-Marie Johnson; Shi-hua Xiang; Jian Li; Brian T. Foley; Lara Doyle-Meyers; Antonito Panganiban; Amitinder Kaur; Ronald S. Veazey; Yuntao Wu; Binhua Ling (Journal of NeuroVirology, 2018)

A new ent -kaurane diterpene derivative from the stems of Eurya chinensis R.Br - Jia-Ling Song; Yao Yuan; Ling-Hui Nie; Bai-Lin Li; Xu-Bing Qin; Yan Li; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2018)

Effects of Dietary Administration of Shewanella xiamenensis A-1, Aeromonas veronii A-7, and Bacillus subtilis, Single or Combined, on the Grass Carp (Ctenopharyngodon idella) Intestinal Microbiota - Kai Hao; Zhuo-Qi Wu; Dong-Liang Li; Xiao-Bo Yu; Gao-Xue Wang; Fei Ling (Probiotics and Antimicrobial Proteins, 2017)

Yangonindimers A-C, three new kavalactone dimers from Piper methysticum (kava) - Jia-Ling Song; Bai-Lin Li; Yao Yuan; Ling-Hui Nie; Jia Niu; David Chiu; Zhi-Fang Xu; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2017)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

AnkG hemizygous mice present cognitive impairment and elevated anxiety/depressive-like traits associated with decreased expression of GABA receptors and postsynaptic density protein - Cui Liu; Ling Zhang; Jie Wu; Xiaolong Sui; Yanfeng Xu; Lan Huang; Yunlin Han; Hua Zhu; Yanhong Li; Xiuping Sun; Chuan Qin (Experimental Brain Research, 2017)

Genotypic Differences in Growth and Antioxidant Enzyme Activities Under Cadmium Stress in Sugarcane - Qiaoying Zeng; Qiuping Ling; Fei Hu; Jiayun Wu; Zhanduan Yang; Yongwen Qi; Qiwei Li (Bulletin of Environmental Contamination and Toxicology, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Synergistic roles of the E2 glycoprotein and 3′ untranslated region in the increased genomic stability of chimeric classical swine fever virus with attenuated phenotypes - Rui Wu; Ling Li; Lei Lei; Cheng Zhao; Xiaofang Shen; Haizhong Zhao; Zishu Pan (Archives of Virology, 2017)

Remote estimation of cyanobacterial blooms using the risky grade index (RGI) and coverage area index (CAI): a case study in the Three Gorges Reservoir, China - Botian Zhou; Mingsheng Shang; Guoyin Wang; Li Feng; Kun Shan; Xiangnan Liu; Ling Wu; Xuerui Zhang (Environmental Science and Pollution Research, 2017)

Climatic and geographic factors affect ecosystem multifunctionality through biodiversity in the Tibetan alpine grasslands - Ying Pan; Jun-xi Wu; Li-ming Luo; Yan-li Tu; Cheng-qun Yu; Xian-zhou Zhang; Yan-jun Miao; Yan Zhao; Jun-ling Yang (Journal of Mountain Science, 2017)

The species of Lentaria (Gomphales, Basidiomycota) from China based on morphological and molecular evidence - Li-Na Liu; Ling Wu; Zuo-Hong Chen; Tolgor Bau; Ping Zhang (Mycological Progress, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

Three new diterpenoids from Croton laui Merr. et Metc - Li Yang; Zhong-Nan Wu; Yu-Bo Zhang; Neng-Hua Chen; Ling Zhuang; Yao-Lan Li; Guo-Cai Wang (Natural Product Research, 2017)

Influenza A virus upregulates PRPF8 gene expression to increase virus production - Chee-Hing Yang; Hui-Chun Li; Yu-Ling Shiu; Tzu-Shan Ku; Chia-Wen Wang; Yi-Shuan Tu; Hung-Ling Chen; Cheng-Hao Wu; Shih-Yen Lo (Archives of Virology, 2017)

Muscarinic acetylcholine receptor-mediated tight junction opening is involved in epiphora in late phase of submandibular gland transplantation - Ning-Yan Yang; Chong Ding; Jing Li; Yan Zhang; Ruo-Lan Xiang; Li-Ling Wu; Guang-Yan Yu; Xin Cong (Journal of Molecular Histology, 2017)

Simulation of exchange flow between open water and floating vegetation using a modified RNG k-ε turbulence model - Zhaowei Liu; Yongcan Chen; Yongyan Wu; Wenyong Wang; Ling Li (Environmental Fluid Mechanics, 2017)

Differentiating Patients with Parkinson’s Disease from Normal Controls Using Gray Matter in the Cerebellum - Ling-Li Zeng; Liang Xie; Hui Shen; Zhiguo Luo; Peng Fang; Yanan Hou; Beisha Tang; Tao Wu; Dewen Hu (The Cerebellum, 2017)

Development of an integrated linkage map of einkorn wheat and its application for QTL mapping and genome sequence anchoring - Kang Yu; Dongcheng Liu; Wenying Wu; Wenlong Yang; Jiazhu Sun; Xin Li; Kehui Zhan; Dangqun Cui; Hongqing Ling; Chunming Liu; Aimin Zhang (Theoretical and Applied Genetics, 2017)

Young Seedling Stripe1 encodes a chloroplast nucleoid-associated protein required for chloroplast development in rice seedlings - Kunneng Zhou; Yulong Ren; Feng Zhou; Ying Wang; Long Zhang; Jia Lyu; Yihua Wang; Shaolu Zhao; Weiwei Ma; Huan Zhang; Liwei Wang; Chunming Wang; et al. (Planta, 2017)

Purified isolation of vacuoles from Sedum alfredii leaf-derived protoplasts - Xiao-yu Gao; Xing-cheng Liao; Ruo-lai Wu; Ting Liu; Hai-xing Wang; Ling-li Lu (Journal of Zhejiang University-SCIENCE B, 2017)

Genome-wide profiling of genetic variation in Agrobacterium-transformed rice plants - Wen-xu Li; San-ling Wu; Yan-hua Liu; Gu-lei Jin; Hai-jun Zhao; Long-jiang Fan; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

The status evaluation of the permafrost environment along the Chaida’er-Muli Railway in southern Qilian Mountains in northern Qinghai Province, China - Wei Cao; Yu Sheng; Ya-ling Chou; Ji-chun Wu; Jing Li; Sheng-ting Wang (Journal of Mountain Science, 2016)

Mineralogy and geochemistry of three weathered Lower Cambrian black shale profiles in Northeast Chongqing, China - Sixiang Ling; Xiyong Wu; Chunwei Sun; Xin Liao; Yong Ren; Xiaoning Li (Geosciences Journal, 2016)

A repressor motif-containing poplar R3 MYB-like transcription factor regulates epidermal cell fate determination and anthocyanin biosynthesis in Arabidopsis - Qingnan Hu; Li Yang; Shanda Liu; Limei Zhou; Xutong Wang; Wei Wang; Ling Cai; Xiuju Wu; Ying Chang; Shucai Wang (Journal of Plant Biology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Comparative efficacy of nonhormonal drugs on menopausal hot flashes - Lujin Li; Ling Xu; Junyi Wu; Lidan Dong; Shuiyu Zhao; Qingshan Zheng (European Journal of Clinical Pharmacology, 2016)

Acute toxicity and histopathological effects of naproxen in zebrafish (Danio rerio) early life stages - Qian Li; Peipei Wang; Ling Chen; Hongwen Gao; Lingling Wu (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Assessment of cytotoxicity and AhR-mediated toxicity of sediments from water level fluctuation zone in the Three Gorges Reservoir, China - Lingling Wu; Li Liu; Tilman Floehr; Thomas-Benjamin Seiler; Ling Chen; Xingzhong Yuan; Henner Hollert (Journal of Soils and Sediments, 2016)

IGF-I stimulates ERβ and aromatase expression via IGF1R/PI3K/AKT-mediated transcriptional activation in endometriosis - Yan Zhou; Cheng Zeng; Xin Li; Pei-Li Wu; Ling Yin; Xiao-Lan Yu; Ying-Fang Zhou; Qing Xue (Journal of Molecular Medicine, 2016)

Investigation of diarrhetic shellfish toxins in Lingshan Bay, Yellow Sea, China, using solid-phase adsorption toxin tracking (SPATT) - Feng-Ling Li; Zhao-Xin Li; Meng-Meng Guo; Hai-Yan Wu; Ting-Ting Zhang; Cai-Hu Song (Food Additives & Contaminants: Part A, 2016)

STAT3 signal that mediates the neural plasticity is involved in willed-movement training in focal ischemic rats - Qing-ping Tang; Qin Shen; Li-xiang Wu; Xiang-ling Feng; Hui Liu; Bei Wu; Xiao-song Huang; Gai-qing Wang; Zhong-hao Li; Zun-jing Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Development of a novel single-step reverse genetics system for the generation of classical swine fever virus - Ling Li; Huining Pang; Rui Wu; Yanwen Zhang; Yiluo Tan; Zishu Pan (Archives of Virology, 2016)

Morphology and molecular analysis of Paratylenchus guangzhouensis n. sp. (Nematoda: Paratylenchinae) from the soil associated with Bambusa multiplex in China - Ke Wang; Yu Li; Hui Xie; Chun-Ling Xu; Wen-Jia Wu (European Journal of Plant Pathology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Morphological and molecular characterisation of Hemicaloosia guangzhouensis n. sp. (Nematoda: Caloosiidae) from China - Ke Wang; Yu Li; Hui Xie; Wen-Jia Wu; Chun-Ling Xu (European Journal of Plant Pathology, 2016)

Embryotoxicity and genotoxicity evaluation of sediments from Yangtze River estuary using zebrafish (Danio rerio) embryos - Qian Li; Ling Chen; Li Liu; Lingling Wu (Environmental Science and Pollution Research, 2016)

Chemical composition and antioxidant activities of the essential oil from Nandina domestica fruits - Shu-Feng Bi; Guang-Qi Zhu; Jie Wu; Zhong-Kang Li; Yong-Zhan Lv; Ling Fang (Natural Product Research, 2016)

Glutathione homeostasis and Cd tolerance in the Arabidopsis sultr1;1-sultr1;2 double mutant with limiting sulfate supply - Xiang Liu; Fei-Hua Wu; Jing-Xi Li; Juan Chen; Guang-Hui Wang; Wen-Hua Wang; Wen-Jun Hu; Li-Jie Gao; Zong-Ling Wang; Jun-Hui Chen; Martin Simon; Hai-Lei Zheng (Plant Cell Reports, 2016)

Novel predictors of soil genesis following natural weathering processes of bauxite residues - Feng Zhu; Shengguo Xue; William Hartley; Ling Huang; Chuan Wu; Xiaofei Li (Environmental Science and Pollution Research, 2016)

Comparison of seven colchicine-induced tetraploid clones with their original diploid clones in purple coneflower (Echinacea purpurea L.) - Rong Chen; Wei-zhen Jiang; Qing-ling Li; Xin-lian Li; Xiao-lu Chen; Yue-sheng Yang; Hong Wu (Euphytica, 2016)

Genome sequencing reveals mechanisms for heavy metal resistance and polycyclic aromatic hydrocarbon degradation in Delftia lacustris strain LZ-C - Wenyang Wu; Haiying Huang; Zhenmin Ling; Zhengsheng Yu; Yiming Jiang; Pu Liu; Xiangkai Li (Ecotoxicology, 2016)

Cannabinoid CB1 receptor signaling dichotomously modulates inhibitory and excitatory synaptic transmission in rat inner retina - Xiao-Han Wang; Yi Wu; Xiao-Fang Yang; Yanying Miao; Chuan-Qiang Zhang; Ling-Dan Dong; Xiong-Li Yang; Zhongfeng Wang (Brain Structure and Function, 2016)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Purification and Identification of a Novel Antimicrobial Protein from the Rabbit Sacculus Rotundus and its Effect on Cellular Immune Function in Mice - Hongwei Chen; Yinglun Li; Junwei Wu; Juan Liu; Qingzhou Huang; Shuyong Wei; Guangwei Zhao; Zhiqiang Zhang; Ling Hua (International Journal of Peptide Research and Therapeutics, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Toxicity of sediment cores from Yangtze River estuary to zebrafish (Danio rerio) embryos - Peipei Wang; Lili Zhang; Li Liu; Ling Chen; Hongwen Gao; Lingling Wu (Environmental Science and Pollution Research, 2015)

Biotransformation of 20(S)-protopanaxatriol by Mucor racemosus and the anti-cancer activities of some products - Guangtong Chen; Hongjuan Ge; Yan Song; Jianlin Li; Xuguang Zhai; Juanjuan Wu; Xiang Ling (Biotechnology Letters, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Upregulation of miR-197 inhibits cell proliferation by directly targeting IGFBP5 in human uterine leiomyoma cells - Jing Ling; Li Jiang; Chenxia Zhang; Jie Dai; Qunying Wu; Jie Tan (In Vitro Cellular & Developmental Biology - Animal, 2015)

Sesamol suppresses the inflammatory response by inhibiting NF-κB/MAPK activation and upregulating AMP kinase signaling in RAW 264.7 macrophages - Xin-Ling Wu; Chian-Jiun Liou; Zih-Ying Li; Xuan-Yu Lai; Li-Wen Fang; Wen-Chung Huang (Inflammation Research, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

Retraction Note to: Identification of gene expression profile in the rat brain resulting from acute alcohol intoxication - Ling-Yu Kong; Guang-Peng Li; Ping Yang; Wei Wu; Jin-He Shi; Xue-Liang Li; Wei-Zhen Wang (Molecular Biology Reports, 2015)

Helicobacter pylori with the Intact dupA Cluster is more Virulent than the Strains with the Incomplete dupA Cluster - Ming-yi Wang; Chen Shao; Jie Li; Ya-Chao Yang; Shao-bo Wang; Jun-ling Hao; Chun-mei Wu; Xiao-zhong Gao; Shi-he Shao (Current Microbiology, 2015)

Identification of differentially expressed genes using digital gene expression profiles in Pyrus pyrifolia Nakai cv. Hosui bud release following early defoliation - Quan-jun Zhang; Shu-tian Tao; Meng Li; Xiao-xiao Qi; Jun Wu; Hao Yin; Jia-lin Deng; Shao-ling Zhang (Tree Genetics & Genomes, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

Pretreatment with lipopolysaccharide attenuates diethylnitrosamine-caused liver injury in mice via TLR4-dependent induction of Kupffer cell M2 polarization - Xianjing Li; Zhuo Wang; Yulian Zou; Ermei Lu; Jingjing Duan; Hongbao Yang; Qijin Wu; Xiaona Zhao; Yun Wang; Linjun You; Ling He; Tao Xi; et al. (Immunologic Research, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Construction of a High-Density Simple Sequence Repeat Consensus Genetic Map for Pear (Pyrus spp.) - Hui Chen; Yue Song; Lei-Ting Li; M. Awais Khan; Xiu-Gen Li; Schuyler S. Korban; Jun Wu; Shao-Ling Zhang (Plant Molecular Biology Reporter, 2015)

Analysis of Cancer Marker in Tissues with Hadamard Transform Fluorescence Spectral Microscopic Imaging - Hao Xu; Chuang Chen; Yue He; Hong-Wu Tang; Zhi-Ling Zhang; Yan Li; Dai-Wen Pang (Journal of Fluorescence, 2015)

Effect of Concussion on Inter-joint Coordination During Divided-Attention Gait - Hao-Ling Chen; Tung-Wu Lu; Li-Shan Chou (Journal of Medical and Biological Engineering, 2015)

RETRACTED ARTICLE: Identification of gene expression profile in the rat brain resulting from acute alcohol intoxication - Ling-Yu Kong; Guang-Peng Li; Ping Yang; Wei Wu; Jin-He Shi; Xue-Liang Li; Wei-Zhen Wang (Molecular Biology Reports, 2014)

Assessment of trace element contamination in sediment cores from the Pearl River and estuary, South China: geochemical and multivariate analysis approaches - Yongqiang Yang; Zhuli Liu; Fanrong Chen; Shijun Wu; Ling Zhang; Mingliang Kang; Jie Li (Environmental Monitoring and Assessment, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Cadmium Neurotoxicity to a Freshwater Planarian - Jui-Pin Wu; Hui-Ling Lee; Mei-Hui Li (Archives of Environmental Contamination and Toxicology, 2014)

Association between serum vitamin D and severity of liver fibrosis in chronic hepatitis C patients: a systematic meta-analysis - Yue-qiu Luo; Xiao-xing Wu; Zong-xin Ling; Yi-wen Cheng; Li Yuan; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2014)

An enhanced MEMS-INS/GNSS integrated system with fault detection and exclusion capability for land vehicle navigation in urban areas - Ling Yang; Yong Li; Youlong Wu; Chris Rizos (GPS Solutions, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Is right ventricular mid-septal pacing superior to apical pacing in patients with high degree atrio-ventricular block and moderately depressed left ventricular function? - Kang Chen; Ye Mao; Shao-hua Liu; Qiong Wu; Qing-zhi Luo; Wen-qi Pan; Qi Jin; Ning Zhang; Tian-you Ling; Ying Chen; Gang Gu; Wei-feng Shen; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

INS-1 cells inhibit the production of extracellular matrix from pancreatic stellate cells - Fengfei Li; Bijun Chen; Ling Li; Min Zha; S. Zhou; Tongzhi Wu; M. G. Bachem; Zilin Sun (Journal of Molecular Histology, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Positive matrix factorization as source apportionment of soil lead and cadmium around a battery plant (Changxing County, China) - Jian-long Xue; Yu-you Zhi; Li-ping Yang; Jia-chun Shi; Ling-zao Zeng; Lao-sheng Wu (Environmental Science and Pollution Research, 2014)

A new modified sesquiterpene glycoside from Cupressus chengiana - Yan Lin; Rong-Jiao Li; Yan Li; Brian D. McGarvey; Hai-Feng Wu; Xiao-Ling Wang (Natural Product Research, 2014)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Mega-shoaling in carbonate platform of the Middle Triassic Leikoupo Formation, Sichuan Basin, southwest China - XiuCheng Tan; Ling Li; Hong Liu; Jian Cao; XiaoQing Wu; SuYan Zhou; XueWen Shi (Science China Earth Sciences, 2014)

Passive Movement Improves the Learning and Memory Function of Rats with Cerebral Infarction by Inhibiting Neuron Cell Apoptosis - Man Li; Jun Peng; Meng-Die Wang; Yan-Ling Song; Yuan-Wu Mei; Yuan Fang (Molecular Neurobiology, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Complete genome sequence analysis of human echovirus 30 isolated during a large outbreak in Guangdong Province of China, in 2012 - Hong Xiao; Keyong Huang; Ling Li; Xianbo Wu; Li Zheng; Chengsong Wan; Wei Zhao; Changwen Ke; Bao Zhang (Archives of Virology, 2014)

Three new olean-type triterpenoid saponins from aerial parts of Eclipta prostrata (L.) - Feng-Min Xi; Chun-Tong Li; Jun-Ling Mi; Zhi-Jun Wu; Wan-Sheng Chen (Natural Product Research, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

The role of sucrose-metabolizing enzymes in pear fruit that differ in sucrose accumulation - Hu Ping Zhang; Ju You Wu; Gai Hua Qin; Gai Fang Yao; Kai Jie Qi; Li Fen Wang; Shao Ling Zhang (Acta Physiologiae Plantarum, 2014)

A 2-yr service report of cell line authentication - Mei-Ling Wu; Li-Chuan Liao; Chiung-Yun Chen; Shin-Ying Lee; Gwo-Fang Yuan; Shiaw-Min Hwang (In Vitro Cellular & Developmental Biology - Animal, 2013)

In vitro binding and bimolecular fluorescence complementation assays suggest an interaction between tomato mosaic virus coat protein and tobacco chloroplast ferredoxin I - Xianchao Sun; Yong Li; Mengdie Shi; Ning Zhang; Gaixia Wu; Tingting Li; Ling Qing; Changyong Zhou (Archives of Virology, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

Genetic variability and evolution of rice stripe virus - Ling-zhe Huang; Li-xia Rao; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2013)

An integrated approach to model the biomagnification of organic pollutants in aquatic food webs of the Yangtze Three Gorges Reservoir ecosystem using adapted pollution scenarios - Björn Scholz-Starke; Richard Ottermanns; Ursula Rings; Tilman Floehr; Henner Hollert; Junli Hou; Bo Li; Ling Ling Wu; Xingzhong Yuan; Katrin Strauch; Hu Wei; Stefan Norra; et al. (Environmental Science and Pollution Research, 2013)

Quantitative trait loci for grain-quality traits across a rice F2 population and backcross inbred lines - Bingyue Lu; Chunyan Yang; Kun Xie; Long Zhang; Tao Wu; Linfang Li; Xi Liu; Ling Jiang; Jianmin Wan (Euphytica, 2013)

Short-chain chlorinated paraffins (SCCPs) in surface soil from a background area in China: occurrence, distribution, and congener profiles - Xue-Tong Wang; Yuan Zhang; Yi Miao; Ling-Ling Ma; Yuan-Cheng Li; Yue-Ya Chang; Ming-Hong Wu (Environmental Science and Pollution Research, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

An AFLP, SRAP, and SSR Genetic Linkage Map and Identification of QTLs for Fruit Traits in Pear (Pyrus L.) - Rui-ping Zhang; Jun Wu; Xiu-gen Li; M. Awais Khan; Hui Chen; Schuyler S. Korban; Shao-ling Zhang (Plant Molecular Biology Reporter, 2013)

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation - Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Yong Wang; Ming Huang; Yan Huang; Jian-Yong Li; Ya-Nan Li; Yuan Gao; Ling Mao; Yuan-Wu Mei; Bo Hu (Molecular Neurobiology, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Decreased PADI4 mRNA Association with Global Hypomethylation in Hepatocellular Carcinoma During HBV Exposure - Changsong Zhang; Lieying Fan; Tingting Fan; Dong Wu; Lu Gao; Yang Ling; Jing Zhu; Rong Li; Lixin Wei (Cell Biochemistry and Biophysics, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

QTL mapping of adult-plant resistances to stripe rust and leaf rust in Chinese wheat cultivar Bainong 64 - Yan Ren; Zaifeng Li; Zhonghu He; Ling Wu; Bin Bai; Caixia Lan; Cuifen Wang; Gang Zhou; Huazhong Zhu; Xianchun Xia (Theoretical and Applied Genetics, 2012)

QTL mapping of adult-plant resistance to stripe rust in a population derived from common wheat cultivars Naxos and Shanghai 3/Catbird - Yan Ren; Zhonghu He; Jia Li; Morten Lillemo; Ling Wu; Bin Bai; Qiongxian Lu; Huazhong Zhu; Gang Zhou; Jiuyuan Du; Qinglin Lu; Xianchun Xia (Theoretical and Applied Genetics, 2012)

The isolation of Pi1, an allele at the Pik locus which confers broad spectrum resistance to rice blast - Lixia Hua; Jianzhong Wu; Caixia Chen; Weihuai Wu; Xiuying He; Fei Lin; Li Wang; Ikuo Ashikawa; Takashi Matsumoto; Ling Wang; Qinghua Pan (Theoretical and Applied Genetics, 2012)

Association of STAT4 rs7574865 polymorphism with autoimmune diseases: a meta-analysis - Ya-ling Liang; Hua Wu; Xi Shen; Pei-qiang Li; Xiao-qing Yang; Li Liang; Wei-hua Tian; Li-feng Zhang; Xiao-dong Xie (Molecular Biology Reports, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Role of Dopamine Receptors in ADHD: A Systematic Meta-analysis - Jing Wu; Haifan Xiao; Hongjuan Sun; Li Zou; Ling-Qiang Zhu (Molecular Neurobiology, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)

Isolation and Characterization of a Temperature-Regulated Microsomal Oleate Desaturase Gene (CtFAD2-1) from Safflower (Carthamus tinctorius L.) - Ling-Liang Guan; Ying-Wen Xu; Yuan-Biao Wang; Li Chen; Jin-feng Shao; Wei Wu (Plant Molecular Biology Reporter, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Effects of average velocity on the growth and surface topography of biofilms attached to the reclaimed wastewater drip irrigation system laterals - Gui Bing Li; Yun Kai Li; Ting Wu Xu; Yao Ze Liu; Hai Jin; Pei Ling Yang; Da Zhuang Yan; Shu Mei Ren; Zhi Fang Tian (Irrigation Science, 2012)

Effects of applied urea and straw on various nitrogen fractions in two Chinese paddy soils with differing clay mineralogy - Shao-Jun Qiu; Pei-Qin Peng; Ling Li; Ping He; Qiang Liu; Jin-Shui Wu; Peter Christie; Xiao-Tang Ju (Biology and Fertility of Soils, 2012)

RCCS enhances EOE cell proliferation and their differentiation into ameloblasts - Ping Li; Ye Zhang; Yan Meng Wang; Cui Mi Duan; Tong Hao; Bu Ling Wu; Chang Yong Wang (Molecular Biology Reports, 2012)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

The conditioned medium from a stable human GDF3-expressing CHO cell line, induces the differentiation of PC12 cells - Qiang Li; Xianghua Liu; Yanhua Wu; Jian An; Saiyin Hexige; Yichen Ling; Mingjun Zhang; Xianmei Yang; Long Yu (Molecular and Cellular Biochemistry, 2012)

Surface topographic characteristics of suspended particulates in reclaimed wastewater and effects on clogging in labyrinth drip irrigation emitters - Yun Kai Li; Yao Ze Liu; Gui Bing Li; Ting Wu Xu; Hai Sheng Liu; Shu Mei Ren; Da Zhuang Yan; Pei Ling Yang (Irrigation Science, 2012)

Facial dermatosis associated with Demodex: a case-control study - Ya-e Zhao; Yan Peng; Xiang-lan Wang; Li-ping Wu; Mei Wang; Hu-ling Yan; Sheng-xiang Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

General depositional features of the carbonate platform gas reservoir of the Lower Triassic Jialingjiang Formation in the Sichuan Basin of southwest China: Moxi gas field of the central basin - Xiucheng Tan; Ling Li; Hong Liu; Bing Luo; Yan Zhou; Jiajie Wu; Xiong Ding (Carbonates and Evaporites, 2011)

Anti-hyperglycemic Activity of Chromium(III) Malate Complex in Alloxan-Induced Diabetic Rats - Xiang-Yang Wu; Fang Li; Wei-Dong Xu; Jiang-Li Zhao; Ting Zhao; Ling-Hong Liang; Liu-Qing Yang (Biological Trace Element Research, 2011)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

A high-throughput method for screening of Aspergillus niger mutants with high transglycosylation activity by detecting non-fermentable reducing sugar - Gui-guang Chen; Wei Li; Yun-kai Zhang; Yong-ling Qin; Kong-yang Wu; Zhi-qun Liang (World Journal of Microbiology and Biotechnology, 2011)

Physiological significance of P2X receptor-mediated vasoconstriction in five different types of arteries in rats - Lu Li; Zhen-Hua Jia; Chao Chen; Cong Wei; Jian-Ke Han; Yi-Ling Wu; Lei-Ming Ren (Purinergic Signalling, 2011)

Characterization of 68Zn uptake, translocation, and accumulation into developing grains and young leaves of high Zn-density rice genotype - Chun-yong Wu; Ying Feng; Md. Jahidul Islam Shohag; Ling-li Lu; Yan-yan Wei; Chong Gao; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2011)

Variations of PM10 concentrations in Wuhan, China - Qi Feng; Shengjun Wu; Yun Du; Xiaodong Li; Feng Ling; Huaiping Xue; Shuming Cai (Environmental Monitoring and Assessment, 2011)

Systematic analysis of gene expression level with tissue-specificity, function and protein subcellular localization in human transcriptome - Qiang Li; Xianghua Liu; Quanyuan He; Lei Hu; Yichen Ling; Yanhua Wu; Xianmei Yang; Long Yu (Molecular Biology Reports, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Spectroscopic Studies on the Thermodynamics of L-Cysteine Capped CdSe/CdS Quantum Dots—BSA Interactions - Ling Ding; P. J. Zhou; S. Q. Li; G. Y. Shi; T. Zhong; M. Wu (Journal of Fluorescence, 2011)

A nested PCR assay targeting the DNA topoisomerase I gene to detect the pine wood nematode, Bursaphelenchus xylophilus - Lin Huang; Xu-ling Xu; Xiao-qin Wu; Feng-mao Chen; Chao Li; Jian-ren Ye (Phytoparasitica, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Characterization of a novel human CDK5 splicing variant that inhibits Wnt/β-catenin signaling - Qiang Li; Xianghua Liu; Mingjun Zhang; Guangming Ye; Qian Qiao; Yichen Ling; Yanhua Wu; Yuanyuan Zhang; Long Yu (Molecular Biology Reports, 2010)

Cloning and Characterization of Functional Trehalose-6-Phosphate Synthase Gene in Maize - Wei Jiang; Feng-Ling Fu; Su-Zhi Zhang; Ling Wu; Wan-Chen Li (Journal of Plant Biology, 2010)

Analysis of two sequence variants in peroxisome proliferator activated receptor gamma gene in Tajik population at high altitudes and Han population at low altitudes in China - Xiao-Ling Liu; Feng-Lin Zhang; Zhi-Yong Zhou; Hua-Lu Zhao; Guo-Min Shen; Wu-Yun Baohan; Zi-Yuan Duan; Wei Li; Jun-Wu Zhang (Molecular Biology Reports, 2010)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

OsMT1a, a type 1 metallothionein, plays the pivotal role in zinc homeostasis and drought tolerance in rice - Zhao Yang; Yaorong Wu; Ye Li; Hong-Qing Ling; Chengcai Chu (Plant Molecular Biology, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

A population-based, case–control study of green tea consumption and leukemia risk in southwestern Taiwan - Yau-Chang Kuo; Chu-Ling Yu; Chen-Yu Liu; Su-Fen Wang; Pi-Chen Pan; Ming-Tsang Wu; Chi-Kung Ho; Yu-Shing Lo; Yi Li; David C. Christiani (Cancer Causes & Control, 2009)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)

Arsenic exposure, urinary arsenic speciation, and the incidence of urothelial carcinoma: a twelve-year follow-up study - Yung-Kai Huang; Ya-Li Huang; Yu-Mei Hsueh; Mo-Hsiung Yang; Meei-Maan Wu; Shu-Yuan Chen; Ling-I Hsu; Chien-Jen Chen (Cancer Causes & Control, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Environmental change inferred from Rb and Sr of lacustrine sediments in Huangqihai Lake, Inner Mongolia - Lei Chen; Hongyuan Shen; Yulian Jia; Jinglu Wu; Xusheng Li; Ling Wei; Pengling Wang (Journal of Geographical Sciences, 2008)

Zero erucic acid trait of rapeseed (Brassica napus L.) results from a deletion of four base pairs in the fatty acid elongase 1 gene - Gang Wu; Yuhua Wu; Ling Xiao; Xiaodan Li; Changming Lu (Theoretical and Applied Genetics, 2008)

Bone regeneration by BMP-2 enhanced adipose stem cells loading on alginate gel - Yunfeng Lin; Wei Tang; Ling Wu; Wei Jing; Xiaoyu Li; Yao Wu; Lei Liu; Jie Long; Weidong Tian (Histochemistry and Cell Biology, 2008)

Ectopic adipogenesis of preconditioned adipose-derived stromal cells in an alginate system - Wei Jing; Yunfeng Lin; Ling Wu; Xiaoyu Li; Xin Nie; Lei Liu; Wei Tang; Xiaohui Zheng; Weidong Tian (Cell and Tissue Research, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Kinetic and equilibrium studies of copper biosorption onto Pseudomonas aeruginosa base using direct determination of copper by a voltammetric method - Xuefang Li; Wanzhi Wei; Xiandong Zeng; Jinxiang Zeng; Jian Yin; Ling Wu (World Journal of Microbiology and Biotechnology, 2007)

A genetically engineered Escherichia coli, expressing the fusion protein of green fluorescent protein and carboxylesterase B1, can be easily detected in the environment following degradation of pesticide residues - Qin Li; Rui Chen; Wei Li; Chuan-Ling Qiao; Yi-Jun Wu (Biotechnology Letters, 2007)

Multiplex specific PCR for identification of the genera Actinopolyspora and Streptomonospora, two groups of strictly halophilic filamentous actinomycetes - Xiao-Yang Zhi; Ling-Ling Yang; Jin-Yuan Wu; Shu-Kun Tang; Wen-Jun Li (Extremophiles, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Pluripotency potential of human adipose-derived stem cells marked with exogenous green fluorescent protein - Yunfeng Lin; Lei Liu; Zhiyong Li; Ju Qiao; Ling Wu; Wei Tang; Xiaohui Zheng; Xizhe Chen; Zhengbin Yan; Weidong Tian (Molecular and Cellular Biochemistry, 2006)

Phylogenetic Relationships and Possible Hybrid Origin of Lycoris Species (Amaryllidaceae) Revealed by ITS Sequences - Shude Shi; Yingxiong Qiu; Enxiang Li; Ling Wu; Chengxin Fu (Biochemical Genetics, 2006)

Study on Chromium (VI) Reduction Kinetics by Pseudomonas aeruginosa Using a Combined System of Acoustic Wave Impedance Analyzer and UV-Vis Spectrophotometer - Xuefang Li; Wanzhi Wei; Xiandong Zeng; Deliang He; Jian Yin; Jinxiang Zeng; Ling Wu (Current Microbiology, 2006)

Polyacetylenes Function as Anti-Angiogenic Agents - Li-Wha Wu; Yi-Ming Chiang; Hsiao-Ching Chuang; Sheng-Yang Wang; Ga-Wen Yang; Ya-Huey Chen; Ling-Ya Lai; Lie-Fen Shyur (Pharmaceutical Research, 2004)

Cloning and localization of vip3A gene of Bacillus thuringiensis - Zeng Ling Wu; Wen Yi Guo; Jun Zhi Qiu; Tian Pei Huang; Xun Bo Li; Xiong Guan (Biotechnology Letters, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

Forskolin up-regulates metastasis-related phenotypes and molecules via protein kinase B, but not PI-3K, in H7721 human hepato-carcinoma cell line - Shi-liang Wu; Jun Ma; Hui-ling Qi; Ying Zhang; Xia-ying Zhang; Hui-li Chen (Molecular and Cellular Biochemistry, 2003)

Polymorphic tetranucleotide repeat site within intron 7 of the β-amyloid precursor protein gene and its lack of association with Alzheimer's disease - Ling Li; Rodney Perry; Jianming Wu; D. Pham; Tauni Ohman; Lindy E. Harrell; Rodney C. P. Go; K. Fukuchi (Human Genetics, 1998)

Simulating study on barchan dune - Yuquan Ling; Zheng Wu; Shaozhong Liu; Changzhi Li (Chinese Geographical Science, 1998)